Correction: The Dual Roles of TIMP-1 in Cancer: From Protease Inhibition to Cytokine Signaling - Haixia Li; Xinzhou Deng; Fang Wang; Yanlin Niu; Pengfei Ruan; Li Gong; Ming Luo; Zhiguo Luo; Nan Cao (Molecular Biology Reports, 2026)

The Dual Roles of TIMP-1 in Cancer: From Protease Inhibition to Cytokine Signaling - Haixia Li; Xinzhou Deng; Fang Wang; Yanlin Niu; Pengfei Ruan; Li Gong; Ming Luo; Zhiguo Luo; Nan Cao (Molecular Biology Reports, 2026)

E3 Ligase KPC1 promotes sepsis-induced liver injury via ubiquitination and processing of NF-κB1 p105 in kupffer cells - Lin Chai; Xiaoyu Liu; Ming Luo; Ling Li; Shubin Guo (Tissue and Cell, 2026)

Global fungal diversity and biomass in anoxic wetlands - Xi Luo; Jianjun Xu; Fei Yang; Jinquan Li; Bo Li; Changming Fang; Guoqing Zhang; Ming Nie (Soil Biology and Biochemistry, 2026)

Sex peptide receptor modulates sex pheromone perception plasticity in female Galleria mellonella across mating status - Zhen-Ping Guo; Xu-Dong Pang; Li-Lin Luo; Ming-Qing Yu; Jun-Hong Linghu; Hua-Yan Xie; Guy Smagghe; Tong-Xian Liu; Shun-Hua Gui (Insect Biochemistry and Molecular Biology, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

A deep learning and generative modeling pipeline for mining and engineering alkaline-stsable xylanases - Ruohan Zhang; Yiyang Zhang; Zhonghao Deng; Pengtao Wang; Lingxi Fan; Feng Guo; Huiying Luo; Yuan Wang; Tao Tu; Bin Yao; Jian Tian; Huoqing Huang; et al. (Bioresource Technology, 2026)

Comparative study of the transient response and failure characteristics of lined tunnels under idealized and realistic plane P-wave seismic excitation - Hao Luo; Ming Tao; Hiroyuki Noda; Xibing Li; Chengqing Wu (Tunnelling and Underground Space Technology, 2026)

Hydrodynamic response of a planar debris-interception netting with different blocking patterns due to wave-current combination - Yue Song; Yuchen Zhang; Ming He; Suifeng Luo; Zhenxiang Sun; Chengyue Li (Ocean Engineering, 2026)

Integrated strategy for genistein production from soybean meal: Microbial mining, enzymatic mechanism, and temperature-adaptable solid-state fermentation - Hang Xu; Li-Ming Luo; Hao-Nan Cao; Hao An; Jian-Gong Duan; Yong-Xing He; Hao Yang (Journal of Environmental Chemical Engineering, 2026)

Multi-level biomarker responses in Eisenia fetida co-exposed to PE-MPs and DiBP: An ecological risk assessment based on physiological, biochemical, and molecular indicators - Yanan Zhang; Yumu Luo; Zhensi Meng; Jun Luo; Ke Li; Yuhang Lin; Minle Li; Rongren Bin; Mingming Fu; Ming Hung Wong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2026)

A lyophilized RPA–CRISPR/Cas13d one-pot platform for rapid detection of porcine circovirus type 3 - Li-Na Shao; Zheng-Luo; Bao-Ling Liu; Tong-Xu; Yuan-Meng Wang; Jia-Qi Duan; Lei-Zhao; You-You Li; Yang-Ming Dai; Qin-Rui Jia; Le-Yi Zhang; Ling-Zhu; et al. (Analytica Chimica Acta, 2026)

Continental crustal growth in collisional orogens: Insights from the Triassic granitoids in East Kunlun, NW China - Wen-Jia Wang; Xiao-Wei Li; Yang-Ming Hu; Yong Zhang; Shuang Dai; Da-Ming Zhang; Dong-Bao Guo; Chang-Hai Luo; Juan Shen; Cheng-Yong Wang; Wei-Ming Ma (Lithos, 2026)

Novel Streptomyces sp. SCUT-3 promoter’ and 5’UTR chimeras enhanced its alginate lyase expression for kelp degradation - Jun Dai; Hai-Ning Wang; Can Qin; Peng-Bo Dan; Jun-Jin Deng; Lei Wu; Zhi-Wei Li; Fu-Gen Zhang; Chu-Yan Liang; Ming-Shu Zhang; Xiao-Chun Luo (Chemical Engineering Journal, 2026)

One novel sesquiterpenoid from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Zi-Lin Wang; Shuai-Ming Zhu; Yu Yang; Rui Xu; Xue Zhao; Chen Sun; Qian Luo; You-Zhi Zhang; Guo-Gang Zhang; Chang-Wei Li (Natural Product Research, 2026)

Baicalin alleviates repeated superovulation induced ovarian dysfunction and oocyte impairment by suppressing excessive glycolysis - Lin-Feng Li; Hao Shen; Zhi-Min Qi; Tian Luo; Sheng-Ming Liu; Li-Li Ou; Chang-Long Xu; Yu Liu (Theriogenology, 2026)

A star’s death by a thousand cuts: the runaway periodic eruptions of AT2023uqm - Yibo Wang; Tinggui Wang; Shifeng Huang; Jiazheng Zhu; Ning Jiang; Wenbin Lu; Rongfeng Shen; Shiyan Zhong; Dong Lai; Yi Yang; Xinwen Shu; Tianyu Xia; et al. (Science Bulletin, 2026)

Aging of buried polyvinyl chloride sewer pipes and microplastics release: Mechanisms and environmental risks - Yuanling Luo; Yuting Ding; Xiya Ao; Xiaoxi Liao; Haiyin Xu; Yin Zhang; Ming Huang; Meiying Jia; Xinjiang Hu; Min Ruan; Erping Li; Jia Yang (Journal of Environmental Chemical Engineering, 2026)

Below-ground crop yields respond twice as strongly as above-ground crop yields to greenhouse CO2 enrichment - Jiejie Sun; Tongli Wang; Chunchen Li; Thomas Andrew Black; Jing Qian; Wenhuan Xu; Yu-xi Feng; Dawei Luo; Xuan Xu; Xiaodong Hu; Danyang Cao; Jiaen Zhang; et al. (European Journal of Agronomy, 2026)

Direct quantification of thallium(I) in water by ESI-MS via supramolecular recognition with cryptand[2.2.2] - Hai Li; Ping Guo; Min Li; Ming Ma; Wei Luo; Bo Chen (Analytica Chimica Acta, 2026)

Integrated transcriptomic and metabolomic analysis reveals the effect of OPP film packaging on ‘Huapi Kumquat’ quality during low-temperature storage - Linliang Wang; Yanhui Wang; Zongbo Jiang; Chunxiu Pang; Chunmei Feng; Ming Chen; Chaodan Luo; Xiyu Zhang; Yewei Tan; Wentao Xu; Xinrong Li (Postharvest Biology and Technology, 2026)

Systematic characterization of FBP gene family in Saccharum reveals ScFBP3 as a key regulator of sucrose-mediated plant branching - Huiwen Zhou; Hanmin Luo; Minyi Wei; Ting Luo; Faqian Xiong; Ming Li; Lihang Qiu; Haifeng Yan (Plant Science, 2026)

Supplementing with vitamin B6 during the active phase can promote digestion, enhance intestinal barrier integrity, and accelerate the maturation of ileum flora in juvenile mice - Ya-Xin Liu; Jin-Hao Pang; Li-Ping Chen; Fei Huan; Qing-Mei Liu; Meng Liu; Yan-Ling Hao; Chen-Hong Zhang; Lian-Zhong Luo; Guang-Ming Liu (Food Bioscience, 2026)

Maternal inulin intervention ameliorates lipid metabolism disorders in offspring induced by a high-fat diet before or during pregnancy via the gut-liver-adipose axis - Bing Chen; Jia Wu; Xiaole Cui; Yaxing Miao; Lingling Li; Kaixin Su; Changchun Liu; Yane Luo; Ming Du; Wei Song (Food Bioscience, 2026)

Electro-chemo-mechanically stable semi-interpenetrating interphase customization for prolonged Zn metal anodes - Jianhui Zhu; LongJun He; Jianbin Ruan; Hongying Li; Chenglong Xu; Ming Yang; Guomin Li; Yanyi Wang; Jingting Luo; Jinlai Zhao; Dingtao Ma; Peixin Zhang (Chemical Engineering Journal, 2026)

Molecularly integrated dynamic chitosan network with topology-adaptive glucose/ROS responsiveness for coupled drug release and immunoregulation - Yuxiang Li; Sheng Dong; Ran Yu; Runjie Liu; Hengxi Xu; Hainuo Li; Wenbo Ming; Guochao Liao; Rong Zhang; Zhongqiu Liu; Wenxian Wang; Xiang Luo; et al. (Chemical Engineering Journal, 2026)

Eco‐morphodynamic response of deltaic salt marshes to successive extreme storms - Jie Wang; Ming Shi; Zhijun Dai; Huan‐Feng Duan; Xuefei Mei; Wen Wei; Jiejun Luo; Weihua Li; Sergio Fagherazzi (Limnology and Oceanography, 2026)
Deltaic salt marshes deliver crucial ecosystem services, including wave and flooding attenuation, making them key components of coastal nature‐based solutions. However, their sustainability under climate change remains poorly understood, particularly regarding cumulative impacts from successive extreme weather events in regions with declining fluvial sediment supply. Here, we investigate the recovery capacity of deltaic salt marshes following successive extreme storms. We leverage in‐situ data on intertidal hydrodynamics, bed elevation changes, and marsh vegetation dynamics, collected during typhoon and cold wave events in the East Chongming Wetland, the largest open tidal wetland in the Changjiang (Yangtze) Delta, China. Our results demonstrate that both typhoons and cold waves enhanced intertidal hydrodynamic forcing (inundation depth, wave energy, and tidal currents) and suspended sediment concentrations in vegetated areas, resulting in mean net bed erosion of 2.98 and 4.82 cm, respectively. The total salt marsh area decreased by 15.7% (from 7.05 × 10 5 to 5.94 × 10 5 m 2 ) after the storms, with fragmentation increasing 50.8% between 2022 and 2023. Elevation‐dependent responses generated two distinct bands of alongshore marsh erosion and vegetation loss. Cold waves caused particularly severe impacts through combined hydromechanical stress and belowground tissue damage from rapid temperature cooling. These findings reveal compounding stressors from sequential extreme hydrometeorological events that threaten the recovery of exposed salt marshes, providing critical insights for nature‐based coastal protection and disaster adaptation strategies.

A Lepidoptera Synthesis Phylogeny of 11,001 Species and Its Application in Phylogenetic Profiling of Herbivore DNA Barcodes: Towards an Integrative Phylogenetic Framework for Insects - Douglas Chesters; Ming‐Qiang Wang; Perttu Anttonen; Jing‐Ting Chen; Rui Cheng; Yi Li; Arong Luo; Michael C. Orr; Tingting Xie; Qingsong Zhou; Chao‐Dong Zhu (Zoologica Scripta, 2026)
We herein constructed a phylogeny of Lepidoptera synthesizing multiple information types, a phylogenomics backbone, a multigene supermatrix with species‐comprehensive DNA barcodes, and topological information from a compiled database of standardized machine‐readable trees from over 100 previous studies. We then applied the new phylogenetic synthesis as a profiling framework for a large DNA barcode dataset of caterpillars from a tree diversity experiment. The synthesis phylogeny comprised 11,001 species. Phylogenetic information content was taxonomically skewed towards butterflies (i.e., Nymphalidae, Papilionidae and Pieridae), and parts of Macroheterocera (Geometridae, Sphingidae, Saturniidae and Bombycidae), while undersampling of Lepidoptera species diversity was present in Erebidae, Noctuidae, Gelechioidea and Pyraloidea. Caterpillar Phylogenetic Diversity (PD) increased with tree richness in the diversity experiment regardless of processing choices in calculating caterpillar PD, including whether calculated on plot OTU alone, plot OTU placed onto a simple reference phylogeny or plot OTU placed to the comprehensive reference phylogeny. Stronger correlations between tree diversity and uncorrected Faith's PD of caterpillars were observed where OTU were placed onto the full reference tree, and where long branch OTU were removed prior to PD calculation, though no significant differences in the strength of the tree diversity effect across context and processing choice were observed for standardized PD. In calculation of plot‐level PD, focus should remain on community sample size, with the results herein supporting the use of any available reference phylogeny as context, though correspondence of PD indices to environmental gradients might be stronger where plot OTU can be placed to a comprehensive reference phylogeny. The phylogeny presented herein enables inference of varied evolutionary information for Lepidoptera DNA barcode sets.

Virulensome: a transient organelle mediating fungal virulence - Pei-Ji Zhao; Qian-Yi Hu; Si-Han Wang; Cheng-Song Wang; Xue-Xian Jian; Xing-Fu Wen; Yu-Lin Luo; Ya-Qi Zhang; Chun-Mei Xiang; Guo-Hong Li; Shu-Qun Liu; Ming-He Mo; et al. (Science China Life Sciences, 2026)

Temporal transcriptomic profiling identifies core regulators in cytokine-induced gut barrier disruption in differentiated Caco-2 cells - Hyo Shin Yoon; Shining Ma; Matt Kanke; Wan-Jung Wu; Uyen Hoang; Jessica A. Tan; Alex Wilks; Priyanka Patel; Sundeep Chandra; Xin Luo; Daniel Lu; Scott Martin; et al. (Inflammation Research, 2026)
Objective The intestinal epithelial barrier maintains gut homeostasis, and its disruption contributes to inflammatory diseases such as Inflammatory Bowel Diseases (IBD). Although barrier restoration is a promising therapeutic strategy, most current approaches target immune responses rather than epithelial function. Since barrier injury and repair progress through discrete phases, this study aimed to define time-resolved epithelial transcriptional programs and identify candidate regulatory nodes for barrier-focused therapeutic intervention. Methods Differentiated Caco-2 epithelial monolayers were used to model cytokine-induced barrier disruption and profiled by time-resolved bulk RNA-seq. Transcriptional dynamics and candidate regulators were identified using pairwise differential expression, likelihood-ratio testing, pathway enrichment, and upstream-regulator inference. Candidate nodes were tested by pharmacologic perturbation, and disease relevance was assessed by qPCR and histology in human IBD colon tissues. Results Time-resolved profiling revealed dynamic epithelial programs involving the Rho GTPase cycle, sirtuin signaling, non-canonical WNT signaling, and junction/EMT-associated pathways. Upstream-regulator inference highlighted JAK2, TNF, gasdermin D, and β-estradiol, and pharmacologic perturbation of these nodes mitigated cytokine-induced barrier loss. HNF4A emerged as a gut epithelial transcriptional hub regulating targets including SATB2 and SLC26A3. Notably, SLC26A3 was markedly reduced in IBD colon tissues. Conclusions This study provides a time-resolved epithelial framework and highlights therapeutic opportunities for barrier-focused interventions.

Genetic effects on feeding habits: An integrated analysis of intestinal histomorphology, digestive enzyme activities, and multi-omics in hybrids from Micropterus salmoides ♀ × Lepomis cyanellus ♂ - Haitao Zhong; Chiye Zhao; Chaoying Luo; Zheduo Xiong; Yan Li; Hong Chen; Mingli Liu; Yilin Wu; Yuheng Wang; Chun Zhang; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2026)

Climate stability shaped fire regimes over the past ∼1400 years in northeastern China - Yufeng Yuan; Xin Zhou; Yong Luo; Anze Chen; Lize Meng; Changchun Huang; Lian Liu; Xiaoyan Liu; Hongfei Zhao; Shiwei Jiang; Xuanqiao Liu; Ming Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Chemical constituents with chemotaxonomic significance from the whole plants of Chloranthus sessilifolius K.F.Wu - Xin-Yu Chen; Meng-Li He; Wan-Wan Yu; Yang Liu; Yong-Ming Luo; Ling-Ying Huang; Zhi-Ping Li; Fang-You Chen (Biochemical Systematics and Ecology, 2026)

Metabolic inflexibility across heart failure phenotypes: mechanisms and type-specific therapeutic implications - Li Chen; Xin-Rui Yang; Yan Jiang; Shi-Qi Cheng; Zhen-Xun Wan; Jin-Wen Wu; Ming-Tai Chen; Yuan-Yuan Li; Gang Luo; Meng-Nan Liu (Apoptosis, 2026)

A NIR Molecular-level Framework Tracks Mercury Ions via Fast and Real-time Determination in Real Samples and Live Cells - Miaoyuan Zhang; Xiaole Chen; Zhijie Luo; Xiangqian Li; Jia Jiang; Jie Deng; Ming Lu; Fuhao Liu; Qianming Wang (Journal of Fluorescence, 2026)

Underestimated legacy of historical metallurgy and modern contamination transformation in southwestern China: insights from crater lake sediments - Wanping Shi; Shiwei Jiang; Yong Luo; Yiyan Chen; Ming Ji; Hongfei Zhao; Xuanqiao Liu; Liqiang Xu; Xiangzhong Li; Zhuoya Zhang; Xin Zhou (Environmental Pollution, 2026)

Effects of mineralization environments on CO₂ capture by Zr/Mg doped calcium-based sorbents and DFT calculation - Jianjun Cai; Qianlang Liang; Qianru Li; Ming Luo (Chemical Engineering Journal, 2026)

Corrigendum to “Ultraviolet-induced Glycyrrhiza polysaccharide hydrogels with different mechanical strength for wound management” [Carbohydrate Polymers 374 (2026) 124712] - Zhuxian Wang; Ming Luo; Lehuan Ni; Yimeng Li; Dan Liu; Hongxia Zhu; Bijun Xia; Yuanyuan Liu; Qiang Liu; Bin Yang (Carbohydrate Polymers, 2026)

Berberine Hydrochloride Enhances the Fluconazole Susceptibility of Candida albicans through Multiple Targets - Lu Yu; Weijia Yi; Wenming Zheng; Dongming Zheng; Jiaqi Li; Lihua Luo; Guining Luo; Ming Xia; Li You; Jiangyan Yong (Current Microbiology, 2026)

The combination of Astragalus membranaceus and Lycium barbarum polysaccharides is superior to either alone in enhancing growth and health of grass carp (Ctenopharyngodon idellus) - Wei Zhang; Lin Ma; Yi-Geng Meng; Ke-Ming Liu; Hong-Qing Sun; Chao Cai; Ming-Ze Li; Yuan-Yuan Dai; Wen-Wen Li; Xin Luo; Nan Li (Animal Feed Science and Technology, 2026)

Detecting extralateral mass variations using inclined satellite pair configurations - Tiantian Qing; Hao Zhou; Ming Li; Le Suo; Zhu Zhu; Mingyang Xia; Yaozong Li; Lijun Zheng; Shuyun Zheng; Siyou Xu; Zhicai Luo (Advances in Space Research, 2026)

Integrated UHPLC-mS/mS analysis, spectrum-effect relationship, and molecular docking to study the antidiabetic components of Cyclocarya paliurus - Dan-Dan Zhang; Ming-Hua Hu; Zhen Luo; Yu-Ying Yang; Hui-Jun Li; Xin-Yao Luo; Qiong Wei; Xiao-Chuan Ye (Natural Product Research, 2026)

Apoptosis and FoxO signaling axis form the core antiviral defense in mud crab (Scylla paramamosain) against MCRV - Xiaoyu Wang; Liangyu Chen; Jing Peng; Zixuan Luo; Ming Zhang; Qian Sun; Ngoc Tuan Tran; Xianliang Zhao; Yueling Zhang; Zhixun Guo; Shengkang Li (Aquaculture, 2026)

The catalytic subunit of cAMP-dependent protein kinase in Taenia solium cysticerci (TsPKA-c): A promising molecular target for the development of novel anti-cysticercosis therapeutics - Li-Qun Wang; Guang-Xue Liu; Pan-Hong Liang; Li Li; Tao-Shan Li; Ai-Ming Guo; Tharheer Oluwashola Amuda; Ke-Ke Wu; Yi-Xuan Wu; Hong Yin; Hong-Bin Yan; Xue-Nong Luo (Veterinary Parasitology, 2026)

Real-time sensing of hourly human thermal comfort by integrating AI, satellite images, and ground observations - Zhaohua Liu; Zhongyuan Li; Zhaoliang Zeng; Ming Luo; Ruqing Zhu; Yaqiang Wang (Remote Sensing Applications: Society and Environment, 2026)

Experimental study on yield–slip characteristics during shutdown–restart of deepwater high-wax oil–water pipelines - Jinghua Chen; Wenlong Liu; Pengcheng Li; Ming Zhang; Zhenyu Zhu; Qi Xiang; Jianheng Chen; Xiaoming Luo (Ocean Engineering, 2026)

Multidimensional evidence of the positive effects of land use on plant biodiversity in the Hengduan Mountains - Yu Huang; Peng Luo; Honglin Li; Hao Yang; Wenwen Xie; Chuan Luo; Honghong Jia; Yue Cheng; Ming Ni; Zhixiang Sun; Zhouyu Luo; Jiang He (Journal of Environmental Management, 2026)

MOF-based nanozyme incorporated composite film with prominent antibacterial activity and multiple functionalities for fruit preservation - Yiyi Shi; Mengmeng Pan; Yan Wei; Wanchun Luo; Ying Ma; Liyun Ma; Ming Jiang; Feng Liu; Xu Yu; Li Xu (Food Chemistry, 2026)

School greenspace and myopia incidence and burden in Chinese children and adolescents: The Guangzhou children and adolescents cohort study - Xiao-Qi Zhu; Yi Sun; Rong Lin; Ya-Na Luo; Jia-Xin Li; Yi-Dan Zhang; Michael S. Bloom; Matthew H.E.M. Browning; Sam SS. Lau; Shu-Jun Fan; Zhi-Qi Li; Ming-Deng Xiang; et al. (Environmental Research, 2026)

Rhubarb-derived extracellular vesicles co-delivered with dexamethasone via multi-layered assembly nanostrategy for targeted ulcerative colitis therapy - Kun Wang; Mengqi Shen; Xu Luo; Lin Li; Ming Wu; Xiaotong Zhang; Huilin Zhu; Qian Du (Chemical Engineering Journal, 2026)

Case study of aircraft icing in-cloud measurements and explicit supercooled water prediction in Eastern China - Liping Luo; Ming Xue; Xin Xu; Lin Deng; Junxia Li; Rong Zhang (Atmospheric Research, 2026)

Impacts of urbanization on soil fungal communities in Guangzhou, China: Changes in composition, functional groups, community assembly, and network properties - Shitao Xu; Kexin Wang; Fangjie Luo; Caimao Luo; Jing Luo; Binger Li; Yiran Xu; Siwei Ye; Linjing Yu; Yiyuan Cao; Ming Li; Yongjian Chen (Urban Ecosystems, 2026)

Accelerating Sugarcane Breeding with Machine Learning: A Concurrent Multi-trait Predictive Approach - Haichuan Fan; Jing Chao; Xiaoyan Liu; Pengcheng Ma; Guanghu Zhu; Ming Li; Rui Yan; Xinyi Li; Yan Jing; Fengbing Li; Ting Luo; Prakash Lakshmanan (Sugar Tech, 2026)
A large and highly polyploid genome, long breeding cycles, low narrow-sense heritability of yield and its components, and persisting yield stagnation continue to challenge sugarcane variety improvement through both conventional and molecular breedings. To address this, this study developed an efficient phenotype-based concurrent multi-trait prediction framework using artificial intelligence, leveraging 2700 parent combinations and their offspring field performance data from the Sugarcane Research Institute of Guangxi Academy of Agricultural Sciences. Five machine learning paradigms were selected based on data characteristics: tree-based models (GBDT, XGBoost) for structured tabular data and nonlinear trait interactions; attention-based tabular models (TabTransformer, TabNet) for subtle cross-trait dependencies; and an MLP as a baseline. All models were optimized via 80/20 stratified train–test split, class-weighted loss, and cross-validated grid search. GBDT achieved the best overall performance with a macro F 1 score of 0.7316, Hamming loss of 0.2052, and sample accuracy of 0.5630, excelling in predicting sucrose content, cane yield, and smut resistance. XGBoost performed comparably, while TabTransformer offered complementary advantages with a higher F 1 score (0.6829) on overall agronomic performance. These results indicate the potential of using artificial intelligence (AI), particularly machine learning (ML), to increase the predictive power and robustness through integrated AI approaches in the future. This phenotype-based framework shows the value of ML as an efficient decision support tool that can help breeders prioritize cross combinations and optimize resource use, thereby reducing reliance on extensive field trials. While the potential of AI in accelerating variety development is evident, its routine application in real-world commercial breeding requires validation.

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

3D MPM simulation of the coseismic Daguangbao landslide with a state-dependent frictional weakening model - Xiaoqin Lei; Lei Zhu; Siming He; Xinpo Li; Liu Ming; Yu Luo (Landslides, 2026)

Chronic Excessive Exposure to Fluoride Impairs the Intestinal Mucosal Barrier to Cause Inflammatory Response and Microbiome Dysbiosis in Rats - Jia-Rong Zhang; Yi-Wen Li; Hong-Xuan Chen; Yi Luo; Ru-Ming Liu; Jian-Bin Wang; Ning-Ning Liu; Jian-Hui Xiao (Biological Trace Element Research, 2026)

Amplified deviation flood index (ADFI) for fast non-prior flood detection - Hui Zhang; Ming Luo; Zhixin Qi; Xing Li; Yongquan Zhao (Remote Sensing of Environment, 2026)

Subspecies-specific epigenetic remodeling drives differential cold adaptation in geng/xian rice - Dong-Ao Li; Xiao-Long Xu; Yu-Hong Luo; Zu-Wen Zhou; Yong-Qing Qian; Qian Tang; Xi-Tong Zhu; Jia-Ming Song; Ling-Ling Chen (Plant Science, 2026)

Three-dimensional WFAM for unsaturated hydraulic conductivity measurement: Theoretical derivation and numerical validation - Xiao-kang Li; Yuan-ming Lai; Xu Li; Wen-zhen Tang; Qin-guo Ma; Xiao-xiao Luo; Lun-yang Zhao (Journal of Hydrology, 2026)

Functional divergence in the rhizosphere microbiome of Codonopsis pilosula drives a soil carbon allocation trade-off - Wen Luo; Yali Guo; Zhihu Wang; Wenying Wang; Yuanli Li; Lili Liu; Wenjuan Wang; Ming Luo; Yonggang Wang (European Journal of Soil Biology, 2026)

Single-nucleus RNA sequencing reveals the underlying roadmap of early gonadal differentiation in teleost - Jialin Wang; Yajuan Huang; Zhongkai Cui; Kaili Zhang; Na Wang; Jun Luo; Yu Song; Bowen Hu; Ming Li; Yadong Chen; Manfred Schartl; Songlin Chen (Science China Life Sciences, 2026)

Tidal irrigation-based rice cultivation enhances coastal blue carbon and decreases GHG emissions in brackish mudflats - Lang Zhang; Linlin Li; Hualei Yang; Wenbang Tang; Ji Chen; Hongkai Zhou; Ying Huang; Xuechu Chen; Xiuzhen Li; Ming Luo; Xingyun Huang; Faming Wang; et al. (Agricultural and Forest Meteorology, 2026)

Principle of Dynamic Noise Compensation in UAV Aeromagnetic Gradiometer Systems - Hua Guo; Jin-peng Huang; Jian-chun Xu; Jia-ming Li; Wen-han Li; Qi-ting Luo; Qi Yu (Applied Geophysics, 2026)

Multiomics approaches identify immunometabolic crosstalk in triploid cyprinid fish after Edwardsiella tarda 1 l-4 infection - Ruo-Xing Yu; Ting Luo; Qin-Yang He; Zi-Rou Zhong; Jie Peng; Yao-Hui Li; Zhuang-Wen Mao; Ming-Zhu Huang; Zi-Le Qin; Xu-Ying Kuang; Zi-Xuan Fang; Jian Li; et al. (Aquaculture, 2026)

Moss biocrusts enhance hydrological functionality on engineered slopes: pore restructuring, water retention, and hydrophobicity compensation in humid subtropical ecosystems - Chen Wang; Jiaqi Tan; Zhou Fang; Yingjie Zhang; Ming Luo; Binbin He; Shaoxian Song; Li Wu; María Luciana Montes; Delong Meng; Ling Xia (Journal of Hydrology, 2026)

Creep of water-bearing soft rock and its influence on long-term rock mass stability - Zhao-Qiang Zheng; Li Zhuo; Jian-Liang Pei; Ming-Li Xiao; Huai-Zhong Liu; Hong-Qiang Xie; Tao Luo (Engineering Geology, 2026)

Ultraviolet-induced Glycyrrhiza polysaccharide hydrogels with different mechanical strength for wound management - Zhuxian Wang; Ming Luo; Lehuan Ni; Yimeng Li; Dan Liu; Hongxia Zhu; Bijun Xia; Yuanyuan Liu; Qiang Liu; Bin Yang (Carbohydrate Polymers, 2026)

Advances in natural products with anti-skin photoaging: mechanisms, phytochemical diversity, and therapeutic potential - Yi Luo; Xiao-Cui Liu; Yu-Jie Li; Yu-Jia Wang; Ming-Hua Qiu; Xing-Rong Peng (Phytochemistry Reviews, 2026)

Discovery of FLF-15 as a novel selective inhibitor of ADAM17 to prevent hepatocellular carcinoma metastasis - Qing Li; Dao-ping Wang; Ting Zhong; Ai-ling Ling-hu; Jia-lin Chen; Fang Luo; Feng Zhang; Ming-zhi Su; Ying Yang; Yan-hua Fan (Molecular Diversity, 2026)

Genetic origins and climate‐induced erosion in economically important Asian walnuts - Peng‐Zhen Fan; Guang‐Fu Zhu; Moses C. Wambulwa; Richard I. Milne; Zeng‐Yuan Wu; Ya‐Huang Luo; Robabeh Shahi Shavvon; Alistair S. Jump; Debabrata Maity; Lian‐Ming Gao; Hai‐Ling Qi; Hong‐Yu Wu; et al. (Conservation Biology, 2026)
The global climate is undergoing unprecedented changes, posing significant threats to species persistence. However, the spatiotemporal impacts on genetic diversity remain poorly understood, hindering species conservation and management. Walnuts, generally referred to as Juglans regia and J. sigillata , are economically vital in Asia, but little is known about their genetic origins and how the species will be affected by future climate change. Using 31 microsatellites, we genotyped 5282 individuals from 233 populations of walnuts in Asia. We assessed genetic diversity patterns and demographic history and investigated potential future genetic erosion risks. Genetic diversity of walnuts was high in the Himalaya and Hengduan Mountains. The 2 species diverged during the Pleistocene (around 1.41 Ma BP), and J. regia contained 2 genetic groups (JR1 and JR2). The JR2 group had the lowest diversity and likely arrived in northern China around 9.77 ka BP, perhaps via human transport. The Western Himalaya likely served both as a glacial refugium and the center of origin for J. regia , and the Eastern Himalaya appears to have been the refugium for J. sigillata . The 2 species appear to have hybridized in the Central Himalaya and the Sichuan basin and surroundings, forming two distinct hybrid zones. Our results indicate that genetic diversity will be reduced by up to 9.03% due to range loss under future climate change and dramatic genetic structure turnover in the Himalaya and Hengduan Mountains. In situ conservation in the Himalaya is essential for safeguarding genetic diversity and adaptive potential in Asian walnuts, while ex situ preservation of genetically unique wild germplasm, coupled with its integration into breeding programs, will enhance climate resilience. The findings advance our understanding of the origin of Asian walnuts and how future climatic change may affect their genetic diversity, offering a model for conservation and breeding strategies in other tree species facing similar threats.

Two new compounds isolated from an endophytic fungus Eutypella sp. XLE005 derived from Conus leopardus - Xin-Ming Li; Li Yang; Qing-Yun Ma; Qing-Yi Xie; Jiao-Cen Guo; Hao-Fu Dai; Du-Qiang Luo; You-Xing Zhao (Natural Product Research, 2026)

A new isoprenyl-phenol-type meroterpenoid from mangrove endophytic fungus Aspergillus sp. GXNU-Y65 - Fan-Fan Wang; Guo-Bao Huang; Cai-Hong Lu; Li-Jun Chen; Hui-Zhen Chen; Meng-Qin Luo; Ping-Fang Tao; Ming-Xiong Tan; Feng Qin (Natural Product Research, 2026)

A multi-band remote sensing method for small-and-medium river discharge estimation based on fused Sentinel-2/Landsat images - Li-ying He; Hua Chen; Nie Zhou; Ming-di Li; Chao Wang; Bin Luo; Chong-Yu Xu (Journal of Hydrology, 2026)

Mechanisms of enhanced synergistic pollution reduction and carbon fixation induced by microalgal-bacterial interactions within different biofilm structures - Chao Li; Kang Liu; Xinming Wu; Weikai Shui; Jingyang Luo; Jiashun Cao; Ming Xu; Weijing Liu (Journal of Environmental Management, 2026)

Sulfite exporter SsTauE enhances bacterial feather degradation by maintaining sulfur homeostasis - Lei Wu; Ming-Shu Zhang; Zhen-Dong Yang; Zhi-Wei Li; Jun-Jin Deng; Xiao-Chun Luo (International Biodeterioration & Biodegradation, 2026)

Endogenous metabolism and electricity conversion of organic clogging substances in constructed wetland microbial fuel cell - Chao Li; Dongxu He; Quan Yuan; Jiashun Cao; Jingyang Luo; Ming Xu; Hongqiang Ren (Environmental Research, 2026)

Integrated mass-charge transfer enhancement in PEMFCs via nonspecific Pt-sulfonate adsorption and surface-channel co-design - Wei Xu; Chuanqi Luo; KeChuang Wan; XueJian Pei; MingYuan Hua; ZiKuan Zhang; CunMan Zhang; PingWen Ming; Bing Li (Chemical Engineering Journal, 2026)

Dynamic hydrolytic ion-pairing enables stable interfaces and high anode utilization in lean-electrolyte Mg-air batteries - Yuxi Zhang; Sensen Yu; Ming Li; Sha Luo; Yu Feng; An Duan; Bao Zhang; Wei Sun (Chemical Engineering Journal, 2026)

Corrigendum to “Dendrobium officinale polysaccharide promotes M1 polarization of TAMs to inhibit tumor growth by targeting TLR2” [Carbohydrate Polymers 292 (2022) 119683] - Hong-Yan Wang; Ji-Chun Ge; Feng-Yun Zhang; Xue-Qiang Zha; Jian Liu; Qiang-Ming Li; Jian-Ping Luo (Carbohydrate Polymers, 2026)

Impact of mobile display background Illuminance and spectrum on circadian rhythms, visual fatigue, and cognitive performance in nighttime environments - Zhenzhen Li; Yuechen Zhu; Qichen Ye; Ming Ronnier Luo (Building and Environment, 2026)

Single-Cell RNA Sequencing Reveals Impaired CHIP-Mediated Heat Stress Response in SCA3 Pathogenesis - Mi-bo Tang; Shi-feng Sheng; Zheng-wei Hu; Hai-yang Luo; Meng-jie Li; Shuo Zhang; Xiao-yan Hao; Cheng-yuan Mao; Shao-hua Li; Hui-fang Sun; Zhi-hua Yang; Yi Song; et al. (Molecular Neurobiology, 2026)

ABCD-type phage cocktail targeting distinct LPS receptor sites demonstrates superior efficacy against multidrug-resistant Salmonella - Yibao Chen; Xiaoqian Wang; Qing Zhang; Zhipeng Zhang; Zhengjie Liu; Xiaonan Zhao; Lulu Li; Ming Hu; Qianghua Lv; Yanbo Luo; Xiaohui Xu; Bent Petersen; et al. (Journal of Hazardous Materials, 2025)

Separation and detection of ginsenosides: Challenges, industrial implications, and developments - Anqi Liu; Junjun Zhou; Yiling Luo; Yingbo Li; Yu Yang; Zibo Meng; Lixia Zhou; Hanlei Zhang; Na Liu; Ming Hui; Dandan Zhai; Peng Li (Food Research International, 2025)

Sesquiterpenoids and monoterpenoids from the aerial parts of Sarcandra glabra (Thunb.) Nakai - Yang Liu; Jie Chen; Wan-Wan Yu; Yong-Ming Luo; Meng-Li He; Xin-Yu Chen; Fang-You Chen (Biochemical Systematics and Ecology, 2025)

FengycinA-M3 Inhibits Listeria monocytogenes by Binding to Penicillin-Binding Protein 2B Targets to Disrupt Cell Structure - Ziruo Wang; Mengsheng Tang; Ming Chen; Xiaohu Luo; Jiali Xing; Xin Zhang; Chunbao Li; Yanan Liu (Probiotics and Antimicrobial Proteins, 2025)

Lithospermic acid targeting heat shock protein 90 attenuates LPS-induced inflammatory response via NF-кB signalling pathway in BV2 microglial cells - Jie Guo; Chen-guang Li; Feng-yi Mai; Jing-rong Liang; Ze-hao Chen; Jiao Luo; Ming-chao Zhou; Yu-long Wang; Wen-tao Yang (Immunologic Research, 2025)

Comparative chloroplast genomic analysis: uncovering variations and phylogenetic relationships in tea plants from Shaoyang, Hunan Province, China - Jin Li; Yu Qin; Jun Tang; Xiao-Yan Qiu; Chang-Qing Xie; Han Tang; Ai-Ming Tang; Xiao Chen; Jun-Ping Xie; Hua Luo (Genetic Resources and Crop Evolution, 2025)

Transforming residual biomass of Irish red seaweed Asparagopsis taxiformis and Palmaria palmata into biosorbents for methylene blue adsorption - Weihao Meng; Ruipeng Zhang; Siwei Gu; Ming Zhao; Jiani Luo; Colm P. O'Donnell; Yuan Li; Hongnan Sun; Taihua Mu; Marco Garcia-Vaquero (Algal Research, 2025)

Network pharmacology, molecular docking and experimental validation to elucidate the anti-ulcerative colitis mechanism of Rosa roxburghii Tratt. leaves - Ming-Liang Luo; Shuang Zhang; Qing-Yong Wang; Ling-Wei Fu; Li-Juan Xiang; Chang Lin; Xin Yin (Natural Product Research, 2025)

CO2 hydrate sequestration in unsealed submarine sediments: A 4D pore-scale experimental investigation - Yanfang Li; Tong Zhang; Liang Yuan; Ming Tang; Ruilong Li; Yongqiang Chen; Wen Luo; Chuanjiu Zhang (Gas Science and Engineering, 2025)

Development of chondroitin sulfate-modified quinoa protein isolate-dihydromyricetin composite nanoparticles: Focus on naringenin delivery, cell cytoprotective ability and anti-inflammatory effects - Ying-Ying Chen; Xue-Ying Li; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Orthogonal functional group tagging combined with computational retention time prediction for discovering furan fatty acids in plant oils - Hua-Ming Xiao; Xiao-Hui Peng; Shuai Zhao; Dilshad Hussain; Qin-Feng Zhang; Jian-Li Chen; Dan Luo; Fang Wei; Xian Wang (Food Chemistry, 2025)

The proteo- and chitinolytic coordinate mechanisms of Streptomyces sp. SCUT-3 and its application in chitinous wastes recycling - Ming-Shu Zhang; Zhi-Wei Li; Lei Wu; Zi-Yang Luo; Can Qin; Fu-Gen Zhang; Chu-Yan Liang; Hai-Ning Wang; De-Lin Lu; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Potential of non-digestible polysaccharides as GLP-1 secretagogues: action mechanisms, structure-activity relationships and clinical applications - Zhen-Zi Shang; Hui-Yu Ye; Qiang-Ming Li; Xue-Qiang Zha; Jian-Ping Luo (Carbohydrate Polymers, 2025)

Waste biomass-derived organic matter for sustainable soil remediation: Enhancing heavy metal removal and eluent reuse in agricultural application - Shuai Yang; Chen Tu; Guo-ming Liu; Yuan Li; Yi Wang; Xia Zhu; Shao-cheng Si; Run-lai Luo; Zhong-yuan Li; Yong-ming Luo (Bioresource Technology, 2025)

Cascading effects of tree diversity loss on herbivore-parasitoid interactions - Ming-Qiang Wang; Kai Zhang; Georg Albert; Sylvia Haider; Yi Li; Jing-Ting Chen; Andréa Davrinche; Qing-Song Zhou; Arong Luo; Tobias Proß; Keping Ma; Helge Bruelheide; et al. (Biological Conservation, 2025)

An analytical method to assess the impact of frequency-dependent accelerometer noise on gravity field model determination - Kang Wang; Hao Zhou; Zhicai Luo; Ming Li; Le Suo (Journal of Geodesy, 2025)

Dysfunction of cerebrospinal fluid circulation and neurovascular decoupling in end-stage renal disease patients with mild cognitive impairment - Zhaoyao Luo; Lurui Bo; Xinyi Zhu; Qiange Zhu; Huijie Yuan; Wen Gu; Peng Li; Yihao Peng; Xiang Chen; Ming Zhang; Shaohui Ma; Junya Mu (GeroScience, 2025)
End-stage renal disease (ESRD) patients frequently experience mild cognitive impairment (MCI), which significantly affects their quality of life. Although dysfunctions in cerebrospinal fluid (CSF) circulation and neurovascular coupling (NVC) have been implicated in cognitive impairment, their interrelationship remains unclear. This study aimed to investigate the association between CSF circulation dysfunction and NVC disruption in ESRD patients with MCI. We enrolled 68 ESRD patients with MCI and 65 healthy controls (HCs). CSF circulation was assessed using choroid plexus volume (CPV), the diffusion tensor imaging along the perivascular space (DTI-ALPS) index, and perivascular space volume fraction (PVSVF). NVC was evaluated using coupling metrics between cerebral blood flow (CBF) and resting-state functional magnetic resonance imaging (MRI) indicators: amplitude of low-frequency fluctuation (ALFF), fractional ALFF (fALFF), and regional homogeneity (ReHo). Cognitive performance was measured using a battery of neuropsychological tests. Compared to HCs, ESRD patients showed significantly increased CPV ( P < 0.001) and enlarged PVSVF ( P < 0.05), along with a decreased DTI-ALPS index ( P < 0.01). Global and regional NVC metrics were significantly reduced in ESRD patients ( P < 0.001). Moreover, regional NVC metrics were negatively correlated with CPV. Mediation analysis further revealed that CBF-ReHo coupling in the left cingulate gyrus pregenual area 32 mediated the relationship between elevated LCPV and cognitive decline. These findings suggest that CSF circulation dysfunction and impaired NVC are interrelated in ESRD-MCI. Disruption of CSF circulation may contribute to cognitive decline by impairing NVC, highlighting both as potential targets for early diagnosis and intervention in ESRD-related cognitive impairment.

Two pairs of novel isochromanone derivatives with antiadipogenic effects from the cultures of Ganoderma gibbosum - Yu-Jie Li; Xiao-Cui Liu; Yi Luo; Ming-Hua Qiu; Ping Zhao; Xing-Rong Peng (Phytochemistry Letters, 2025)

Uncertainty-based assessment of ice loads for ship navigation in ice floe environments - Ji-Ming Luo; Xing-Hui Li; Ze-Wen Yang; Yu-Chao Yuan; Wen-Yong Tang (Ocean Engineering, 2025)

Spatial source-oriented analysis and probabilistic health risk assessment of potentially toxic elements in soils integrating the Geo-detector, APCS-MLR, and Monte-Carlo models - Yunhui Zhang; Denghui Wei; Zhan Xie; Haidong Li; Shiming Yang; Ming Luo; Jelena Vesković; Antonije Onjia; Yangshuang Wang; Ying Wang; Zhihao He; Xun Huang (Journal of Environmental Chemical Engineering, 2025)

Immunosuppressive role of benzo[a]pyrene exposure in prostate cancer progression - Zhijin Zhang; Wentao Zhang; Huan Wang; Haotian Chen; Hong Wang; Yang Yu; Danjing Shen; Man Pi; Yang Wu; Ming Luo; Yanyan He; Shiyu Mao; et al. (Journal of Environmental Sciences, 2025)

Integration of metabolomics and transcriptomics unravels the molecular mechanisms underlying variations in flavor-related volatiles in Citrus reticulata ‘Chachi’ grafted onto different rootstocks - Ding Huang; Jinmei Li; Yuping Wei; Xiang Luo; Xin Xie; Jianhua Chen; Shaochang Yao; Liangbo Li; Jialing Fu; Jidi Xu; Chongling Deng; Rongshao Huang; et al. (Food Research International, 2025)

Purification, identification, and mechanism of action of novel antioxidant peptides from quinoa (Chenopodium quinoa wild.) protein hydrolysate - Huan-Huan Xiao; Xue-Ying Li; Ying-Ying Chen; Jin-Xiang Zhou; Ting Zhang; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Chemistry, 2025)

Novel receptor-binding protein from phage PJNS004 for sensitive detection of Salmonella - Yibao Chen; Simin Yang; Qing Zhang; Ming Hu; Qianghua Lv; Xiaonan Zhao; Lulu Li; Yanbo Luo; Xiaohui Xu; Yujun Zhao; Yuqing Liu (Food Chemistry, 2025)

The impact of cultural background on lighting preferences for viewing paintings - Li Qin; LiLi Dong; Ming Ronnier Luo; Kaida Xiao (Energy and Buildings, 2025)

A ratiometric fluorescence probe based on curcumin and supramolecular deep eutectic solvent for in vivo imaging cerebral pH - Wan-Chun Luo; Jin-Tao Zhang; Li-Na Bao; Lin-Jiao Yang; Zi-Ke Yang; Ming Jiang; Xu Yu; Li Xu (Chemical Engineering Journal, 2025)

Biomimetic reed-leaf nanostructures enabling dual-channel-responsive biopolymer platforms for IoT-embedded intelligent active packaging - Liuying Li; Xiaomin Luo; Ying Liu; Ming Teng; Xudan Liu; Xiaomeng Zhang; Xinhua Liu (Chemical Engineering Journal, 2025)

Highly efficient and sustainable bioconversion of cottonseed meal to high-value products through solid-state fermentation by protease-enhanced Streptomyces sp. SCUT-3 - Zhen-Jie Dai; Ming-Shu Zhang; Zhi-Wei Li; De-Lin Lu; Lei Wu; Can Qin; Hai-Ning Wang; Jun-Jin Deng; Xiao-Chun Luo (Chemical Engineering Journal, 2025)

Neural Responses to Hypoxic Injury in a Vascularized Cerebral Organoid Model - Yang Li; Xin-Yao Sun; Peng-Ming Zeng; Zhen-Ge Luo (Neuroscience Bulletin, 2025)
Hypoxic injury (HI) in the prenatal period often causes neonatal neurological disabilities. Due to the difficulty in obtaining clinical samples, the molecular and cellular mechanisms remain unclear. Here we use vascularized cerebral organoids to investigate the hypoxic injury phenotype and explore the intercellular interactions between vascular and neural tissues under hypoxic conditions. Our results indicate that fused vascularized cerebral organoids exhibit broader hypoxic responses and larger decreases in panels of neural development-related genes when exposed to low oxygen levels compared to single cerebral organoids. Interestingly, vessels also exhibit neural protective effects on T-box brain protein 2 + intermediate progenitors (IPs), which are markedly lost in HI cerebral organoids. Furthermore, we identify the role of bone morphogenic protein signaling in protecting IPs. Thus, this study has established an in vitro organoid system that can be used to study the contribution of vessels to brain injury under hypoxic conditions and provides a strategy for the identification of intervention targets.

Small-molecule fluorescent probes for imaging intracellular amyloid toxicity induces ferroptosis via HClO fluctuation in Alzheimer's disease - Wenhui Ma; Bingbing Tang; Han Zhang; Yixin Qu; Jinfeng Luan; Kelong Wang; Wenbo Chen; Xijuan Wang; Xinran Liu; Hongyan Zhao; Haixia Li; Ming Luo; et al. (Analytica Chimica Acta, 2025)

Telaprevir attenuates caspase-11-dependent pyroptosis in mouse heart following ischemia/reperfusion via inhibition of MALT1/TRAF6 pathway - Ming-Rui Li; Bi-Feng Yao; Can Tang; Xiu-Ju Luo; Jun Peng (Toxicology and Applied Pharmacology, 2025)

First experiment using post-accelerated unstable ion beams at BRIF: angular distribution of the 21 , 22 Na elastic scattering from doubly magic 40 Ca - Wei Nan; Bing Guo; Cheng-Jian Lin; Dan-Yang Pang; Lei Yang; Dong-Xi Wang; Guo Yang; Yang-Ping Shen; Bing Tang; Qi-Wen Fan; Yi-Wen Bao; Lei Cao; et al. (Science Bulletin, 2025)

Cross-reactivity and conserved epitope analysis of tropomyosin from Lateolabrax japonicus and shellfish species - Meng-Si Li; Fei Xia; Qing-Mei Liu; Fa-Jie Li; Yu-Ni Liao; Li-Qiang Zhong; Gui-Xia Chen; Lian-Zhong Luo; Yi-Xiang Liu; Guang-Ming Liu (Food Chemistry, 2025)

Identification of a Streptomyces sp. SCUT-3 aminopeptidase SsLap1 and its synergistic with endopeptidase Sep39 for peanut meal hydrolysis - Hua-Hong Cai; Ming-Shu Zhang; Lei Wu; Zhi-Wei Li; Can Qin; Chu-Yan Liang; Jun-Jin Deng; Xiao-Chun Luo (Food Bioscience, 2025)

Evaluation of quality characteristics of 15 Gastrodia elata germplasm resources based on HS-SPME-GC-MS, HPLC and electronic nose techniques - Bingbing Zhang; Huaijing Zhu; Lihui Zhang; Ming Luo; Xiaohua Li; Dahui Liu (Food Bioscience, 2025)

Perovskite-socketed FeCoNiCu quaternary alloy nanoparticles for efficient CO2 reduction in solid oxide electrolyzer - Shuo Liu; Lin-Bo Liu; Ming Yang; Yan Li; Qinglin Pan; Yifei Sun; Xian-Zhu Fu; Subiao Liu; Jing-Li Luo (Chemical Engineering Journal, 2025)

PHB/PBAT blended melt-blown micro-nano fiber carbon source for efficient solid-phase denitrification: Insights into low-carbon treatment and enhanced mechanism - Hao Yuan; Liang Tang; Ziwei Yang; Xiang Pi; Jinxiang Zhao; Rongshen Luo; Ming Tang; Zuwen Liu; Zhendong Lei; Shiyang Li (Chemical Engineering Journal, 2025)

Wheat stripe rust resistance gene Yr9, derived from rye, is a CC-NBS-LRR gene in a highly conserved NLR cluster - Yang Yu; Jiajun Liu; Shengjie Lan; Qihang Chen; Jinlong Li; Haoyuan Song; Chen Pan; Juan Qi; Yu Cui; Xingfeng Li; Ming-Cheng Luo; Fei Ni; et al. (Science China Life Sciences, 2025)

Two alkenyl phenol derivatives from the fungus Pestalotiopsis clavata JSQ 12 isolated from the mushroom Lanmaoa asiatica - Jing Tang; Rui Xu; Hao Ma; Shuai-Ming Zhu; Fu-Yao Luo; Xue Zhao; Ya-Shuai Kang; Yuan-Wei Gao; Yu Yang; Chang-Wei Li (Natural Product Research, 2025)

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Corrigendum to “Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties” [Food Chemistry 481 (2025) 1–11 144089] - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Olfactory GnRH3 crypt sensory neurons transduce sex pheromone signals to induce male courtship behavior in zebrafish - Xuefan Cui; Lu Chen; Binbin Tao; Xiya Zhang; Yanlong Song; Ji Chen; Ming Duan; Weiwei Li; Kuangxin Chen; Yang Pei; Xuerui Hu; Ke Feng; et al. (Science China Life Sciences, 2025)

IRBITs, signaling molecules of great functional diversity - Ying Liu; Xuhui Feng; Han Wu; Tianxiang Gui; Mingfeng Fu; Xudong Luo; Lei Zhao; Li-Ming Chen (Pflügers Archiv - European Journal of Physiology, 2025)

Mulching increases soil organic carbon via plant inputs and its microbial transformation - Rongqin Zhang; Yuanji Wang; Xuechen Zhang; Fan Luo; Xiaomeng Wei; Ming Li; Huike Li; Xining Zhao; Zhilong Duan; Xiaolin Song; Yakov Kuzyakov (Biology and Fertility of Soils, 2025)

Quantitative Reconstruction of Salinity and Precipitation Changes in Central Asia over the Past 3 200 Years Using Diatom and Pollen Records of Lacustrine Sediment in Aibi Lake of SW Junggar Basin - Long Pan; Guoqiang Li; Xiaoyan Wang; Ming Jin; Xinrong He; Luo Qin; Zhong Wang; Wenwei Zhao; Chunzhu Chen; Yuanlu Liu; Jin Yang; Lele Shu (Journal of Earth Science, 2025)

Leaf and Root Traits Show Contrasting Resource Exploitation Strategies, but Converge Along Elevation in the Hengduan Mountain Forests - Jie Song; Sebastian Seibold; Liang‐Liang Ma; Jia‐Yun Zou; Jie Liu; Ming‐Shu Zhu; Wei Zheng; Zhi‐Qiong Mo; Sheng‐Ping Ming; Jin Li; Kun Xu; De‐Zhu Li; et al. (Journal of Biogeography, 2025)
Aim The variations of leaf and root traits in communities are associated with above‐ and below‐ground resource exploitation strategies and are used to infer community assembly processes along environmental gradients. However, little is known about variations in leaf and root traits and their drivers along elevations in mountain forests. Location Yulong Mountain, southeastern Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We measured six leaf traits and seven root traits across 47 woody species and collected environmental variables from forest plots along a 1200 m elevational gradient. We employed linear mixed models to examine how resource exploitation strategies (community‐weighted mean, CWM) and functional diversity (standardised effect size of RaoQ, SES.RaoQ) associated with leaf and root traits varied along elevations. Furthermore, we determined the relative effects of environmental variables on these metrics. Results We observed that the resource exploitation strategy of leaves shifted from an acquisitive to a conservative strategy (higher leaf carbon concentration) with increasing elevation. Conversely, root trait variation exhibited an opposite trend, shifting from a conservative to an acquisitive strategy (higher root branching intensity but lower root diameter and root tissue density) along elevations, potentially influenced by mycorrhizal interactions. We detected functional convergence for leaf and root traits across elevations, with a greater degree of functional convergence at high elevations. Leaf trait convergence was closely linked to soil nitrogen conditions, whereas root trait convergence was associated with soil organic carbon levels. Main Conclusions Our results highlight that the patterns of resource exploitation strategies along elevational gradients are decoupled for leaf and root traits, with distinct environmental factors shaping the convergence of root and leaf traits. We argue that forest communities in mountain ecosystems may modify their resource exploitation strategies and functional diversity through varying combinations of leaf and root traits to improve resilience to future global change.

A ships encounter sector analysis approach for intelligent navigation safety - Zhichen Liu; Ying Li; Ming Xie; Zhaoyi Zhang; Yulei Wang; Jianan Luo (Ocean Engineering, 2025)

Industrial air pollution and newborn hearing screening failure - Yanhong Huang; Yan Lin; Roberta P. Lavin; Li Luo; Ming Luo; Shuguang Leng; Netanya M. Mullen; Karen Hawley; Xi Gong (Journal of Hazardous Materials, 2025)

PtBi nanocatalysts with controlled chain-like structure and composition: Solvothermal synthesis and ethanol oxidation performance - Luo-Yi Yan; Han-Tao Zhang; Xiao-Yu Lu; Li-Ming Liu; Rong-Hua Zhang; Zheng Cheng; Shuai-Wei Fan; Xin-Wen Zhou (Fuel, 2025)

Synergistic effects of polymethoxyflavonoids from citrus peel extracts on harmful compound formation and flavor quality in grilled beef patties - Zhuoming Huang; Yang Xu; Ming Jin; Zixin Jiang; Lan Mo; Maiquan Li; Aihua Lou; Yan Liu; Chaoyi Xue; Jie Luo; Qingwu Shen; Shuai Wang; et al. (Food Chemistry, 2025)

Effect of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel on physicochemical, texture and sensory properties of low-fat yoghurt - Ya-Hui Yu; Luo-Bang Wu; Long-Qing Li; Ming-Yu Jin; Xiaozhen Liu; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2025)

Establishment of mud crab (Scylla paramamosain) spermatogonial stem cell line: A potential tool for immunological research - Ying Song; Yanchuang Duan; Haiqing Luo; Linying Yun; Ming Zhang; Ngoc Tuan Tran; Huaiping Zheng; Qicun Zhou; Shengkang Li (Fish & Shellfish Immunology, 2025)

Identification, characterization, and functional verification of a novel fish-egg lectin (FEL) from the golden pompano, Trachinotus ovatus - Ming Luo; Weifeng Li; Sanghyok Ri; Weixia Zhang; Tongchol Kim; Kwangjin Ju; Longlong Liu; Weishang Zhou; Wei Shi; Guangxu Liu (Fish & Shellfish Immunology, 2025)

Downregulation of METTL3 enhances TRADD-mediated apoptosis in inflammatory bowel disease - Tingyue Gong; Zhiyang Zeng; Zurui Huang; Yang Luo; Xiya Cao; Hao Li; Yongheng Zhao; Dali Han; Dali Li; Ming Zhong (Science China Life Sciences, 2025)

Characteristics and evolution of mass-transport complex since Late Miocene in the Zengmu and Beikang basins, southern South China Sea - Shuqin Huang; Ming Su; Haiteng Zhuo; Li Zhang; Shan Liu; Zhi Lin Ng; Zhixuan Lin; Boda Zhang; Kunwen Luo; Li’e Lin (Journal of Oceanology and Limnology, 2025)

A Hierarchical Reinforcement Learning Framework for Multi-Agent Cooperative Maneuver Interception in Dynamic Environments - Qinlong Huang; Yasong Luo; Zhong Liu; Jiawei Xia; Ming Chang; Jiaqi Li (Journal of Marine Science and Engineering, 2025)
To address the challenges of real-time decision-making and resource optimization in multi-agent cooperative interception tasks within dynamic environments, this paper proposes a hierarchical framework for reinforcement learning-based interception algorithm (HFRL-IA). By constructing a hierarchical Markov decision process (MDP) model based on dynamic game equilibrium theory, the complex interception task is decomposed into two hierarchically optimized stages: dynamic task allocation and distributed path planning. At the high level, a sequence-to-sequence reinforcement learning approach is employed to achieve dynamic bipartite graph matching, leveraging a graph neural network encoder–decoder architecture to handle dynamically expanding threat targets. At the low level, an improved prioritized experience replay multi-agent deep deterministic policy gradient algorithm (PER-MADDPG) is designed, integrating curriculum learning and prioritized experience replay mechanisms to effectively enhance the interception success rate against complex maneuvering targets. Extensive simulations in diverse scenarios and comparisons with conventional task assignment strategies demonstrate the superiority of the proposed algorithm. Taking a typical scenario of 10 agents intercepting as an example, the HFRL-IA algorithm achieves a 22.51% increase in training rewards compared to the traditional end-to-end MADDPG algorithm, and the interception success rate is improved by 26.37%. This study provides a new methodological framework for distributed cooperative decision-making in dynamic adversarial environments, with significant application potential in areas such as maritime multi-agent security defense and marine environment monitoring.

Integrated GWAS and transcriptome analysis reveals regulatory networks underlying growth in improved grass carp - Yakui Tai; Ling Liu; Yiyan Zeng; Mengdan Li; Mengxue Luo; Wuhui Li; Hailu Zhou; Jinhui Zhang; Xiaohuan Han; Conghui Yang; Ming Wen; Li Ren; et al. (Aquaculture, 2025)

Hydrological connectivity creates additional cooling effects for urban wetland complexes - Wenwen Xie; Hao Yang; Peng Luo; Honglin Li; Shijun Zhang; Yu Huang; Yue Cheng; Ming Ni; Sujuan Wu; Haoyu Yang (Urban Climate, 2025)

Functional identification of mango MiEXPLA1a2 and MiEXPA4e1 genes in transgenic Arabidopsis and tomato - Xiang-juan Zhang; Ji-hong Yang; Jia-jun Li; Hui-jun Yang; Ming-qing Li; Yue-xing Zhang; Cong Luo; Xin-hua He (Plant Science, 2025)

Early Eocene Metasequoia and Taxodium (Cupressaceae) from Lingbao, Henan Province and their implication for a perhumid climate in central China - Ping Liu; Hui Jia; Li Xu; Yu Li; Ming-Yue Luo; Tian-Qi Dong; Jiao Huang; Cheng Quan (Palaeoworld, 2025)

Pan-genome and haplotype map of cassava cultivars and wild ancestors provide insights into its adaptive evolution and domestication - Zhiqiang Xia; Zhenglin Du; Xincheng Zhou; Sirong Jiang; Tingting Zhu; Le Wang; Fei Chen; Luiz Carvalho; Meiling Zou; Luis Augusto Becerra Lopez-Lavalle; Xiaofei Zhang; Liangye Xu; et al. (Molecular Plant, 2025)

Composition characteristics, source analysis and risk assessment of PAHs in surface waters of Lipu - Jun Luo; Gui-Bin Huang; Mei Wang; Ya-Nan Zhang; Zi-Xuan Liu; Qin Zhang; Shao-Yuan Bai; Dan-Dan Xu; Hui-Li Liu; Sheng-Peng Mo; Xiao-Bin Zhou; Ming-Ming Fu (Journal of Hazardous Materials, 2025)

Co3O4@carbon nanofiber aerogel electrodes with wide detection range for electrochemical detection of Cd(II) in cigarette butts - Wei Wu; Jieqiong Wang; Diyin Luo; You Wu; Zhengchuan Hu; Weibo Zhou; Qi Wang; Xingyue You; Ming Li; Lu Wang (Journal of Environmental Chemical Engineering, 2025)

Epigenetics in the modern era of crop improvements - Yan Xue; Xiaofeng Cao; Xiangsong Chen; Xian Deng; Xing Wang Deng; Yong Ding; Aiwu Dong; Cheng-Guo Duan; Xiaofeng Fang; Lei Gong; Zhizhong Gong; Xiaofeng Gu; et al. (Science China Life Sciences, 2025)
Epigenetic mechanisms are integral to plant growth, development, and adaptation to environmental stimuli. Over the past two decades, our comprehension of these complex regulatory processes has expanded remarkably, producing a substantial body of knowledge on both locus-specific mechanisms and genome-wide regulatory patterns. Studies initially grounded in the model plant Arabidopsis have been broadened to encompass a diverse array of crop species, revealing the multifaceted roles of epigenetics in physiological and agronomic traits. With recent technological advancements, epigenetic regulations at the single-cell level and at the large-scale population level are emerging as new focuses. This review offers an in-depth synthesis of the diverse epigenetic regulations, detailing the catalytic machinery and regulatory functions. It delves into the intricate interplay among various epigenetic elements and their collective influence on the modulation of crop traits. Furthermore, it examines recent breakthroughs in technologies for epigenetic modifications and their integration into strategies for crop improvement. The review underscores the transformative potential of epigenetic strategies in bolstering crop performance, advocating for the development of efficient tools to fully exploit the agricultural benefits of epigenetic insights.

Graph Neural Networks and Multimodal DTI Features for Schizophrenia Classification: Insights from Brain Network Analysis and Gene Expression - Jingjing Gao; Heping Tang; Zhengning Wang; Yanling Li; Na Luo; Ming Song; Sangma Xie; Weiyang Shi; Hao Yan; Lin Lu; Jun Yan; Peng Li; et al. (Neuroscience Bulletin, 2025)

Evolutionary origins override contemporary environmental filtering in shaping terrestrial algae diversity - Shuyin Li; Qingyi Luo; Qinghua Cai; Ming‐Chih Chiu; Vincent H. Resh (Ecology, 2025)
An understanding of mechanisms that influence biogeographical patterns can play a pivotal role in deciphering the intricate dynamics underlying species distributions and, ultimately, biodiversity patterns. Biodiversity composition results from both evolutionary origins and contemporary processes. However, how this combination jointly shapes biodiversity patterns and operates through mechanistic links to real‐world evidence generally has been overlooked. Using the information on microalgae that comprise the phyllosphere biota that grow on the surface of the leaves of terrestrial plants in China, we quantitatively evaluate the role of contemporary and phylogenetic processes in influencing species adaptability and their persistence across landscapes. Through biodiversity modeling, this study separates the effects of phylogenetic and contemporary factors affecting the community structure of these algal communities. Results demonstrate that the evolutionary history of these terrestrial algae can exert a dominant influence over contemporary filtering of environmental processes in shaping species diversity and community structure. These results underscore the significance of integrating evolutionary origins into biodiversity modeling to more accurately understand current biodiversity patterns and, therefore, facilitate more effective biodiversity management and ecosystem conservation efforts.

YOLO-DAFS: A Composite-Enhanced Underwater Object Detection Algorithm - Shengfu Luo; Chao Dong; Guixin Dong; Rongmin Chen; Bing Zheng; Ming Xiang; Peng Zhang; Zhanwei Li (Journal of Marine Science and Engineering, 2025)
In computer vision applications, the primary task of object detection is to answer the following question: “What object is present and where is it located?”. However, underwater environments introduce challenges, such as poor lighting, high complexity, and diverse marine organism shapes, leading to missed detections or false positives in deep learning-based algorithms. To improve detection accuracy and robustness, this paper proposes an enhanced YOLOv11-based algorithm for underwater object detection that strengthens the ability to capture both local and global details and global contextual information in complex underwater environments. To better capture local and global features while integrating contextual information, the proposed method introduces several enhancements. The backbone incorporates a DualBottleneck module to enhance feature extraction, replacing the standard bottleneck structure in C3k, thus enhancing the feature extraction and the channel aggregation. The detection head adopts DyHead-GDC, integrating ghost depthwise separable convolution with DyHead for greater efficiency. Furthermore, the ADown module replaces conventional feature extraction and downsampling convolutions, reducing parameters and FLOPs by 14%. The C2PSF module, combining focal modulation and C2, strengthens local feature extraction and global context processing. Additionally, a SCSA module is inserted before the detection head to fully utilize multi-semantic information, improving the detection performance in complex underwater scenes. Experimental results confirm the effectiveness of these improvements. The model achieves 84.2% mAP50 on UTDAC2020, 84.4% on DUO and 86.7% on RUOD, surpassing the baseline by 2.5%, 1.6% and 1.2%, respectively. It remains lightweight, with 6.5 M parameters and a computational cost of 7.1 GFLOPs.

DNA damage may cause the reproductive differences between the male tetraploid fish and diploid red crucian carp - Haitao Zhong; Hong Chen; Mingli Liu; Chiye Zhao; Chaoying Luo; Zheduo Xiong; Yan Li; Yilin Wu; Yuheng Wang; Chun Zhang; Chang Wu; Qizhi Liu; et al. (Aquaculture, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Henry; et al. (Molecular Plant, 2025)

Redox state of NAD modulates the activation of Na-bicarbonate cotransporter NBCe1-B via IRBIT and L-IRBIT - Tianxiang Gui; Ying Liu; Mingfeng Fu; Han Wu; Pan Su; Xuhui Feng; Mengmeng Zheng; Zixuan Huang; Xudong Luo; Walter F. Boron; Li-Ming Chen (Science China Life Sciences, 2025)

Cereal-legume intercropping stimulates straw decomposition and promotes soil organic carbon stability - Wei Wang; Meng-Ying Li; Qing-Hui Wen; Yue Ma; Zhi-Ming Zhang; Muhammad Maqsood Ur Rehman; Fei Mo; Hong-Yan Tao; Bao-Luo Ma; Joann K. Whalen; You-Cai Xiong (Science China Life Sciences, 2025)

Preparation and epitope identification of a novel monoclonal antibody against 3A protein of Senecavirus A - Xiang-hui Ling; Biao Zhang; Hao-jie Ren; Ming-yang Li; Shun-da Liu; Meng-ru Luo; Ke-wei Guo; Shi-chong Han; Wen-rui He; Gai-ping Zhang; Yu-hang Zhang; Bo Wan (Veterinary Microbiology, 2025)

Human-perceived temperature changes linked to local climate zones under extreme hot and cold weathers: A study in the North China Plain - Xiang Li; Ming Luo; Jianfeng Li; Sijia Wu; Hui Zhang; Ziwei Huang; Qiuting Wang; Wenyue Cao; Yu Tang; Xiaoyu Wang (Sustainable Cities and Society, 2025)

Siegesoxylipin A‒J, previously undescribed phyto-oxylipins inhibition of methicillin-resistant Staphylococcus aureus and vancomycin-resistant Enterococci from Sigesbeckia orientalis - Zhong-Shun Zhou; Wen-Biao Zu; Yan-Yan Zhu; Mei-Zhen Wei; Yue-Ming Jiang; Zhao-Jie Wang; Yun-Li Zhao; Xiao-Dong Luo (Phytochemistry, 2025)

Aeration strategies for microalgae in wastewater treatment: Enhancing pollutant removal and community dynamics - Pan Li; Yajun Luo; Fei Ming; Jingxian Zheng; Zhicheng Pan; Rui Wang; Yanqing He; Miao Zhou; Xin Xiong; Chi Zhang; Yu Lei; Zhaoqi Wang; et al. (Journal of Environmental Management, 2025)

Terrestrial ecosystem response to Early Cretaceous global environmental change: A calibrated, high-resolution Aptian record from Northeast China - Ming-Dao Sun; Qin Lin; Jahandar Ramezani; Jiang-Si Liu; Zheng-An Lu; Han-Qing Yang; Jiang-Hao Bai; Shi-Xi Cai; Jun-Cai Chen; Xuan-Yu Chen; Hao Cui; Guang-Chao Deng; et al. (Earth and Planetary Science Letters, 2025)

Remodeling of bacterial nitrilase active pocket improves the capability to degrade glucosinolate-derived nitriles - Ming-Yu Liu; Yu-Yue Wang; Han-Zhi Li; Xue-Mei Luo; Jia-Xun Feng; Shuai Zhao (World Journal of Microbiology and Biotechnology, 2025)

Incorporating Genetic Diversity to Optimize the Plant Conservation Network in the Third Pole - Moses C. Wambulwa; Guang‐Fu Zhu; Ya‐Huang Luo; Zeng‐Yuan Wu; Jim Provan; Marc W. Cadotte; Alistair S. Jump; Francis N. Wachira; Lian‐Ming Gao; Ting‐Shuang Yi; Jie Cai; Hong Wang; et al. (Global Change Biology, 2025)
Climate change poses a significant threat to the survival of many species. Although protected areas can slow down biodiversity loss, they often lack systematic planning and do not integrate genetic diversity. Genetic diversity is a key prerequisite for species survival and the ability to tolerate new conditions. Using population genetic and distribution data from 96 plant species in the Third Pole (encompassing the Tibetan Plateau and adjacent mountains), we mapped patterns of genetic diversity, projected climate‐driven range dynamics and future genetic erosion, and designed an optimal conservation framework for the region. We identified several patches of high haplotype diversity ( H D ), with a relatively high number of haplotypes in southeastern Third Pole. Regression models revealed that climate and topography have interacted to shape patterns of genetic diversity, with latitude and precipitation being the best predictors for H D of cpDNA and nrDNA, respectively. Ecological niche modeling predicted an approximate 43 km northwestward and 86 m upward shift in suitable habitats under future climate scenarios, likely leading to a significant loss of up to 13.19% and 15.49% of cpDNA and nrDNA genetic diversity, respectively. Alarmingly, 71.20% of the newly identified conservation priority areas fall outside of the existing protected areas and planned National Park Clusters. Therefore, we recommend expanding the network by 2.02 × 10 5 km 2 (5.91%) in the Third Pole, increasing the total conserved area to 1.36 × 10 6 km 2 (39.93%) to effectively preserve the evolutionary potential of plants. This study represents an innovative attempt to incorporate genetic diversity into biodiversity conservation efforts.

2.08 Ga andesitic gneisses in the southwestern Yangtze Block: Unveiling new insights into its geological evolution - Jun-Ping Liu; Zai-Bo Sun; Wei-Ke Li; Hua-Li Luo; Shi-Jun He; Shao-Bin Hu; Jiang-Tai Zhao; Hai-bao Yan; Ming-Guo Zhai; Hai-Long He (Precambrian Research, 2025)

International research initiative on genomics-guided sugarcane breeding - Xingtan Zhang; Jungang Wang; Noor-ul-Áin; Youxiong Que; Jisen Zhang; Javeria Abid; Peifang Zhao; Yuebin Zhang; Jishan Lin; Li-yu Chen; Yixue Bao; Robert Herry; et al. (Molecular Plant, 2025)

Analysis of genetic diversity and population structure of Pinellia ternata using EST-SSR markers - Mingxing Wang; Rong Xu; Ming Luo; Xinyao Li; Lu Wei; Mi Lei; Dahui Liu; Yuhuan Miao (Journal of Applied Research on Medicinal and Aromatic Plants, 2025)

RGS22 maintains the physiological function of ependymal cells to prevent hydrocephalus - Xue Pang; Lin Gu; Qiu-Ying Han; Jia-Qing Xing; Ming Zhao; Shao-Yi Huang; Jun-Xi Yi; Jie Pan; Hao Hong; Wen Xue; Xue-Qing Zhou; Zhi-Hui Su; et al. (Science China Life Sciences, 2025)

Abnormal sensory processing cortex in insomnia disorder: a degree centrality study - Hui Wang; Haining Li; Ziyi Liu; Chiyin Li; Zhaoyao Luo; Wei Chen; Meiling Shang; Huiping Liu; Fatemeh Naderi Nejad; Yuanping Zhou; Ming Zhang; Yingxiang Sun (Brain Imaging and Behavior, 2025)

Regulating self-assembly of concomitant isotropic Ag78 and anisotropic Ag110 nanoclusters - Xin-Lan Peng; Shuo Huang; Yu-Jing Zhao; Xi-Ming Luo; Hai-Yang Li; Jia-Hua Hu; Jia-Hong Huang; Shuang-Quan Zang (Science Bulletin, 2025)

Structurally diversified sesquiterpenoids from Chloranthus henryi and their neuroprotective activities on H2O2 damaged PC12 cells - Meng-Li He; Lian-Lian Xu; Yang Liu; Yan-Ping Gao; Yong-Ming Luo; Rong-Cai Yue; Fang-You Chen (Phytochemistry, 2025)

Cynbungenins A-K, structurally diverse steroids with cytotoxic activity from the roots of Cynanchum bungei Decne - Xiao-San Li; Ming-Shang Liu; Wan-Bi Feng; Yu-Hao Luo; Wei-Bin Yuan; Ting-Ting Li; Xiao-Fu Peng; Yong-Mei Huang; Xue-Mei Yang; Hui Luo (Phytochemistry, 2025)

Fast photocatalytic Cr(VI) removal by an organic hybrid silver antimony sulfide coupled with PEDOT - Yimin Han; Longfei Zhai; Wen-Bo Pei; Jiahua Luo; Ji-Ming Yu; Haohao Li; Chunhui Hou; Zihui Wang; Juan Ma; Bing Hu; Wei-Wei Xiong (Journal of Cleaner Production, 2025)

Effect of Maillard reaction on the allergenicity of crude extract of Mactra quadrangularis - Fa-Jie Li; Xin-Rong He; Dong-Xiao Li; Yang Yang; Shuai Kang; Qing-Mei Liu; Lian-Zhong Luo; Gui-Xia Chen; Guang-Ming Liu (Food Research International, 2025)

Characterization, adsorption kinetic and in vitro release behavior of curcumin loaded with porous mannitol and porous lactose: Template agent method vs. Pore-forming agent method - Zhe Li; Xiaosui Luo; Abid Naeem; Zhengji Jin; Qiong Li; Yongmei Guan; Lihua Chen; Weifeng Zhu; Liangshan Ming (Food Research International, 2025)

Radiofrequency affects the decrystallization efficiency and physicochemical properties of rape honey via crystal structure modification and inactivating enzyme - Shi-Ye Luo; Jia-Li Tao; Yan-Xiang Bi; Hong-Wei Xiao; Hua-Lei Chen; Xiang-Xin Li; Yin-Chen Wang; Xiao-Ming Fang (Food Chemistry, 2025)

Effect of excitation voltage in a magnetically induced electric field on the physicochemical, structural and functional properties of citrus pectin - Ya-Hui Yu; Xiaozhen Liu; Luo-Bang Wu; Xiangying Yu; Ming-Yu Jin; Long-Qing Li; Fengyuan Liu; Yuting Li; Lin Li; Bing Li; Jing-Kun Yan (Food Chemistry, 2025)

Bioconversion of agriculture by-products with functionally enhanced Streptomyces sp. SCUT-3: Fish skin as a model - Jing-Tao Ni; Ming-Shu Zhang; De-lin Lu; Wen-jun Lu; Lei Wu; Zhen-dong Yang; Can Qin; Zhen-jie Dai; Zhi-wei Li; Wen-jing Feng; Hua-hong Cai; Jia-rui Zhang; et al. (Food Chemistry, 2025)

The impeded film-formation kinetics with ameliorated carrier trap density to construct efficient as-cast organic solar cells through short multi-branched alkylthio chains strategy - Ling Li; Na Li; Jiefeng Hai; Shenzheng Gao; Hao Xu; Ming Luo; Xinjie Zhou; Xiaoyu Shi; Shanlei Xu; Xueming Li; Zhenhuan Lu; Youyong Pang; et al. (Chemical Engineering Journal, 2025)

Overexpression of OsSTP1 increases grain yield via enhancing carbohydrate metabolism and transport in rice - Dong Liu; Ming-juan Li; Jin-song Luo; Hai-fei Chen; Yong Yang; Gui Xiao; Jun Wu; Abdelbagi M. Ismail; Zhen-hua Zhang (Planta, 2025)

Hyperspectral image classification with embedded linear vision transformer - Yunfei Tan; Ming Li; Longfa Yuan; Chaoshan Shi; Yonghang Luo; Guihao Wen (Earth Science Informatics, 2025)

Extracellular vesicles in Chlamydomonas reinhardtii: Mediators of nutrient sensing and cell-to-cell communication - Chao Li; Rongfang Zhu; Zixi Chen; Ming Du; Yerong Liu; Chenchen Liu; Panpan Jiang; Yixuan Luo; Anping Lei; Qiong Liu; Hui Zhu; Liqing Zhao; et al. (Algal Research, 2025)

Hydrogen sulfide alleviates cadmium stress in germinating carrot seeds by promoting the accumulation of proline - Miao Sun; Huan-Xuan Qiao; Tao Yang; Peng Zhao; Jun-Hao Zhao; Jia-Ming Luo; Hai-Ye Luan; Xiang Li; Sheng-Cai Wu; Ai-Sheng Xiong (Journal of Plant Physiology, 2024)

Dendrobium huoshanense stem polysaccharide exhibits gastroprotective effect via regulating PI3K/AKT, NF-κB and Nrf-2 signaling in high-salt diet-induced gastritis mice - Hui-Yu Ye; Zhen-Zi Shang; Xin Gao; Xue-Qiang Zha; Feng-Yun Zhang; Qiang-Ming Li; Jian Liu; Jian-Ping Luo (Food Bioscience, 2024)

Exploring the adaptive behaviour and environmental acclimation of artificially-bred Chinese sturgeon (Acipenser sinensis) in semi-open marine environment: insights for endangered species conservation - Huangxin Liu; Pengcheng Li; Xiaoqian Leng; Ming Jiang; Li Shen; Puyuan Wang; Hui Zhang; Jiang Luo; Wei Xiong; Yuan Liu; Hao Du (Reviews in Fish Biology and Fisheries, 2024)

A Protocol for Body MRI/CT and Extraction of Imaging-Derived Phenotypes (IDPs) from the China Phenobank Project - Chengyan Wang; Shuo Wang; Sha Hua; Ruokun Li; Yan Li; Zhang Shi; Kai Feng; Lizhen Lan; Meng Liu; Xutong Kuang; Xueqin Xia; Shihai Zhao; et al. (Phenomics, 2024)

Peroxynitrite-Triggered Carbon Monoxide Donor Improves Ischemic Stroke Outcome by Inhibiting Neuronal Apoptosis and Ferroptosis - Xin-Jian Guo; Lin-Yan Huang; Shi-Tong Gong; Ming Li; Wan Wang; Jie Chen; Yi-De Zhang; Xicun Lu; Xiaohua Chen; Lan Luo; Youjun Yang; Xiao Luo; et al. (Molecular Neurobiology, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Evaluation of perception and analysis of energy saving potential of nighttime illumination in different types of residential areas: A case study of Dalian, China - Ming Liu; Ruicong Li; Baogang Zhang; Weili Jiao; Tong Luo; Boris A. Portnov; Tamar Trop; Jie Liu; Han Zhang (Sustainable Cities and Society, 2024)

Spatial asymmetry of temporal ecological processes can shift in riverine macroinvertebrates responding to fluctuating climate conditions - Xiaowei Lin; Zhen Tian; Qingyi Luo; Jingting Li; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Science of The Total Environment, 2024)

Methods and experiments for automatic control of surface back pressure based on dung beetle optimizer-PID controller - Zhenyu Long; Jun Li; Hongwei Yang; Wang Chen; Geng Zhang; Biao Wang; Wenxu Wang; Ming Luo; Wentuo Li; Zhiming Yin; Meipeng Ren (Process Safety and Environmental Protection, 2024)

Sustainable protein/polysaccharide aerogel for the simultaneous and efficient removal of multiple organic contaminants: Insights from DFT calculations and phenomenological mass–transfer modeling - Ming-Xing Li; Yan-Shu Xiong; Qi-Qi Huang; Yi-Wen Luo; Wei Wei; Hai-Qin Lu; Fang-Xue Hang; Wen Li; Fujie Liu; Kai Li (Journal of Hazardous Materials, 2024)

Dual decoration of quinoa protein isolate by different dietary polyphenols with covalent and noncovalent approaches: Structure characterization, conformational changes and functional properties - Ying-Ying Chen; Xue-Ying Li; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Edible packaging revolution: Enhanced functionality with natural collagen aggregates - Liuying Li; Xiaomin Luo; Ying Liu; Ming Teng; Xudan Liu; Xiaomeng Zhang; Xinhua Liu (Food Hydrocolloids, 2024)

CDKN1A promotes Cis-induced AKI by inducing cytoplasmic ROS production and ferroptosis - Qian Gao; Jun-ming Chen; Chen-sui-zi Li; Jia-yi Zhan; Xue-dong Yin; Ben-shang Li; Hong-liang Dong; Lian-xiang Luo; Zhi-ling Li (Food and Chemical Toxicology, 2024)

Single-cell transcriptome profiles and E−64 inhibitor data reveal the essential role of cysteine proteases in the ontogeny of Ichthyophthirius multifiliis - Weitian Zhou; Weishan Zhao; Shiman Yang; Fanya Nie; Daji Luo; Ming Li; Wenxiang Li; Hong Zou; Guitang Wang (Fish & Shellfish Immunology, 2024)

MGDA-assisted plant washing agent for improving the removal of Cd and Cu from farmland soils - Yi Wang; Chen Tu; Yuan Li; Shuai Yang; Ying Liu; Xia Zhu; Shao-cheng Si; Run-lai Luo; Xiang-liang Pan; Yong-ming Luo (Environmental Pollution, 2024)

Controlled synthesis of CoFe@TiN composites and their rapid and efficient degradation of emerging organic pollutants: RhB as an example - Qi Jiang; Kunyue Luo; Kang Peng; Ling Li; Hongda Liu; Ming Chen; Min Cheng (Colloids and Surfaces C: Environmental Aspects, 2024)

A multifunctional biomass-based solar interface evaporator with feather-like structure for efficient selective transport, antibacterial properties, salt resistance, and oil-fouling prevention - Peng Zhang; Xudan Liu; Ming Teng; Liuying Li; Xiaomeng Zhang; Wenjing Wang; Wenqing Wang; Xuechuan Wang; Xiaomin Luo (Chemical Engineering Journal, 2024)

From Skin to Gut: Understanding Microbial Diversity in Rana amurensis and R. dybowskii - Ming-he Yang; Hong Liu; Hao Wang; Zhao-ning Lu; Xiao-yun Han; Zhi-wen Luo; Li-gang Wu; Qing Tong (Current Microbiology, 2024)

Understanding Simulated Causes of Damaging Surface Winds in a Derecho-Producing Mesoscale Convective System near the East China Coast Based on Convection-Permitting Simulations - Liping Luo; Ming Xue; Xin Xu; Lijuan Li; Qiang Zhang; Ziqi Fan (Advances in Atmospheric Sciences, 2024)

Complex function method considering rock strength for determining critical warning deformation of deep-buried complex cavern - Ao-Ying Luo; Li Zhuo; Huai-Zhong Liu; Hong-Qiang Xie; Nu-Wen Xu; Ming-Li Xiao; Yong-Jian Shuai (Tunnelling and Underground Space Technology, 2024)

Coarse particulate air pollution and mortality in a multidrug-resistant tuberculosis cohort - Huiying Feng; Erjia Ge; Nicholas Grubic; Xin Liu; Hui Zhang; Qiang Sun; Xiaolin Wei; Fangjing Zhou; Shanshan Huang; Yuhui Chen; Huixin Guo; Jianwei Li; et al. (Science of The Total Environment, 2024)

Glycoprotein from selenium-enriched yam activates immune cells and enhances intestinal immunity via the NF-κB signaling pathway - Siqi Wang; Jinjin Yu; Lili Zhou; Yuzhi Luo; Lingyi Liu; Sha Wen; Lingli Li; Yajing Ma; Huixin Song; Song Ming; Weifeng Li; Xiaofeng Niu (Food Bioscience, 2024)

A wearable electrochemical sensor for the monitoring of neonicotinoid insecticides, salicylic acid and the pH in plant guttation - Guanglei Chu; Siping Yu; Yuhang Wang; Weifeng Zhang; Bing Xue; Jinqi Huang; Zhiwei Wang; Jianghe Luo; Xia Sun; Ming Li (Chemical Engineering Journal, 2024)

Dual-Salt aqueous electrolyte for enhancing Charge-Storage properties of VO2 polymorphic cathodes for Zn-Ion batteries - Jing-Hong Huang; Xu-Feng Luo; Tzu-Yu Kuo; Yu-Hua Lai; Purna Chandra Rath; Chun-Wei Huang; Ming-Hsien Lin; An-Yuan Hou; Ju Li; Yu-Sheng Su; Wen-Wei Wu; Jeng-Kuei Chang (Chemical Engineering Journal, 2024)

A pair of cadinane-type sesquiterpene enantiomers and other chemical constituents from the whole plants of Chloranthus henryi - Meng-Li He; Lian-Lian Xu; Shi-Qin Fu; Yang Liu; Yong-Ming Luo; Fang-You Chen (Biochemical Systematics and Ecology, 2024)

Effects of different biogas slurry application patterns on nitrogen and phosphorus losses in a paddy field - Ming Li; Yinxiu Liu; Linping Luo; Shanshan Ying; Peikun Jiang (Paddy and Water Environment, 2024)

CRISPR-Cas9-mediated editing of GmARM improves resistance to multiple stresses in soybean - Tingting Luo; Chongxuan Ma; Yuanhang Fan; Zhendong Qiu; Ming Li; Yusu Tian; Yuzhuo Shang; Chang Liu; Qingqian Cao; Yuhan Peng; Shuzhen Zhang; Shanshan Liu; et al. (Plant Science, 2024)

Asynchronous hydroclimate variability in Northeast Asia during the last millennium - Anze Chen; Xin Zhou; Shiwei Jiang; Yong Luo; Xuanqiao Liu; Junchi Liu; Xiangzhong Li; Zhenhao Wu; Min Ding; Xiaolin Zhang; Liqiang Xu; Ming Ji; et al. (Palaeogeography, Palaeoclimatology, Palaeoecology, 2024)

Nitrogen cycling in China marginal seas: Progress and challenges - Siqi Wu; Xiuli Yan; Jin-Ming Tang; Ehui Tan; Li Luo; Senwei Tong; Zhen-Zhen Zheng; Yifeng Huang; Min Nina Xu; Shuh-Ji Kao (Marine Chemistry, 2024)

In vitro simulated digestion and fermentation characteristics of pectic polysaccharides from fresh passion fruit (Passiflora edulis f. flavicarpa L.) peel - Ya-Hui Yu; Luo-Bang Wu; Xiaozhen Liu; Li-Chao Zhao; Long-Qing Li; Ming-Yu Jin; Xiangying Yu; Fengyuan Liu; Yuting Li; Lin Li; Jing-Kun Yan (Food Chemistry, 2024)

Silk-fibroin-based nanofibrous scaffolds integrated with nano-engineered living bacteria enabling antibiotic-free accelerated infected wound healing - Ming Teng; Xiaomin Luo; Fen Ao; Liuying Li; Jianyan Feng; Peng Zhang; Xiaomeng Zhang; Xudan Liu; Chen Yang; Lufeng Ji; Xuechuan Wang; Haiyan Ju; et al. (Chemical Engineering Journal, 2024)

Quantitative SERS detection of serum protein biomarkers for assessment of tumor microwave ablation outcomes - Yuzhen Ouyang; Wei Xie; Tian Tang; Xiaoming Su; Shasha Xiao; Zimo Liu; Ming Li; Minghua Wu; Jia Liu; Jia Luo; Pan Chen (Chemical Engineering Journal, 2024)

Micafungin protects mouse heart against doxorubicin-induced oxidative injury via suppressing MALT1-dependent k48-linked ubiquitination of Nrf2 - Li-Qun Lu; Ming-Rui Li; Lin-Lu Huang; Yan-Xi Che; Ya-Nan Qi; Xiu-Ju Luo; Jun Peng (Chemico-Biological Interactions, 2024)

Insight into furfural-tolerant and hydrogen-producing microbial consortia: Mechanism of furfural tolerance and hydrogen production - Li-Li Luo; Ming-Jun Zhu (Bioresource Technology, 2024)

Overexpression of the MiAGL1 gene from mango promoted flowering in transgenic Arabidopsis - Xue-mei Zeng; Xin-hua He; Wen-jing Mo; Hai-xia Yu; Ting-ting Lu; Li-ming Xia; Yi-li Zhang; Jia-wei Zhu; Cong Luo (Journal of Plant Biochemistry and Biotechnology, 2024)

Signal Transduction Associated with Mn-induced Neurological Dysfunction - Xiao-wei Zheng; Yuan-yuan Fang; Jun-jie Lin; Jing-jing Luo; Shao-jun Li; Michael Aschner; Yue-ming Jiang (Biological Trace Element Research, 2024)

Establishment of a callus induction system of Saxifraga stolonifera Meerb. and its response to different elicitors - Lin Song; Ta Zhao; Chun-Li Luo; Jin-Ling Li; Song-Shu Chen; Dan-Dan Li; Jin Liang; Hong-Chang Liu; Fu-Lai Luo; Ming-Jin Huang; Hua-Lei Wang (South African Journal of Botany, 2024)

Histology and transcriptomic analysis reveal the inflammation and affected pathways under 2-methylisoborneol (2-MIB) exposure on grass carp - Huan Han; Jun-ming Zhang; Shuang Ji; Xiang-biao Zeng; Xi-chen Jin; Zi-qian Shen; Bin Xie; Xue-neng Luo; Kang Li; Li-ping Liu (Science of The Total Environment, 2024)

Construction and characterization of a novel Myr-OSADS-CIn micelle for enhanced stability and bioavailability of myricetin - Zhi-Yuan Nie; Xue-Ying Li; Ying-Ying Chen; Yuan-Yuan Deng; Dan-Dan Kuang; Yu-Lin Sun; Huan-Huan Xiao; Qiang-Ming Li; Jian-Ping Luo; Xue-Qiang Zha (Food Bioscience, 2024)

Co-assembly of quinoa protein isolate and shellac as nano-vehicles for naringenin: Characterization, formation mechanism, release behavior and cellular uptake - Ying-Ying Chen; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Multiomics Analyses Explore the Immunometabolic Interplay in the Liver of White Crucian Carp (Carassius cuvieri) After Aeromonas veronii Challenge - Fei Wang; Zi-Rou Zhong; Qing Xie; Jie Ou; Ning-Xia Xiong; Ming-Zhu Huang; Shi-Yun Li; Gang Hu; Zi-Le Qin; Sheng-Wei Luo (Marine Biotechnology, 2024)

Microalgae-mediated heavy metal removal in wastewater treatment: Mechanisms, influencing factors, and novel techniques - Ke Xu; Ming Du; Rao Yao; Jing Luo; Zixi Chen; Chao Li; Anping Lei; Jiangxin Wang (Algal Research, 2024)

Niche convergence and biogeographic history shape elevational tree community assembly in a subtropical mountain forest - Liang-Liang Ma; Sebastian Seibold; Marc W. Cadotte; Jia-Yun Zou; Jie Song; Zhi-Qiong Mo; Shao-Lin Tan; Lin-Jiang Ye; Wei Zheng; Kevin S. Burgess; Zhi-Fa Chen; De-Tuan Liu; et al. (Science of The Total Environment, 2024)

Chronology of late Holocene sediments related to the Qicheng ruins in central China - Ning Di; Huili Yang; Jie Chen; Jinsong Yang; Yipi Li; Jintang Qin; Ming Luo (Quaternary International, 2024)

Maternal PM2.5 exposure and hypospadias risk in Chinese offspring: Insights from a nationwide surveillance-based study - Wenyan Li; Yanhua Li; Wenli Xu; Zhiyu Chen; Yuyang Gao; Zhen Liu; Qi Li; Ming Jiang; Hanmin Liu; Biru Luo; Yu Zhan; Li Dai (Journal of Hazardous Materials, 2024)

Indole-3-acetic acid regulating the initial adhesion of microalgae in biofilm formation - Zhihuai Xie; Zixuan Ou; Meili Zhang; Guotao Tang; Xiaoshi Cheng; Wangbei Cao; Jingyang Luo; Fang Fang; Yingqiang Sun; Ming Li; Juan Cai; Qian Feng (Environmental Research, 2024)

Characterization of a pangolin SARS-CoV-2-related virus isolate that uses the human ACE2 receptor - Luo-Yuan Xia; Xue-Feng Wang; Xiao-Ming Cui; Yi-Ming Zhang; Zhen-Fei Wang; En-Tao Li; Chang-Fa Fan; Ke Song; Yuan-Guo Li; Run-Ze Ye; Fang-Xu Li; Dai-Yun Zhu; et al. (Science China Life Sciences, 2024)

Copper pruning improves root morphology and structure as well as growth of container-grown Ligustrum lucidum seedings - Ming Yang; Jingjing Jia; Zhijuan Tai; Yuxin Luo; Zhuo Yang; Huan Chen; Mai-He Li; Yumei Zhou (New Forests, 2024)

Thermostability-assisted limited proteolysis-coupled mass spectrometry for capturing drug target proteins and sites - Liu Yang; Chen-Wan Guo; Qi-Ming Luo; Zi-Fan Guo; Ling Chen; Yasushi Ishihama; Ping Li; Hua Yang; Wen Gao (Analytica Chimica Acta, 2024)

Rock moisture reinforces belowground water storage under different precipitation scenarios and vegetation coverage - Zhanbin Luo; Jun Fan; Ming'an Shao; Qian Yang; Minghui Li (Journal of Hydrology, 2024)

Kidney-targeted antioxidant salvianolic acid B nanoparticles restoring lysosome homeostasis for acute kidney injury therapy - Jian-Li Chen; Xiao-Hui Jia; Xuan Wu; Ming-Heng Yuan; Xinyue Xia; Dan Yin; Xu Chen; Ze-Yun Gu; Jia-Zheng Liu; Li-Ping Bai; Kathy Qian Luo; Jianfang Wang; et al. (Chemical Engineering Journal, 2024)

Decoding plant specialized metabolism: new mechanistic insights - Qianqian Li; Susan Duncan; Yuping Li; Shuxian Huang; Ming Luo (Trends in Plant Science, 2024)

Role and action mechanisms of miR-149 and miR-31 in regulating function of pig cumulus cells and oocytes - Jia-Shun Wu; Shuai Gong; Min Zhang; Rui-Jie Ma; Hui-Li Wang; Ming-Jiu Luo; Nan He; Jing-He Tan (Theriogenology, 2024)

Recent advances in swine wastewater treatment technologies for resource recovery: A comprehensive review - Lingling Zhou; Ming Liang; Dongqing Zhang; Xiaojun Niu; Kai Li; Zitao Lin; Xiaojun Luo; Yuying Huang (Science of The Total Environment, 2024)

Vertical migration behavior simulation and prediction of Pb and Cd in co-contaminated soil around Pb-Zn smelting slag site - Ying Luo; Zhe Wang; Yong-De Zhang; Jia-Qian Zhang; Qiu-ping Zeng; Zhen-Long Zhang; Duan Tian; Chao Li; Chao-liang Peng; Kai Ye; Yi-Ming Chen; Feng-Yu Huang; et al. (Journal of Hazardous Materials, 2024)

Rational biodiesel production from oxidation stability perspective: Evaluation of lipid-soluble carbonyl compound formation in the seed oil and biodiesel with long-term storage - Xiao-Hui Peng; Hua-Ming Xiao; Shuai Zhao; Dilshad Hussain; Jian-Li Chen; Dan Luo; Dan Wang; Xin Lv; Xian Wang; Hong Chen; Fang Wei (Fuel, 2024)

2D ZIF-8 derived N-doped porous carbon nanosheets for high-performance Li-Se batteries - Xu-Wei Luo; Ming-Ran Zhou; Mao-Jin Ran; Dao-Xiang Xun; Jia-Le He; Zhi-Yi Hu; Hemdan S.H. Mohamed; Jing Liu; Li-Hua Chen; Yu Li; Bao-Lian Su (Chemical Engineering Journal, 2024)

Inhibition of PARP1 improves cardiac function after myocardial infarction via up-regulated NLRC5 - Jia-Ming Luo; Hong-Bin Lin; Ya-Qian Weng; Ying-Hui Lin; Lu-Ying Lai; Ji Li; Feng-Xian Li; Shi-Yuan Xu; Hong-Fei Zhang; Wei Zhao (Chemico-Biological Interactions, 2024)

VqNAC44 enhances stilbene synthesis and disease resistance in Chinese wild grape by interacting with VqMYB15 - Linxia Wang; Ming Zhang; Jia Li; Qin Luo; Qian Yao; Qiuyu Huang; Runxin Zhang; Dong Duan (Plant Science, 2024)

Existing levels of biodiversity and river location may determine changes from small hydropower developments - Qingyi Luo; Shuyin Li; Tsuyoshi Kinouchi; Naicheng Wu; Xiaocheng Fu; Chang Ling; Qinghua Cai; Ming-Chih Chiu; Vincent H. Resh (Journal of Environmental Management, 2024)

Toxin gene detection and antibiotic resistance of Clostridium perfringens from aquatic sources - Mengxuan Li; Ying Wang; Bingyu Hou; Yibao Chen; Ming Hu; Xiaonan Zhao; Qing Zhang; Lulu Li; Yanbo Luo; Yuqing Liu; Yumei Cai (International Journal of Food Microbiology, 2024)

pH-shifted quinoa protein isolate-based nanocarriers for naringenin: Structure characterization and stability evaluation - Ying-Ying Chen; Qiang-Ming Li; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Food Hydrocolloids, 2024)

Alleviating the adverse effects of Cd–Pb contamination through the application of silicon fertilizer: Enhancing soil microbial diversity and mitigating heavy metal contamination - Ke Ren; Xiongwei Yang; Jian Li; Hongyan Jin; Kaiyuan Gu; Yi Chen; Ming Liu; Yigui Luo; Yonglei Jiang (Chemosphere, 2024)

Compound flood effects, challenges and solutions: Lessons toward climate-resilient Chinese coastal cities - Faith Ka Shun Chan; Xiaohui Lu; Jianfeng Li; Yangchen Lai; Ming Luo; Yongqin David Chen; Donghai Wang; Nan Li; Wei-Qiang Chen; Yong-Guan Zhu; Hing Kai Chan (Ocean & Coastal Management, 2024)

Sesquiterpenoid derivatives isolated from a liquid culture of Hypholoma capnoides 819 - Yu-Ting Wang; Hong-Yu Tan; Xue Zhao; Yu Yang; Rui Xu; Shuai-Ming Zhu; Hao Ma; Fu-Yao Luo; Cai-Hong Dong; Chang-Wei Li (Phytochemistry, 2024)

CRISPR/Cas9-mediated ebony knockout causes melanin pigmentation and prevents moth Eclosion in Ectropis grisescens - Jia-Li Li; Shun-Si Li; Zi-Jun Luo; Ji Lu; Xiao-Ming Cai; Zong-Xiu Luo; Lei Bian; Chun-Li Xiu; Nan-Xia Fu; Nai-Yong Liu; Zhao-Qun Li (Pesticide Biochemistry and Physiology, 2024)

Methyl jasmonate regulation of pectin polysaccharides in Cosmos bipinnatus roots: A mechanistic insight into alleviating cadmium toxicity - Chun-Yu Fan; Xiao-Fang Yu; Yu-Jia Liu; Xiao-Xuan Zeng; Fu-Wen Luo; Xian-Tong Wang; Xuan Yang; Xiao-Yu Wang; Xiao Xue; Li-Juan Yang; Ting Lei; Ming-Yan Jiang; et al. (Environmental Pollution, 2024)

Dihydroartemisinin abolishes cisplatin-induced nephrotoxicity in vivo - Yan Luo; Jiaxing Zhang; Yue Jiao; Hao Huang; Liangshan Ming; Yunlei Song; Yanlong Niu; Xiaolu Tang; Liwei Liu; Yi Li; Yumao Jiang (Journal of Natural Medicines, 2024)

Sustainable valorizing high-protein feather waste utilization through solid-state fermentation by keratinase-enhanced Streptomyces sp. SCUT-3 using a novel promoter - Wen-Jun Lu; Ming-Shu Zhang; De-Lin Lu; Zhi-Wei Li; Zhen-Dong Yang; Lei Wu; Jing-Tao Ni; Wei-Dong Chen; Jun-Jin Deng; Xiao-Chun Luo (Waste Management, 2024)

Heat shock induces HuR-dependent MKP-1 posttranslational regulation through the p38 MAPK signaling cascade - Xiao-juan Ma; Zhan Sun; Yi-ping Wang; Xue-ping Yao; Ting-ting Luo; Ya-li Bao; Dina Ainiwaer; Tian Zhang; Hengyi Zhu; Yan Zhang; Fei-ming Hu; Wen-yan Yu (Tissue and Cell, 2024)

A new method of the hydrocarbon secondary migration research: Numerical simulation - Hao Xu; Jun Li; Xiaorong Luo; Ming Cheng; Chao Li; Xiaoying Zhang; Huanquan Pan (Marine and Petroleum Geology, 2024)

Study on the elastic stiffness calculation method of single-bolted steel-bamboo scrimber-steel shear connections - Ming Zhang; Haodong Fan; Wenlong Li; Hongsen Wu; Zhixiang Yu; Shixing Zhao; Qiaoling Zhou; Changliang Liu; Yongjing Li; Haiyan Luo; Alireza Behnejad; Gerry Parke (Engineering Structures, 2024)

Synergistic enhanced kinetics and dual active sites in PANI@V2O5 nanoflower for superior Ca2+ ion storage - Ping Luo; Dongyao Zhu; Chunli Zuo; Wenwei Zhang; Ming Li; Feiyang Chao; Gongtao Yu; Wenhui Zhong; Qinyou An (Chemical Engineering Journal, 2024)

OsNAC103, an NAC transcription factor negatively regulates plant height in rice - Yan Li; Liming Zhao; Chiming Guo; Ming Tang; Wenli Lian; Siyu Chen; Yuehan Pan; Xiaorong Xu; Chengke Luo; Yin Yi; Yuchao Cui; Liang Chen (Planta, 2024)
Main conclusion OsNAC103 negatively regulates rice plant height by influencing the cell cycle and crosstalk of phytohormones. Abstract Plant height is an important characteristic of rice farming and is directly related to agricultural yield. Although there has been great progress in research on plant growth regulation, numerous genes remain to be elucidated. NAC transcription factors are widespread in plants and have a vital function in plant growth. Here, we observed that the overexpression of OsNAC103 resulted in a dwarf phenotype, whereas RNA interference (RNAi) plants and osnac103 mutants showed no significant difference. Further investigation revealed that the cell length did not change, indicating that the dwarfing of plants was caused by a decrease in cell number due to cell cycle arrest. The content of the bioactive cytokinin N 6 -Δ 2 -isopentenyladenine (iP) decreased as a result of the cytokinin synthesis gene being downregulated and the enhanced degradation of cytokinin oxidase. OsNAC103 overexpression also inhibited cell cycle progression and regulated the activity of the cell cyclin OsCYCP2;1 to arrest the cell cycle. We propose that OsNAC103 may further influence rice development and gibberellin–cytokinin crosstalk by regulating the Oryza sativa homeobox 71 ( OSH71 ). Collectively, these results offer novel perspectives on the role of OsNAC103 in controlling plant architecture.

Quantitative assessment of expected direct economic losses of buildings for debris flows in multiple rainfall intensity scenarios in Yangling Gully, Southwest China - Ming Chen; Yuting Luo; Chuan Tang; Ning Li (Natural Hazards, 2024)

Myricetin-based fluorescence probes with AIE and ESIPT properties for detection of hydrazine in the environment and fingerprinting - Wei Xiao; Qing Zhang; Dong Hui You; Wei Xue; Feng Peng; Nian Bing Li; Guang Ming Zhou; Hong Qun Luo (Analytica Chimica Acta, 2024)

China's subtropical deciduous plants are more sensitive to climate change than evergreen plants by flowering phenology - Hong‐Li Li; Arshad Ali; Xu Luo; Ke Liao; Nan Sun; Ming‐Shan Xu; Long‐Bin Sha; Dong He; Yan‐Jun Du; Wei‐Wei Sun; Xiao‐Dong Yang (Global Change Biology, 2024)
The ongoing climate change‐induced shifts in flowering phenology have emerged as a consequential force impacting biodiversity and ecosystems. Despite the globally recognized significance of flowering phenology as a key reproductive attribute, studies in subtropical regions have been relatively fewer, particularly in comparison to temperate and cold regions. Additionally, the nuanced response of deciduous and evergreen plants to climate change remains insufficiently explored. In addressing this gap, we built a phenological model and a generalized linear mixed effect model to assess the differential responses of key flowering phenological traits, that is, first flowering date (FFD), peak flowering date (PFD), end of flowering date (EFD), and flowering duration (FD), to climate factors (temperature and precipitation) between deciduous and evergreen plants. We observed distinct responses in flowering phenological traits to climate change between deciduous and evergreen plants. Specifically, the advancement of FFD, PFD, and EFD in deciduous in response to temperature rise exceeded that in evergreen plants. FD in evergreen plants exhibited a stronger extension to temperature increase compared to deciduous. Conversely, the phenological change of evergreen plants in response to decreasing precipitation was greater than that of deciduous ones. Since temperature is a decisive climatic factor in affecting phenological changes, climate change‐induced advances in flowering phenology of deciduous plants are still larger than evergreen plants. Projections from our phenological model under future climate scenarios (SSP 1‐2.6 and SSP 5‐8.5) indicate a continuous enlargement of difference in flowering phenology between deciduous and evergreen plants, with this trend escalating into the future (2100>2070>2050>2030). The larger extension in FD of evergreens to climate change suggests a potential increase in their proportion within subtropical forest communities relative to deciduous plants. These insights contribute significantly to our understanding of the intricate dynamics of climate‐induced changes in subtropical plant ecosystems.

Lignan glucosides from Gentiana macrophylla with potential anti-arthritis and hepatoprotective activities - Pei-Qi Huang; Kai-Wen Kang; Dan-Yu Huang; Chun-Lin Zhao; Hao Zheng; Yong-Xin Luo; Yan Wen; Ming-Feng Zou; Dong-Li Li; Ri-Hui Wu; Yun-Cai Tian; Yong Tian; et al. (Phytochemistry, 2024)

Preparation and characterization of lotus root starch based bioactive edible film containing quercetin-encapsulated nanoparticle and its effect on grape preservation - Ya-Fan Zeng; Ying-Ying Chen; Yuan-Yuan Deng; Chao Zheng; Cheng-Zhi Hong; Qiang-Ming Li; Xue-Fei Yang; Li-Hua Pan; Jian-Ping Luo; Xue-Ying Li; Xue-Qiang Zha (Carbohydrate Polymers, 2024)

Advances in regulating vitamin K2 production through metabolic engineering strategies - Yan Liu; Jian Wang; Jun-bao Huang; Xiang-fei Li; Yu Chen; Kun Liu; Ming Zhao; Xi-lin Huang; Xu-li Gao; Ya-ni Luo; Wei Tao; Jing Wu; et al. (World Journal of Microbiology and Biotechnology, 2024)

Diversity and distribution of yeasts in intertidal zones of China - Hai-Yan Zhu; Da-Yong Han; Liang-Chen Guo; Jun-Ning Li; Xu-Yang Wei; Ri-Peng Zhang; Qi-Ming Wang; Yu-Jie Shang; Lu-Jun Luo; Yu-Hua Wei; Xin-Zhan Liu; Feng-Yan Bai (Frontiers in Marine Science, 2023)
China has the second greatest extent of intertidal zones in the world. The intertidal zone is the most dynamic environments in the biosphere and potentially supports high biodiversity. Marine yeasts show excellent performance in various industrial, environmental and medical applications, however, the marine yeast diversity has rarely been studied in China. In this study, we collected 1241 samples including marine sediments, marine water, plants, and benthos at 161 GPS sites in different types of intertidal zones along the Chinese coastline from north to south. A total of 4436 strains were isolated from these samples using different methods and 286 species including 39 potential novel species were identified from these strains based on the internal transcribed spacer (ITS) region or the D1/D2 domain of the large subunit rRNA gene sequence analysis. The majority of the yeast species in different geographical locations belong to the five orders Serinales , Saccharomycetales , Tremellales , Sporidiobolales , and Pichiales . The yeast species diversity varied depending on sample types, depth of marine sediments, intertidal zone types and geographical locations. Mean annual temperature (MAT), salinity and pH had the greatest effect on the community structures of the yeasts isolated from the intertidal zones. This study represents one of the most comprehensive surveys of marine yeasts in China to date and provides a better understanding of marine yeast diversity and distribution.

Dietary inositol improved glucose and lipid metabolism mediated by the Insulin-PI3K-Akt signaling pathway in Pacific white shrimp (Litopenaeus vannamei) - Jingjing Lu; Xinyue Tao; Ming Li; Xin Zhang; Qicun Zhou; Jiaxiang Luo; Tingting Zhu; Lefei Jiao; Min Jin (Aquaculture, 2023)

Multiple paternally inherited chloroplast capture events associated with Taxus speciation in the Hengduan Mountains - Han-Tao Qin; Michael Mӧller; Richard Milne; Ya-Huang Luo; Guang-Fu Zhu; De-Zhu Li; Jie Liu; Lian-Ming Gao (Molecular Phylogenetics and Evolution, 2023)

Intensification of heatwaves in Central Asia from 1981 to 2020 – Role of soil moisture reduction - Xuechun Wang; Yongkang Li; Yaning Chen; Yupeng Li; Chuan Wang; Azamat Kaldybayev; Ruikun Gou; Ming Luo; Weili Duan (Journal of Hydrology, 2023)

Nonthermal plasma-activated polyvalent cerium-manganese bimetallic (hydro)oxide-functionalized nanographene for the removal of thallium(I) contaminants and mechanism exploration - Dongping Song; Tao Huang; Yinglan Luo; Di Wu; Shouze Li; Yujie Yan; Chaojun Yang; Qi Fang; Yuxing Wang; Yuxuan Feng; Nan Shang; Ming Xia; et al. (Journal of Cleaner Production, 2023)

Energy-efficient fluorine-free electro-refining of crude lead in a green methanesulfonic acid system - You-gang Li; Cong Chang; Jun-jie Qu; Chang-liu Xiang; Tao Luo; Shan-shan Liu; Shuai Li; Sheng-hai Yang; Heng-hui Wang; Xiao-bo Min; Chang-hong Wang; Yong-ming Chen (Journal of Environmental Chemical Engineering, 2023)

Effects of polyethylene microplastics with different particle sizes and concentrations on the community structure and function of periphytic biofilms - Weiyu Li; Dan Luo; Ning Yan; Lingzhan Miao; Tanveer M. Adyel; Ming Kong; Jun Hou (Journal of Environmental Chemical Engineering, 2023)

Synergy of adsorbates and surface-reconstructed interfaces in Fe7S8/NiS2 for efficient oxygen evolution at high current density - Yanli Yu; Yucheng Wu; Wei Luo; Sijun Li; Yimin Jiang; Wei Shen; Rongxing He; Ming Li (Chemical Engineering Journal, 2023)

Abnormal grey matter structural changes in patients with end-stage kidney disease and mild cognitive impairment: correlations with clinical features - Huijie Yuan; Zhaoyao Luo; Wen Gu; Shaohui Ma; Guangyu Li; Dun Ding; Xueying Ma; Peng Li; Jing Yang; Xiaoling Xu; Junya Mu; Ming Zhang (Metabolic Brain Disease, 2023)
End-stage kidney disease and mild cognitive impairment (ESKD-MCI) affect the quality of life and long-term treatment outcomes of patients affected by these diseases. Clarifying the morphological changes from brain injuries in ESKD-MCI and their relationship with clinical features is helpful for the early identification and intervention of MCI before it progresses to irreversible dementia. This study gathered data from 23 patients with ESKD-MCI, 24 patients with ESKD and non-cognitive impairment (NCI), and 27 health controls (HCs). Structural magnetic resonance studies, cognitive assessments, and general clinical data were collected from all participants. Voxel-based morphometry analysis was performed to compare grey matter (GM) volume differences between the groups. The patients’ GM maps and clinical features were subjected to univariate regression to check for possible correlations. Patients with ESKD-MCI displayed significantly more impairments in multiple cognitive domains, including global cognition, visuospatial and executive function, and memory, compared to patients with ESKD-NCI. Using a more liberal threshold ( P < 0.001, uncorrected), we found that compared to patients with ESKD-NCI, patients with ESKD-MCI exhibited clusters of regions with lower GM volumes, including the right hippocampus (HIP), parahippocampal gyrus (PHG), Rolandic operculum, and supramarginal gyrus. The volumes of the right HIP and PHG were negatively correlated with serum calcium levels. ESKD-MCI was associated with a subtle volume reduction of GM in several brain areas known to be involved in memory, language, and auditory information processing. We speculate that these slight morphometric impairments may be associated with disturbed calcium metabolism.

Elevational changes in soil properties shaping fungal community assemblages in terrestrial forest - Huan Luo; Chunyan Wang; Kaile Zhang; Li Ming; Honglong Chu; Haihua Wang (Science of The Total Environment, 2023)

Sedimentary facies and chronological study for a Late Pleistocene sand layer with swash cross bedding within a sand hill at north of Poyang Lake, as inferred from sedimentary structure and optical dating of K-feldspar and quartz grains - Zhijun Gong; Qiwei Li; Ming Luo; Chaocheng Dai; Huaming Peng (Quaternary International, 2023)

Characterization of the Clostridium perfringens phage endolysin cpp-lys and its application on lettuce - Xiaonan Zhao; Lulu Li; Qing Zhang; Mengxuan Li; Ming Hu; Yanbo Luo; Xiaohui Xu; Yibao Chen; Yuqing Liu (International Journal of Food Microbiology, 2023)

Dual N-modification enables high-performance Solid-State Li metal batteries with Li5.5PS4.5Cl1.5 - Chaochao Wei; Ru Wang; Zhongkai Wu; Qiyue Luo; Ziling Jiang; Liang Ming; Long Zhang; Hongcheng Lu; Guangshe Li; Liping Li; Chuang Yu; Shijie Cheng (Chemical Engineering Journal, 2023)

Introgression of the bread wheat D genome encoded Lr34/Yr18/Sr57/Pm38/Ltn1 adult plant resistance gene into Triticum turgidum (durum wheat) - Hongyu Li; Peng Zhang; Ming Luo; Mohammad Hoque; Soma Chakraborty; Brenton Brooks; Jianbo Li; Smriti Singh; Kerrie Forest; Allan Binney; Lianquan Zhang; Diane Mather; et al. (Theoretical and Applied Genetics, 2023)
Key Message Lack of function of a D-genome adult plant resistance gene upon introgression into durum wheat. Abstract The wheat Lr34/Yr18/Sr57/Pm38/Ltn1 adult plant resistance gene ( Lr34 ), located on chromosome arm 7DS, provides broad spectrum, partial, adult plant resistance to leaf rust, stripe rust, stem rust and powdery mildew. It has been used extensively in hexaploid bread wheat (AABBDD) and conferred durable resistance for many decades. These same diseases also occur on cultivated tetraploid durum wheat and emmer wheat but transfer of D genome sequences to those subspecies is restricted due to very limited intergenomic recombination. Herein we have introgressed the Lr34 gene into chromosome 7A of durum wheat. Durum chromosome substitution line Langdon 7D(7A) was crossed to Cappelli ph1c , a mutant derivative of durum cultivar Cappelli homozygous for a deletion of the chromosome pairing locus Ph1 . Screening of BC 1 F 2 plants and their progeny by KASP and PCR markers, 90 K SNP genotyping and cytology identified 7A chromosomes containing small chromosome 7D fragments encoding Lr34 . However, in contrast to previous transgenesis experiments in durum wheat, resistance to wheat stripe rust was not observed in either Cappelli/Langdon 7D(7A) or Bansi durum plants carrying this Lr34 encoding segment due to low levels of Lr34 gene expression. Key message

Advances and Applications of Brain Organoids - Yang Li; Peng-Ming Zeng; Jian Wu; Zhen-Ge Luo (Neuroscience Bulletin, 2023)
Understanding the fundamental processes of human brain development and diseases is of great importance for our health. However, existing research models such as non-human primate and mouse models remain limited due to their developmental discrepancies compared with humans. Over the past years, an emerging model, the “brain organoid” integrated from human pluripotent stem cells, has been developed to mimic developmental processes of the human brain and disease-associated phenotypes to some extent, making it possible to better understand the complex structures and functions of the human brain. In this review, we summarize recent advances in brain organoid technologies and their applications in brain development and diseases, including neurodevelopmental, neurodegenerative, psychiatric diseases, and brain tumors. Finally, we also discuss current limitations and the potential of brain organoids.

Role of sonic hedgehog signaling pathway in the regulation of ion channels: focus on its association with cardio-cerebrovascular diseases - Ming-Rui Li; Xiu-Ju Luo; Jun Peng (Journal of Physiology and Biochemistry, 2023)

Ångstrom-scale silver particles ameliorate collagen-induced and K/BxN-transfer arthritis in mice via the suppression of inflammation and osteoclastogenesis - Ze-Hui He; Jing-Tao Zou; Xia Chen; Jiang-Shan Gong; Ya Chen; Ling Jin; Yi-Wei Liu; Shan-Shan Rao; Hao Yin; Yi-Juan Tan; Zun Wang; Wei Du; et al. (Inflammation Research, 2023)

Analysis of spatial and temporal variation of vegetation NPP in Daning River Basin and its driving forces - Wenqian Bai; Li He; Zhengwei He; Xueman Wang; Yang Zhao; Rui Qu; Fang Luo; Xin Chen; Zhifei Wang; Ming Liu (International Journal of Remote Sensing, 2023)

Whole-genome resequencing reveals genetic diversity and signatures of selection in mono-female grass carp (Ctenopharyngodon idella) - Dong-Yang Zhang; Xin-Ming Liu; Wei-Jie Huang; Yao Wang; Khan Anwarullah; Li-Fei Luo; Ze-Xia Gao (Aquaculture, 2023)

Inhibition of postharvest rachis browning of table grapes by sulfur dioxide: Evidence from phenolic metabolism and sulfur assimilation - Zhenbiao Li; Siqi Chen; Ming Qi; Mingyi Yang; Hemao Yuan; Yanqun Xu; Jing Huang; Dong Li; Wei Zhou; Yaya Yuan; Zisheng Luo; Li Li (Postharvest Biology and Technology, 2023)

Polyurethane sponge loading improves the suspension of magnetic materials without affecting the Pb(Ⅱ) adsorption - Ruifeng Li; Guihong Lan; Yongqiang Liu; Qiao Sun; Bin Luo; Ming Zhang; Haiyan Qiu; Bo Xu; Chunping Deng (Journal of Environmental Chemical Engineering, 2023)

Molecular characterization of stable QTL and putative candidate genes for grain zinc and iron concentrations in two related wheat populations - Mengjing Sun; Qiaoling Luo; Qi Zheng; Jingyang Tong; Yue Wang; Jie Song; Yelun Zhang; Zongjun Pu; Jianmin Zheng; Lianzheng Liu; Anding Zhou; Awais Rasheed; et al. (Theoretical and Applied Genetics, 2023)

Tree communities and functional traits determine herbivore compositional turnover - Ming-Qiang Wang; Zhixin Wen; Jinzhao Ke; Douglas Chesters; Yi Li; Jing-Ting Chen; Arong Luo; Xiaoyu Shi; Qing-Song Zhou; Xiao-Juan Liu; Keping Ma; Helge Bruelheide; et al. (Oecologia, 2023)

Exploration of glycosyltransferases mutation status in cervical cancer reveals PARP14 as a potential prognostic marker - Hui Wang; Shen Luo; Xin Wu; Yuanyuan Ruan; Ling Qiu; Hao Feng; Shurong Zhu; Yanan You; Ming Li; Wenting Yang; Yanding Zhao; Xiang Tao; et al. (Glycoconjugate Journal, 2023)
This study investigates the potential role of Glycosyltransferases (GTs) in the glycosylation process and their association with malignant tumors. Specifically, the study focuses on PARP14, a member of GTs, and its potential as a target for tumors in the diagnosis and treatment of cervical cancer. To gather data, the study used somatic mutation data, gene expression data and clinical information from TCGA-CESE dataset as well as tissue samples from cervical cancer patients. Further verification was conducted through RT-qPCR and immunohistochemistry staining on cervical cancer tissues to confirm the expression of PARP14. The study utilized Kaplan-Meier for survival analysis of cervical cancer patient and found significant mutational abnormalities in GTs. The high frequency mutated gene was identified as PARP14. RT-qPCR revealed significantly higher mRNA expression of PARP14 compared to precancerous tissue. Using IHC combined with Kaplan-Meier,patients in the PARP14 high expression group had a better prognosis than the low expression group. The study identified PARP14 as a frequently mutated gene in cervical cancer and proposed its potential role in diagnosis and treatment.

Contaminant occurrence, water quality criteria and tiered ecological risk assessment in water: A case study of antifouling biocides in the Qiantang River and its estuary, Eastern China - Hai-Wei Luo; Jian-Ming Jiang; Xun Wang; Minjie Li; Jin-Jian Ding; Wen-Jun Hong; Liang-Hong Guo (Marine Pollution Bulletin, 2023)

Spatial-temporal changes of compound temperature-humidity extremes in humid subtropical high-density cities: An observational study in Hong Kong from 1961 to 2020 - Yueyang He; Zixuan Wang; Hau Man Wong; Guangzhao Chen; Chao Ren; Ming Luo; Yuguo Li; Tsz-cheung Lee; Pak Wai Chan; Janice Ying-en Ho; Edward Ng (Urban Climate, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

N-acyl homoserine lactone mediating initial adhesion of microalgal biofilm formation - Zixuan Ou; Xindi Chen; Xinming Wu; Changren Zhou; Kaijie Zhang; Jingyang Luo; Fang Fang; Yinqiang Sun; Ming Li; Qian Feng (Environmental Research, 2023)

Codelivery of vorinostat and chloroquine by autophagy-inhibitory hollow ZrO2 nanoshells for synergistic combination chemotherapy - Jian-Li Chen; Xiao-Hui Jia; Xinyue Xia; Xuan Wu; Yan-Neng Xu; Gang Yuan; Ze-Yun Gu; Kathy Qian Luo; Ming-Heng Yuan; Ruibin Jiang; Jianfang Wang; Xiao-Ming Zhu (Chemical Engineering Journal, 2023)

Meteorological and hydrological droughts in the Lancang-Mekong River Basin: Spatiotemporal patterns and propagation - Xuan Luo; Xian Luo; Xuan Ji; Wenting Ming; Lin Wang; Xin Xiao; Jianan Xu; Yue Liu; Yungang Li (Atmospheric Research, 2023)

Driving forces and their interactions of soil erosion in soil and water conservation regionalization at the county scale with a high cultivation rate - Bang-lin Luo; Jiang-wen Li; Chun-ming Gong; Shou-qin Zhong; Chao-fu Wei (Journal of Mountain Science, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Anti-apoptotic effect of adrenomedullin gene delivery on Leydig cells by suppressing TGF-β1 via the Hippo signaling pathway - You-wen Luo; Xia-lian Zhu; Ming-yong Li; Jian-hua Zhou; Zhi-min Yang; Tao Tong; Bing-hai Chen; Song-lin Qin; Bo-long Liu; Wei Hu (Reproductive Toxicology, 2023)

Dual-modular immunosensor for bongkrekic acid detection using specific monoclonal antibody - Xue-Ming Cao; Li-Hua Li; Hong-Zhi Liang; Jia-Dong Li; Zi-Jian Chen; Lin Luo; Yi-Na Lu; Yu-Xin Zhong; Yu-Dong Shen; Hong-Tao Lei; Hong Wang; Zhen-Lin Xu (Journal of Hazardous Materials, 2023)

Rational design of surface reconstruction with pinning effect to relieving bulk fatigue for high energy single-crystal Ni-rich cathodes - Ying-de Huang; Han-Xin Wei; Pei-Yao Li; Lin-Bo Tang; Yu-Hong Luo; Xin-Ming Fan; Cheng Yan; Jing Mao; Ke-Hua Dai; He-Zhang Chen; Xia-hui Zhang; Jun-chao Zheng (Chemical Engineering Journal, 2023)

Drivers of global surface urban heat islands: Surface property, climate background, and 2D/3D urban morphologies - Ledi Shao; Weilin Liao; Peilin Li; Ming Luo; Xuehui Xiong; Xiaoping Liu (Building and Environment, 2023)

Chemical constituents from Chloranthus henryi Hemsl. (Chloranthaceae) and their chemotaxonomic significance - Fang-You Chen; Meng-Li He; Lian-Lian Xu; Bao Yang; Yong-Ming Luo (Biochemical Systematics and Ecology, 2023)

Corrigendum to: “Exposure to polystyrene microplastics impairs hippocampus-dependent learning and memory in mice” J. Hazard. Mater. 430 (2022) 128431 - Chiang-Wen Lee; Lee-Fen Hsu; I.-Lin Wu; Yung-Li Wang; Wei-Chen Chen; Yan-Jun Liu; Lu-Tang Yang; Chong-Lun Tan; Yueh-Hsia Luo; Chia-Ching Wang; Hui-Wen Chiu; Thomas Chung-Kuang Yang; et al. (Journal of Hazardous Materials, 2023)

Simulation of anaerobic co-digestion of steam explosion pulping wastewater with cattle manure: Focusing on degradation and inhibition of furfural - Pengfei Li; Xinyu Wei; Ming Wang; Di Liu; Jie Liu; Zhanjiang Pei; Fengmei Shi; Su Wang; Xin Zuo; Dan Li; Hongjiu Yu; Nan Zhang; et al. (Bioresource Technology, 2023)

Beta-naphthoflavone increases the differentiation of osteoblasts and suppresses adipogenesis in human adipose derived stem cells involving STAT3 pathway - Ming Lu; Min Li; Tao Luo; Yongsui Li; Mingxin Wang; Huashi Xue; Mengchen Zhang; Qiu Chen (Molecular & Cellular Toxicology, 2023)

The combined effect of seawater salinity and duration on the survival and growth of eelgrass Zostera marina - Yan-Hao Zhang; Jian-Du Li; Wen-Jie Yan; Fan-Shu Luo; Li Wang; Li-Ming Zuo; Jun-Ge Xu; Wen-Tao Li; Pei-Dong Zhang (Aquatic Botany, 2023)

Correction to: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2023)

Site-directed transformants with E407K substitution in Bcmdl1 possesses different fitness from field anilinopyrimidine resistant isolates with E407K mutation in Botrytis cinerea - Fei Fan; Ming-Yi Wu; Yong-Xu Zhu; Guo-Qing Li; Chao-Xi Luo (Pesticide Biochemistry and Physiology, 2023)

Evaluating the threshold limit value of acceptable exposure concentration for exposure to bioaerosols in a wastewater treatment plant: Reverse-quantitative microbial risk assessment and sensitivity analysis - Beibei Cui; Dongzi An; Haojun Li; Xi Luo; Hao Zhu; Ming Li; Xiaojun Ai; Jiaxin Ma; Wajid Ali; Cheng Yan (Journal of Hazardous Materials, 2023)

Formation of microbial products by activated sludge in the presence of sulfamethoxazole (SMZ) and zinc oxide nanoparticles (ZnO NPs) in long-term operated sequencing batch reactors - Chao Li; Chaoyue Wang; Jingyang Luo; Jiashun Cao; Liangshan Hao; Yang Liu; Ming Xu (Journal of Environmental Chemical Engineering, 2023)

The cotton protein GhIQD21 interacts with GhCaM7 and modulates organ morphogenesis in Arabidopsis by influencing microtubule stability - Xing Li; Li Wang; Yupeng Cui; Chen Liu; Yujie Liu; Lili Lu; Ming Luo (Plant Cell Reports, 2023)

Caveolin-1-Mediated Cholesterol Accumulation Contributes to Exaggerated mGluR-Dependent Long-Term Depression and Impaired Cognition in Fmr1 Knockout Mice - Li Luo; Le Yang; Kun Zhang; Shi-Meng Zhou; Yan Wang; Liu-Kun Yang; Bin Feng; Shui-Bing Liu; Yu-Mei Wu; Ming-Gao Zhao; Qi Yang (Molecular Neurobiology, 2023)
Fragile X syndrome (FXS) is one of the most common inherited mental retardation diseases and is caused by the loss of fragile X mental retardation protein (FMRP) expression. The metabotropic glutamate receptor (mGluR) theory of FXS states that enhanced mGluR-dependent long-term depression (LTD) due to FMRP loss is involved in aberrant synaptic plasticity and autistic-like behaviors, but little is known about the underlying molecular mechanism. Here, we found that only hippocampal mGluR-LTD was exaggerated in adolescent Fmr1 KO mice, while N-methyl-D-aspartate receptor (NMDAR)-LTD was intact in mice of all ages. This development-dependent alteration was related to the differential expression of caveolin-1 (Cav1), which is essential for caveolae formation. Knockdown of Cav1 restored the enhanced mGluR-LTD in Fmr1 KO mice. Moreover, hippocampal Cav1 expression in Fmr1 KO mice induced excessive endocytosis of the α-amino-3-hydroxyl-5-methyl-4-isoxazolepropionate (AMPA) receptor subunit GluA2. This process relied on mGluR1/5 activation rather than NMDAR. Interference with Cav1 expression reversed these changes. Furthermore, massive cholesterol accumulation contributed to redundant caveolae formation, which provided the platform for mGluR-triggered Cav1 coupling to GluA2. Importantly, injection of the cholesterol scavenger methyl-β-cyclodextrin (Mβ-CD) recovered AMPA receptor trafficking and markedly alleviated hyperactivity, hippocampus-dependent fear memory, and spatial memory defects in Fmr1 KO mice. Together, our findings elucidate the important role of Cav1 in mediating mGluR-LTD enhancement and further inducing AMPA receptor endocytosis and suggest that cholesterol depletion by Mβ-CD during caveolae formation may be a novel and safe strategy to treat FXS.

Src inhibition induces mitotic arrest associated with chromosomal passenger complex - Song Yang; Youguang Luo; Mulin Yang; Hua Ni; Hanxiao Yin; Ming Hu; Min Liu; Jun Zhou; Yunfan Yang; Dengwen Li (Cell and Tissue Research, 2023)

Sugar intake and risk of hypertension: a systematic review and dose–response meta-analysis of cohort and cross-sectional studies - Yang Zhao; Yifei Feng; Yunhong Zeng; Wencheng Di; Xinping Luo; Xiaojing Wu; Ruiyun Guan; Lidan Xu; Xingjin Yang; Yang Li; Yuying Wu; Xiaoyan Wu; et al. (Critical Reviews in Food Science and Nutrition, 2023)

Stability analysis for pre-reinforced piles within high cutting slope - Yu Luo; Ming-li Xiao (European Journal of Environmental and Civil Engineering, 2023)

Air pollution exposure and heart failure: A systematic review and meta-analysis - Dongdong Zhang; Weiling Chen; Cheng Cheng; Hao Huang; Xi Li; Pei Qin; Chuanqi Chen; Xinping Luo; Ming Zhang; Jing Li; Xizhuo Sun; Yu Liu; et al. (Science of The Total Environment, 2023)

Soft rot disease of Belamcanda chinensis caused by Dickeya fangzhongdai in China - Yawen Yang; Qiaohuan Chen; Jia Zhou; Jiawei Xu; Jinxin Li; Tingting Zhao; Ming Luo; Bisheng Huang; Yuhuan Miao; Dahui Liu (Physiological and Molecular Plant Pathology, 2023)

Overexpression of Sedum SpHMA2, SpHMA3 and SpNramp6 in Brassica napus increases multiple heavy metals accumulation for phytoextraction - Zi Yang; Hai-Tao Wu; Hao Yang; Wan-Di Chen; Jia-Lan Liu; Fan Yang; Li Tai; Bin-Bin Li; Bo Yuan; Wen-Ting Liu; Yan-Feng Zhang; Yan-Rong Luo; et al. (Journal of Hazardous Materials, 2023)

Comparative genomics revealed that Vibrio furnissii and Vibrio fluvialis have mutations in genes related to T6SS1 and T6SS2 - Jiakai Sun; Haochen Su; Wenhui Zhang; Xuesong Luo; Ruichao Li; Ming Liu (Archives of Microbiology, 2023)

Dynamic responses of carbon metabolism of sediment microbial communities to Ag nanoparticles: Effects of the single and repeated exposure scenarios - Weiyu Li; Dan Luo; Tanveer M. Adyel; Jun Wu; Lingzhan Miao; Ming Kong; Jun Hou (Science of The Total Environment, 2023)

Vertically transferred overpressures along faults in Mesozoic reservoirs in the central Junggar Basin, northwestern China: Implications for hydrocarbon accumulation and preservation - Likuan Zhang; Chao Li; Xiaorong Luo; Zengbao Zhang; Zhiping Zeng; Xincheng Ren; Yuhong Lei; Meng Zhang; Junyang Xie; Ming Cheng; Naigui Liu; Bingbing Xu (Marine and Petroleum Geology, 2023)

Multiple mechanisms collectively mediate tungsten homeostasis and resistance in Citrobacter sp. Lzp2 - Zipei Luo; Zhen Li; Jing Sun; Kaixiang Shi; Ming Lei; Boqing Tie; Huihui Du (Journal of Hazardous Materials, 2023)

The priming effects of plant leachates on dissolved organic matter degradation in water depend on leachate type and water stability - Yuan Cui; Jian-Qiao Meng; Yu-Han Chen; Fei-Fan Shao; Xuan-Zheng Chen; Yu Jin; Ming-Xiang Zhang; Guo Yun-Qian; Fang-Li Luo; Fei-Hai Yu (Environmental Research, 2023)

Suppressing staircase-like electrochemical profile induced by P O transition by solid-solution reaction with continuous structural evolution in layered Na-ion battery cathode - Kun Luo; Ming Chen; Mengdan Tian; Wenhui Li; Yang Jiang; Zhihao Yuan (Chemical Engineering Journal, 2023)

Inhibiting Cyclin B1-treated Pontine Infarction by Suppressing Proliferation of SPP1+ Microglia - Ming Luo; Zhihua Qiu; Xiangyue Tang; Li Wu; Shaojun Li; Juehua Zhu; Yongjun Jiang (Molecular Neurobiology, 2023)

The diversity of mycorrhiza‐associated fungi and trees shapes subtropical mountain forest ecosystem functioning - Ya‐Huang Luo; Liang‐Liang Ma; Sebastian Seibold; Marc W. Cadotte; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Wei Zheng; Jia‐Yun Zou; Zhi‐Fa Chen; De‐Tuan Liu; Guang‐Fu Zhu; et al. (Journal of Biogeography, 2023)
Aim Mycorrhiza play key roles for ecosystem structure and functioning in forests. However, how different mycorrhizal types influence mountain forest biodiversity–ecosystem functioning (BEF) relationships are largely unknown. We evaluate how the diversity of distinct mycorrhiza‐associated fungi and trees shapes forest carbon storage along elevational gradients. Location Gaoligong Mountains within Hengduan Mountains, Southwest China. Taxon Seed plants and mycorrhizal fungi. Methods We used the data from 31 subtropical forest plots along elevational gradients on two aspects (east and west) of the mountain. We quantified species richness of trees and symbiotic fungi and assigned both to their mycorrhizal type (arbuscular mycorrhiza [AM], ectomycorrhiza [EcM] and ericoid mycorrhiza [ErM]). We then examined the diversity effects of mycorrhiza‐associated fungi and trees on above‐ground carbon stored in trees and organic carbon stored in soils. Results Species richness was highest for AM trees (79.5%), followed by ErM trees (13.4%) and then EcM trees (7.1%). Species richness of AM‐associated trees and fungi decreased with increasing elevation, while ErM‐associated trees and fungi showed an opposite trend. EcM‐associated diversity followed a hump‐shaped relationship with elevation. Positive relationships between diversity and above‐ground carbon were detected in all three mycorrhizal associations, but despite low species number, canopy‐dominating EcM trees comprised 64.4% of the amount of above‐ground carbon. Furthermore, community‐weighted means of height exhibited positive correlations with forest above‐ground carbon, indicating that positive selection effects occur. Soil organic carbon was positively related to EcM‐associated fungi diversity, above‐ground carbon mass and soil nitrogen availability, with the latter having strongest direct effects. Main Conclusions The distributions of forest biodiversity and carbon storage can be modulated by distinct mycorrhizal fungi and trees. Moreover, future global changes (e.g. climate warming, intensifying nitrogen deposition) could alter the mycorrhizal‐mediated BEF relationships in mountain forests.

Transition of source/sink processes and fate of ammonium in groundwater along with redox gradients - Li-Li Han; Helin Wang; Lianghao Ge; Min Nina Xu; Jin-Ming Tang; Li Luo; Ping Li; Shuh-Ji Kao (Water Research, 2023)

Feeding the world using speed breeding technology - Ying Xu; Hongbing Luo; Hao Zhang; Wai-Shing Yung; Man-Wah Li; Hon-Ming Lam; Cheng Huang (Trends in Plant Science, 2023)

Quality assessment of royal jelly based on physicochemical properties and flavor profiles using HS-SPME-GC/MS combined with electronic nose and electronic tongue analyses - Lili Chen; Fangjian Ning; Li Zhao; Huihui Ming; Jinping Zhang; Wenjie Yu; Shengxiang Yi; Liping Luo (Food Chemistry, 2023)

Low-noise, low-power-consumption seafloor vector magnetometer - Xiaochen Li; Xianhu Luo; Ming Deng; Ning Qiu; Zhen Sun; Kai Chen (Journal of Oceanology and Limnology, 2023)

Changes in planting methods will change the potential distribution of rice in South China under climate warming - Shuo Li; Zhou Lu; Jie Zhao; Ming Luo; Fu Chen; Qingquan Chu (Agricultural and Forest Meteorology, 2023)

Sodium para-aminosalicylic acid ameliorates brain neuroinflammation and behavioral deficits in juvenile lead-exposed rats by modulating MAPK signaling pathway and alpha-synuclein - Zhao-cong Li; Yue-song Zhao; Jun-jie Lin; Lei-lei Wang; Han-xiao Song; Cui-liu Gan; Xiao-wei Zheng; Shi-yan Ou; Michael Aschner; Yue-ming Jiang; Jing-jing Luo; Yan Li (Toxicology Letters, 2023)

Investigation of the mechanisms and sensitivity of wellbore breathing effects during drilling in deepwater shallow formations - Honglin Huang; Jun Li; Reyu Gao; Geng Zhang; Hongwei Yang; Wang Chen; Ming Luo; Wentuo Li (Ocean Engineering, 2023)

Enhanced removal of typical odor compounds in constructed wetlands integrated with iron carbon and tidal flow - Yuwei She; Yan Zhao; Hongyan Ding; Qian Feng; Zhaoxia Xue; Jingyang Luo; Minfeng Lu; Qian Hu; Jiashun Cao; Yu Dai; Ming Li (Journal of Water Process Engineering, 2023)

MiR-130/SNAP-25 axis regulate presynaptic alteration in anterior cingulate cortex involved in lead induced attention deficits - Tao Wang; Rui-Li Guan; Yun-Feng Zou; Gang Zheng; Xue-Feng Shen; Zi-Peng Cao; Rui-Hua Yang; Ming-Chao Liu; Ke-Jun Du; Xue-Hang Li; Michael Aschner; Ming-Gao Zhao; et al. (Journal of Hazardous Materials, 2023)

Ongoings in the apple watercore: First evidence from proteomic and metabolomic analysis - Mingyi Yang; Qianwei Lin; Zisheng Luo; Zhaojun Ban; Xihong Li; Russel J. Reiter; Shuang Zhang; Lei Wang; Ze Liang; Ming Qi; Li Li (Food Chemistry, 2023)

Sesamol alleviates manganese-induced neuroinflammation and cognitive impairment via regulating the microglial cGAS-STING/NF-κB pathway - Jinxia Wu; Honggang Chen; Tingting Guo; Ming Li; Changhao Yang; Michael Aschner; Jingyuan Chen; Peng Su; Wenjing Luo (Environmental Pollution, 2023)

Highly efficient shrimp shell recovery by solid-state fermentation with Streptomyces sp. SCUT-3 - De-Lin Lu; Ming-Shu Zhang; Jun-Jin Deng; Wen-Jun Lu; Zhen-Dong Yang; Zhi-Wei Li; Yu-Chen Chen; Xiao-Chun Luo (Chemical Engineering Journal, 2023)

Corrigendum to “Dendrobium huoshanense stem polysaccharide ameliorates rheumatoid arthritis in mice via inhibition of inflammatory signaling pathways” [Carbohydr. Polym. 258 (2021) 117657] - Zhen-Zi Shang; Dan-Yang Qin; Qiang-Ming Li; Xue-Qiang Zha; Li-Hua Pan; Dai-Yin Peng; Jian-Ping Luo (Carbohydrate Polymers, 2023)

Highly efficient polyhydroxyalkanoate production from lignin using genetically engineered Halomonas sp. Y3 - Yuan-Qiu Li; Ming-Jun Wang; Chao-Bing Luo (Bioresource Technology, 2023)

Sodium Para-Aminosalicylic Acid Modulates Autophagy to Lessen Lead-Induced Neurodegeneration in Rat Cortex - Lei-lei Wang; Xiao-juan Zhu; Yuan-yuan Fang; Yan Li; Yue-song Zhao; Cui-liu Gan; Jing-jing Luo; Shi-yan Ou; Michael Aschner; Yue-ming Jiang (Neurotoxicity Research, 2023)

A Method for Reducing Ocean Wave-Induced Magnetic Noises in Shallow-Water MT Data Using a Complex Adaptive Filter - Yunju Wu; Ming Luo; Yuguo Li; Jiaqi Ge; Lindong Pan (Journal of Ocean University of China, 2023)

Retraction Note: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2023)

Black soldier fly larvae replace traditional iced trash fish diet to enhance the delicious flavor of Chinese mitten crab (Eriocheir sinensis) - Jian-Feng Qiu; Cheng Luo; Li-Hua Ren; Wei Li; Tai-Ming Dai; Guang Wang; Xiao-Ning Sun; Kou-Chang Chong Moua; Yang-Hu Sima; Shi-Qing Xu (Frontiers in Marine Science, 2023)
Chinese mitten crabs ( Eriocheir sinensis ) are traditionally fed iced trash fish, but the industry is facing problems such as low breeding safety. Black soldier fly ( Hermetia illucens ) is an alternative protein source in animal diets, including diets for aquatic animals, due to its high nutritional value. However, studies on the effects of black soldier fly on the flavor characteristics of aquatic animals are still limited. In the present study, we investigated the effects of the complete replacement of iced trash fish with black soldier fly larvae during the fattening period of Chinese mitten crab on the flavor molecule contents and evaluation indices. The levels of free amino acids and nucleotides were determined in three edible parts (muscle, hepatopancreas, and gonads) of crab. Taste activity value analysis showed that glutamic acid, glycine, alanine, and arginine were the main amino acids contributing to the umami taste and sweetness, while histidine, lysine, valine, and methionine were the main amino acids contributing to the bitterness. Equivalent umami concentration (EUC) analysis showed that female gonads had the strongest umami taste, followed by the hepatopancreas and muscle. Sweetness value (SWT) analysis showed that the sweetness of muscle was the highest. Feeding black soldier fly larvae affected the flavor characteristics of crabs with tissue and sex differences. The EUC of the female gonads and SWT of the muscle were significantly increased. Meanwhile, the EUC of the hepatopancreas and SWT of the gonads were slightly decreased in male crabs. Our results indicate that the complete replacement of iced trash fish with black soldier fly larvae during the fattening period significantly enhances the flavor characteristics of crabs based on the contents of flavoring amino acids and nucleotides. It is important for sustainable aquaculture to replace animal protein with alternative protein sources such as black soldier fly larvae.

H3K4me3 as a target of di(2-ethylhexyl) phthalate (DEHP) impairing primordial follicle assembly - Ming-Hao Li; Jun-Jie Wang; Yan-Qin Feng; Xuan Liu; Zi-Hui Yan; Xiao-Jun Zhang; Ya-Xin Wen; Hao-Wei Luo; Lan Li; Massimo De Felici; Ai-Hong Zhao; Wei Shen (Chemosphere, 2023)

Modified flood potential index (MFPI) for flood monitoring in terrestrial water storage depletion basin using GRACE estimates - Wei Jiang; Xuan Ji; Yungang Li; Xian Luo; Luyi Yang; Wenting Ming; Chang Liu; Siyi Yan; Chuanjian Yang; Cezong Sun (Journal of Hydrology, 2023)

Early Paleozoic collision-related structures in the Tarim Craton, NW China: Implications for the Proto-Tethys evolution - Yue-Jun Li; Yong-Jin Gao; Hui Zhou; Guang-Ya Zhang; Lei Wen; Yan Zhao; Cheng Li; Duo-Ming Zheng; Ya-Lei Liu; Hong-Hui Li; Cai-Ming Luo; Tong-Fei Huang; et al. (Journal of Asian Earth Sciences, 2023)

Molting-related proteases in the brown planthopper, Nilaparvata lugens - Yu-Cheng Xie; Hou-Hong Zhang; Han-Jing Li; Xiao-Ya Zhang; Xu-Mei Luo; Ming-Xing Jiang; Chuan-Xi Zhang (Insect Biochemistry and Molecular Biology, 2023)

Fluoro-cotton assisted non-targeted screening of organic fluorine compounds from rice (Oryza sativa L.) grown in perfluoroalkyl substance polluted soil - Hua-Ming Xiao; Shuai Zhao; Dilshad Hussain; Jian-Li Chen; Dan Luo; Fang Wei; Xian Wang (Environmental Research, 2023)

Cleaner 2,3-butanediol production from unpretreated lignocellulosic biomass by a newly isolated Klebsiella pneumoniae PX14 - Yuan-Qiu Li; Ming-Jun Wang; Xiao-Feng Gan; Chao-Bing Luo (Chemical Engineering Journal, 2023)

Genesis of hydrous-oxidized parental magmas for porphyry Cu (Mo, Au) deposits in a postcollisional setting: examples from the Sanjiang region, SW China - Lei-Luo Xu; Jing-Jing Zhu; Ming-Liang Huang; Li-Chuan Pan; Ruizhong Hu; Xian-Wu Bi (Mineralium Deposita, 2023)

Therapeutic Effects of Human Pluripotent Stem Cell-Derived Mesenchymal Stem Cells on a Murine Model of Acute Type-2-Dominated Airway Inflammation - Si-Yuan Ma; Ning Zhao; Lele Cui; Ying Li; Hang Zhang; Jing Wang; Jie Pang; Ming Wang; Chengshuo Wang; Sun Ying; Zi-Bing Jin; Luo Zhang (Stem Cell Reviews and Reports, 2022)

Uncovering expression and functional analysis of newly discovered high-affinity K+ transporter family members from sugarcane - Hai-bin Luo; Cheng-mei Huang; Yuan-wen Wei; Hui-ming Zhu; Hui-qing Cao; Sheng-li Jiang; Zhi-nian Deng; Kai-chao Wu; Lin Xu (Journal of Plant Biochemistry and Biotechnology, 2022)

Comparison of infections with respiratory syncytial virus between children and adults: a multicenter surveillance from 2015 to 2019 in Beijing, China - Ming Luo; Cheng Gong; Yan Zhang; Xue Wang; Yang Liu; Qing Luo; Maozhong Li; Aihua Li; Yiting Wang; Mei Dong; Wenbo Xu; Fang Huang (European Journal of Clinical Microbiology & Infectious Diseases, 2022)

Removal of Cd from contaminated farmland soil by washing with residues of traditional Chinese herbal medicine extracts - Yi Wang; Yuan Li; Shuai Yang; Qi-hao Wang; Shao-cheng Si; Han-yi Mei; Guo-ming Liu; Xiang-liang Pan; Yong-ming Luo (Environmental Science and Pollution Research, 2022)

Molecular characterization of a novel victorivirus isolated from Botryosphaeria dothidea, the causal agent of longan leaf spot disease - Jiali Li; Lifeng Zhai; Meixin Zhang; Gangjun Luo; Yongqi Wen; Tingting Cao; Huan Xia; Jiayu Zhang; Ming Liu (Archives of Virology, 2022)

Quantitative microbial risk assessment with nasal/oral breathing pattern for S. aureus bioaerosol emission from aeration tanks and residual sludge storage yard in a wastewater treatment plant - Cheng Yan; Xiao-yan Zhao; Xi Luo; Dong-zi An; Hao Zhu; Ming Li; Xiao-jun Ai; Wajid Ali (Environmental Science and Pollution Research, 2022)

Sexual size dimorphism in golden pompano (Trachinotus blochii): Potential roles of changes in energy allocation and differences in muscle metabolism - Jun Long Sun; Fei Biao Song; Lei Wang; Wei Wei Zhang; You Ming Chen; Li Zhou; Jian Fang Gui; Jian Luo (Frontiers in Marine Science, 2022)
Golden pompano ( Trachinotus blochii ) is becoming increasingly popular and produces high yields, but the growth differences between males and females are a concern. In this study, the differences between the growth of males and females were compared, and the transcriptome analysis of muscle tissues was performed. A significant difference between the growth of males and females was observed; females were found to be 17% larger than males after reaching 7 months of age. Gonadal histological analysis revealed that the ovaries were arrested in 7- to 9-month-old golden pompano, whereas the testes continued to develop. The AMPK and adipocytokine signaling pathways were also found to be involved in the regulation of muscle growth and metabolism. After reaching 7 months of age, the expression levels of glut1 , glut4 , ldh , gys, acsl and cpt2 in the muscle of females were lower than those in males, but the hk gene, which is involved in glycolysis, was found to remain highly expressed in females. Additionally, in females, the synthesis of arginine and ornithine and the production of carnosine were found to be inhibited, but the breakdown of glutamine was found to be enhanced and OXPHOS ability was found to be stronger in females after reaching 7 months of age. These results support a certain negative correlation between gonadal development and muscle metabolism depending on differences in energy distribution. Clearly, the faster growth in females after reaching 7 months of age was found to be associated with the more active metabolism of glucose, and amino acids, as well as stronger oxidative phosphorylation levels.

3-D Marine CSEM Modeling in General Anisotropic Media by Using an Adaptive Finite Element Approach Based on the Vector-Scalar Potential - Yixin Ye; Fenyong Jiang; Zhibing Feng; Ming Luo; Gang Li; Yuguo Li (Journal of Ocean University of China, 2022)

Adsorption properties and mechanism research of phosphorus with different molecular structures from aqueous solutions by La-modified biochar - Ming-yao Yuan; Shang-kai Qiu; Meng-meng Li; Yuan Li; Ji-Xiu Wang; Yuan Luo; Ke-qiang Zhang; Feng Wang (Environmental Science and Pollution Research, 2022)

Novel CRISPR/Cas9-mediated knockout of LIG4 increases efficiency of site-specific integration in Chinese hamster ovary cell line - Chuanjie Wang; Zhaolin Sun; Ming Wang; Zhiyang Jiang; Mengmeng Zhang; Hongxu Cao; Longlong Luo; Chunxia Qiao; He Xiao; Guojiang Chen; Xinying Li; Jinqing Liu; et al. (Biotechnology Letters, 2022)

Multitrophic diversity and biotic associations influence subalpine forest ecosystem multifunctionality - Ya‐Huang Luo; Marc W. Cadotte; Jie Liu; Kevin S. Burgess; Shao‐Lin Tan; Lin‐Jiang Ye; Jia‐Yun Zou; Zhong‐Zheng Chen; Xue‐Long Jiang; Juan Li; Kun Xu; De‐Zhu Li; et al. (Ecology, 2022)
Biodiversity across multiple trophic levels is required to maintain multiple ecosystem functions. Yet it remains unclear how multitrophic diversity and species interactions regulate ecosystem multifunctionality. Here, combining data from 9 different trophic groups (including trees, shrubs, herbs, leaf mites, small mammals, bacteria, pathogenic fungi, saprophytic fungi, and symbiotic fungi) and 13 ecosystem functions related to supporting, provisioning, and regulating services, we used a multitrophic perspective to evaluate the effects of elevation, diversity, and network complexity on scale‐dependent subalpine forest multifunctionality. Our results demonstrated that elevation and soil pH significantly modified species composition and richness across multitrophic groups and influenced multiple functions simultaneously. We present evidence that species richness across multiple trophic groups had stronger effects on multifunctionality than species richness at any single trophic level. Moreover, biotic associations, indicating the complexity of trophic networks, were positively associated with multifunctionality. The relative effects of diversity on multifunctionality increased at the scale of the larger community compared to a scale accounting for neighboring interactions. Our results highlight the paramount importance of scale‐ and context‐dependent multitrophic diversity and interactions for a better understanding of mountain ecosystem multifunctionality in a changing world.

Improving protected area effectiveness through consideration of different human‐pressure baselines - Chun‐Ting Feng; Ming Cao; Fang‐Zheng Liu; Yue Zhou; Jin‐Hong Du; Li‐Bo Zhang; Wen‐Jie Huang; Jian‐Wu Luo; Jun‐Sheng Li; Wei Wang (Conservation Biology, 2022)
Previous assessments of the effectiveness of protected areas (PAs) focused primarily on changes in human pressure over time and did not consider the different human‐pressure baselines of PAs, thereby potentially over‐ or underestimating PA effectiveness. We developed a framework that considers both human‐pressure baseline and change in human pressure over time and assessed the effectiveness of 338 PAs in China from 2010 to 2020. The initial state of human pressure on PAs was taken as the baseline, and changes in human pressure index (HPI) were further analyzed under different baselines. We used the random forest models to identify the management measures that most improved effectiveness in resisting human pressure for the PAs with different baselines. Finally, the relationships between the changes in the HPI and the changes in natural ecosystems in PAs were analyzed with different baselines. Of PAs with low HPI baselines, medium HPI baselines, and high HPI baselines, 76.92% ( n =150), 11.11% ( n =12), and 22.86% ( n =8) , respectively, showed positive effects in resisting human pressure. Overall, ignoring human‐pressure baselines somewhat underestimated the positive effects of PAs, especially for those with low initial human pressure. For PAs with different initial human pressures, different management measures should be taken to improve effectiveness and reduce threats to natural ecosystems. We believe our framework is useful for assessing the effectiveness of PAs globally, and we recommend it be included in the Convention on Biological Diversity Post‐2020 Strategy.

Increases in temperature response to CO2 emissions in biochar-amended vegetable field soil - Rong Huang; Zifang Wang; Yi Xiao; Luo Yu; Xuesong Gao; Changquan Wang; Bing Li; Qi Tao; Qiang Xu; Ming Gao (Environmental Science and Pollution Research, 2022)

Effects of secondary succession on soil fungal and bacterial compositions and diversities in a karst area - Genzhu Wang; Yuguo Liu; Ming Cui; Ziyuan Zhou; Qian Zhang; Yajin Li; Wenxiu Ha; Danbo Pang; Jiufu Luo; Jinxing Zhou (Plant and Soil, 2022)

A Deep Mesencephalic Nucleus Circuit Regulates Licking Behavior - Di Zheng; Jia-Yu Fu; Meng-Yu Tang; Xiao-Dan Yu; Yi Zhu; Chen-Jie Shen; Chun-Yue Li; Shi-Ze Xie; Shan Lin; Minmin Luo; Xiao-Ming Li (Neuroscience Bulletin, 2022)

Chromosomes polymorphisms of Sichuan wheat cultivars displayed by ND-FISH landmarks - Zhenglei Hu; Jiangtao Luo; Linrong Wan; Jie Luo; Yazhou Li; Shulan Fu; Dengcai Liu; Ming Hao; Zongxiang Tang (Cereal Research Communications, 2022)

Corrigendum: Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2022)

Genetic Diversity and Structure of Tropical Porites lutea Populations Highlight Their High Adaptive Potential to Environmental Changes in the South China Sea - Yanqiu Luo; Wen Huang; Kefu Yu; Ming Li; Biao Chen; Xueyong Huang; Zhenjun Qin (Frontiers in Marine Science, 2022)
Global climate change and anthropogenic disturbance have significantly degraded biodiversity in coral reef ecosystems. The genetic potential and adaptability of corals are key factors used to predict the fate of global coral reefs under climate change. In this study, we used eight microsatellite loci to study the patterns of reproduction, genetic diversity, and genetic structure of 302 Porites lutea samples across 13° latitudes in the South China Sea (8.8644°N–22.6117°N). The results indicated that P. lutea reproduces largely via sexual reproduction on scales of 5 m and greater and has abundant gene diversity. Additionally, the tropical populations harbored high genetic diversity (based on alleles, effective number of alleles, gene diversity, and heterozygosity). In contrast, genetic diversity was lower in subtropical coral populations. Genetic variation values and pairwise F ST revealed that tropical and subtropical populations had significantly different genetic structures. Finally, the Mantel tests showed that the genetic differentiation and genetic variation of P. lutea were strongly correlated with sea surface temperature and slightly correlated with geographical distance. These results indicated that tropical P. lutea populations have high genetic potential and adaptability because of their sexual reproduction and genetic diversity, giving them a greater capacity to cope with climate change. Subtropical coral populations showed lower genetic diversity and, thus, relatively poor genetic resilience in response to low average sea surface temperature and human activities. Our study provides a theoretical basis for the protection and restoration of coral reefs.

A feasible vibration measurement and active control method of reinforced concrete lightweight pier railway bridges for heavy-haul monorail trains - Ling-kun Chen; Li-zhong Jiang; Rui Li; Qiao Li; Ming Zhang; Nan Zhang; Jin-zhang Luo; Liang Ling; Sheng-yang Zhu (European Journal of Environmental and Civil Engineering, 2022)

Near-epicenter weather conditions several hours before strong earthquakes (Ms ≥ 6) - Tao Chen; Lei Li; Xiao-Xin Zhang; Qi-Ming Ma; Wen Li; Shuo Ti; Han Wu; Ren-Kang Li; Jing Luo; Jian-Feng Su (Natural Hazards, 2022)

Assessment of probiotic adhesion and inhibitory effect on Escherichia coli and Salmonella adhesion - Ya Wang; Dan Jia; Jia-hui Wang; He-hai Li; Jun-long Liu; Ai-hong Liu; Jin-ming Wang; Gui-quan Guan; Jian-xun Luo; Hong Yin; You-quan Li (Archives of Microbiology, 2021)

Geo-structures and deformation-failure characteristics of rockslide areas near the Baige landslide scar in the Jinsha River tectonic suture zone - Shi-lin Zhang; Yue-ping Yin; Xie-wen Hu; Wen-pei Wang; Zong-liang Li; Xin-ming Wu; Gang Luo; Sai-nan Zhu (Landslides, 2021)

Sandaracinobacteroides hominis gen. nov., sp. nov., isolated from human skin - Ping-Hua Qu; Hai-Min Luo; Jun-Hui Feng; Song Li; Cha Chen; Lei Dong; Yu-Zhen Ming; Wen-Jun Li; Ying Lin (Archives of Microbiology, 2021)

Dynamic mechanical behavior and damage constitutive model of shales with different bedding under compressive impact loading - Xueru Fan; Ning Luo; Yishuo Yuan; Hanliang Liang; Cheng Zhai; Zhe Qu; Ming Li (Arabian Journal of Geosciences, 2021)

Quantitative Proteomics Analysis of Sugarcane Ratoon Crop Chlorosis - Ye-Geng Fan; Rong-Fa Chen; Li-Hang Qiu; Zhong-Feng Zhou; Hui-Wen Zhou; Ji-Guang Wei; Xiu-Peng Song; Ting Luo; Prakash Lakshmanan; Xing Huang; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2021)

Different posterior hippocampus and default mode network modulation in young APOE ε4 carriers: a functional connectome-informed phenotype longitudinal study - Li Juan Zheng; Li Lin; U. Joseph Schoepf; Akos Varga-Szemes; Rock H. Savage; Han Zhang; Yun Fei Wang; Xin Yuan Zhang; Song Luo; Ya Liu; Gui Fen Yang; Guang Ming Lu; et al. (Molecular Neurobiology, 2021)

Endocrine Dysfunction Following Stroke - Fei Wang; Ming-ying Luo; Lei Zhou; Li Yang; Giuseppe Lanzino; Heng-Jui Chang; George C Wellman (Journal of Neuroimmune Pharmacology, 2021)

Pigmentibacter ruber gen. nov., sp. nov., a novel bacterium of the family Silvanigrellaceae isolated from human blood - Na Peng; Wen Xu; Hai-Min Luo; Peng-Wen Ouyang; Bin Jiang; Zhi-Hua Zhang; You-De Cao; Li-Ming Tan; Ping-Hua Qu; Liang-Yi Xie (Antonie van Leeuwenhoek, 2021)

Amygdala-based Functional Network Reveals Dissociated Neural Correlates of Consensual and Idiosyncratic Emotional Movie Experiences - Lin Cui; Bingbing Guo; Dan Zhao; Jiaxin Li; Yu Luo; Ming Meng (Neuroscience Bulletin, 2021)

Subcellular Localization of the D27 Protein in Sugarcane (Saccharum spp. Hybrids) Using an Optimized Protoplast Isolation, Purification, and Transient Gene Expression Protocol - Zhuan-di Wu; Xin Hu; Feng-gang Zan; Yong-bao Pan; David M. Burner; Zheng-ying Luo; Jia-yong Liu; Li-ping Zhao; Li Yao; Yong Zhao; Xin-long Liu; Hong-ming Xia; et al. (Sugar Tech, 2021)

Photocatalytic optical fibers for degradation of organic pollutants in wastewater: a review - Yongwu Wu; Lanlan Zhong; Jilin Yuan; Wenhao Xiang; Xin Xin; Huimin Liu; Hongyang Luo; Linyang Li; Ming Chen; Dengjie Zhong; Xinghong Zhang; Nianbing Zhong; et al. (Environmental Chemistry Letters, 2021)

Noroleanane-type triterpenoids from Dolichos trilobus L. and their anti-α-glucosidase activities - Ming Luo; Yan-Hong Li; Ya Lu; Yan Yuan; Rong-Sheng Ruan; Yong-Ming Chuan; Kai Tian; Xiang-Zhong Huang (Natural Product Research, 2021)

Ferroptosis occurs in phase of reperfusion but not ischemia in rat heart following ischemia or ischemia/reperfusion - Li-Jing Tang; Xiu-Ju Luo; Hua Tu; Heng Chen; Xiao-Ming Xiong; Nian-Sheng Li; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Astrocyte-Derived Lactate Modulates the Passive Coping Response to Behavioral Challenge in Male Mice - Ya-Nan Yin; Jian Hu; Yi-Li Wei; Ze-Lin Li; Zhou-Cai Luo; Rui-Qi Wang; Ke-Xin Yang; Shu-Ji Li; Xiao-Wen Li; Jian-Ming Yang; Tian-Ming Gao (Neuroscience Bulletin, 2021)

A Fluorogenic and Chromogenic Probe Distinguishes Fluoride Anions and Thiols: Implications for Discrimination of Fluoride-Containing G Series and Sulfur-Containing V Series Nerve Agents - Wei-hui Wu; Xin Wang; Liang Zong; Dan Li; Yan-hua Xiao; Shao-hui Sui; Jian Li; Meng Liu; Gao-yun Chen; Teng Luo; Min Liu; Xin-ming Wang; et al. (Journal of Fluorescence, 2021)

KASP markers to detect sub-chromosomal arm translocations between 6VS of Haynaldia villosa and 6AS of wheat - Shujie Zhang; Chaolan Fan; Jiangtao Luo; Lei Huang; Die Xie; Yazhou Li; Zhuo Chen; Bo Jiang; Shunzong Ning; Zhongwei Yuan; Lin Huang; Lianquan Zhang; et al. (Euphytica, 2021)

Anxiolytic Effects of 8-O-Acetyl Shanzhiside Methylester on Acute and Chronic Anxiety via Inflammatory Response Inhibition and Excitatory/Inhibitory Transmission Imbalance - Ting Sun; Li Luo; Qin-Qin Tian; Wen-Ju Wang; Qing-Qing Liu; Le Yang; Kun Zhang; Wei Zhang; Ming-Gao Zhao; Qi Yang (Neurotoxicity Research, 2020)
Anxiety leads to a global decline in quality of life and increase in social burden. However, treatments are limited, because the molecular mechanisms underlying complex emotional disorders are poorly understood. We explored the anxiolytic effects of 8-O-acetyl shanzhiside methylester (8-OaS), an active component in Lamiophlomis rotata ( L . rotata ; Benth.) or Kudo, a traditional herb that has been shown to be effective in the clinical treatment of chronic pain syndromes in China. Two mouse anxiety models were used: forced swimming stress (FSS)–induced anxiety and complete Freund’s adjuvant (CFA)–induced chronic inflammatory pain. All animal behaviors were analyzed on the elevated plus maze and in the open-field test. 8-OaS significantly ameliorated anxiety-like behaviors in both anxiety models and inhibited the translation enhancement of GluN2A, GluN2B, and PSD95. Moreover, a reduction in GABA receptors disrupted the excitatory/inhibitory (E/I) balance in the basolateral amygdala (BLA), indicated by increased excitatory and decreased inhibitory presynaptic release. 8-OaS also blocked microglia activation and reduced the phosphorylation of p38, c-Jun N-terminal kinase (JNK), NF-κB p65, and tumor necrosis factor alpha (TNF-α) in the BLA of anxiety mice. 8-OaS exhibits obvious anxiolytic effects by regulating the excitatory/inhibitory (E/I) synaptic transmission and attenuating inflammatory responses in the BLA.

Role of major histocompatibility complex II antigen‐presentation pathway genes in orange‐spotted grouper infected with Cryptocaryon irritans - Jun‐Jin Deng; Shun Xu; Yan‐Wei Li; Dong‐Dong Xu; Ze‐Quan Mo; Jia‐Zhou Li; Xue‐Ming Dan; Xiao‐Chun Luo (Journal of Fish Diseases, 2020)
Cryptocaryon irritans , a pathogen model for fish mucosal immunity, causes skin mucosal and systematic humoral immune response. Where and how MHC II antigen presentation occurs in fish infected with C . irritans remain unknown. In this study, the full‐length cDNA of the grouper cysteine protease CTSS was cloned. The expression distributions of six genes (CTSB, CTSL, CTSS, GILT, MHC IIA and MHC IIB) involved in MHC II antigen presentation pathway were tested. These genes were highly expressed in systematic immune tissues and skin and gill mucosal‐associated immune tissues. All six genes were upregulated in skin at most time points. Five genes expected CTSS was upregulated in spleen at most time points. CTSB, CTSL and MHC IIA were upregulated in the gill and head kidney at some time points. These results indicate that the presentation of MHC II antigen intensively occurred in local infected skin and gill. Spleen, not head kidney, had the most extensive systematic antigen presentation. In skin, six genes most likely peaked at day 2, earlier than in spleen (5–7 days), marking an earlier skin antibody peak than any recorded in serum previously. This significant and earlier mucosal antigen presentation indicates that specific immune response occurs in local mucosal tissues.

Chronic minocycline treatment exerts antidepressant effect, inhibits neuroinflammation, and modulates gut microbiota in mice - Qi Yang; Li Luo; Ting Sun; Le Yang; Li-Fei Cheng; Yan Wang; Qing-Qing Liu; An Liu; Hai-Yan Liu; Ming-Gao Zhao; Sheng-Xi Wu; Bin Feng (Psychopharmacology, 2020)

Effects of arbuscular mycorrhizal fungi on redox homeostasis of rice under Cd stress - Hui Li; Xun Wen Chen; Li Wu; Na Luo; Wei Xiong Huang; Ce Hui Mo; Yan Wen Li; Lei Xiang; Hai Ming Zhao; Quan Ying Cai; Ming Hung Wong (Plant and Soil, 2020)

Structural features of an acidic polysaccharide with the potential of promoting osteoblast differentiation from Lycium ruthenicum Murr. - Shu-Qi Wang; Bing Liu; Su Liu; Song-Zi Xie; Li-Hua Pan; Xue-Qiang Zha; Qiang-Ming Li; Jian-Ping Luo (Natural Product Research, 2020)

A robust segmentation framework for closely packed buildings from airborne LiDAR point clouds - Xinsheng Wang; Ting On Chan; Kai Liu; Jun Pan; Ming Luo; Wenkai Li; Chunzhu Wei (International Journal of Remote Sensing, 2020)

The trichome-specific acetolactate synthase NtALS1 gene, is involved in acylsugar biosynthesis in tobacco (Nicotiana tabacum L.) - Ai-Xia Chang; Biao Chen; Ai-Guo Yang; Ri-Sheng Hu; Quan-Fu Feng; Ming Chen; Xiao-Ning Yang; Cheng-Gang Luo; Yang-Yang Li; Yuan-Ying Wang (Planta, 2020)

MicroRNA-153-3p enhances the sensitivity of chronic myeloid leukemia cells to imatinib by inhibiting B-cell lymphoma-2-mediated autophagy - Yu-Ling Li; Jia-Ming Tang; Xiao-Yun Chen; Bing Luo; Guo-Hua Liang; Qian Qu; Zi-Yuan Lu (Human Cell, 2020)

Recommended turbulent energy dissipation rate for biomass and lipid production of Scenedesmus obliquus in an aerated photosynthetic culture system - Mei An; Songqi Yang; Haiming Wu; Guanghong Luo; Ming Li (Environmental Science and Pollution Research, 2020)

Physiological and proteomic responses of mangrove plant Avicennia marina seedlings to simulated periodical inundation - Huan Li; Zan Li; Zhi-Jun Shen; Mei-Rong Luo; Yi-Ling Liu; Ming-Yue Wei; Wen-Hua Wang; Ying-Ying Qin; Chang-Hao Gao; Ke-Ke Li; Qian-Su Ding; Shan Zhang; et al. (Plant and Soil, 2020)

AAV/BBB-Mediated Gene Transfer of CHIP Attenuates Brain Injury Following Experimental Intracerebral Hemorrhage - Shuo Zhang; Zheng-wei Hu; Hai-yang Luo; Cheng-yuan Mao; Mi-bo Tang; Yu-sheng Li; Bo Song; Yao-he Wang; Zhong-xian Zhang; Qi-meng Zhang; Li-yuan Fan; Yao Zhang; et al. (Translational Stroke Research, 2020)

Anti-inflammatory bibenzyls from the stems of Dendrobium huoshanense via bioassay guided isolation - Qiang-Ming Li; Hui Jiang; Xue-Qiang Zha; De-Ling Wu; Li-Hua Pan; Jun Duan; Jian Liu; Jian-Ping Luo (Natural Product Research, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Correction to: Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Recombination between homoeologous chromosomes induced in durum wheat by the Aegilops speltoides Su1-Ph1 suppressor - Hao Li; Le Wang; Ming-Cheng Luo; Fang Nie; Yun Zhou; Patrick E. McGuire; Assaf Distelfeld; Xiongtao Dai; Chun-Peng Song; Jan Dvorak (Theoretical and Applied Genetics, 2019)

Effects of Exogenous GA3 and DPC Treatments on Levels of Endogenous Hormone and Expression of Key Gibberellin Biosynthesis Pathway Genes During Stem Elongation in Sugarcane - Li-Hang Qiu; Rong-Fa Chen; Han-Min Luo; Ye-Geng Fan; Xing Huang; Jun-Xian Liu; Fa-Qian Xiong; Hui-Wen Zhou; Chong-Kun Gan; Jian-Ming Wu; Yang-Rui Li (Sugar Tech, 2019)

NRG1–ErbB4 signaling promotes functional recovery in a murine model of traumatic brain injury via regulation of GABA release - Weike Deng; Fei Luo; Bao-ming Li; Lin Mei (Experimental Brain Research, 2019)

Identification and Phylogenetic Analysis of Xanthomonas albilineans (Ashby) Dowson Based on Multiple Gene Sequences in Yunnan Province, China - Rong-Yue Zhang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Wen-Feng Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin; Ying-Kun Huang (Sugar Tech, 2019)

Molecular Identification of Sugarcane White Leaf in Puer, Yunnan Province, China - Rong-Yue Zhang; Wen-Feng Li; Ying-Kun Huang; Xiao-Yan Wang; Hong-Li Shan; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Sugar Tech, 2019)

Developing genetically segregating populations for localization of novel sugarcane brown rust resistance genes - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Hong-Li Shan; Rong-Yue Zhang; Jie Li; Xiao-Yan Cang; Zhi-Ming Luo; Jiong Yin (Euphytica, 2019)

Forest community assembly is driven by different strata‐dependent mechanisms along an elevational gradient - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Journal of Biogeography, 2019)
Aim The mechanisms driving forest community assembly along elevational gradients remain elusive. The distinct strata in heterogeneous forest are subject to differing assembly mechanisms. This study aims to evaluate how different ecological mechanisms driving forest community assembly across strata and spatial scales, and to identify how these assemblages respond to different abiotic or biotic variables along an elevational gradient. Location Yulong Mountain within Hengduan Mountains, Southwest China. Taxon Seed plants. Methods We sampled plant species along a 1,200 m elevational gradient across forest strata (trees, shrubs and herbs) at different spatial scales (neighbourhood and community). We integrated phylogenetic and functional diversity to disentangle the roles of ecological mechanisms in structuring community assembly. We also determined the relative effects of climatic, soil and biotic variables and their interactions on these community assemblages. Results The phylogenetic and functional diversity of trees were lower at the extremes of the elevational gradient, where they were constrained by water availability or temperature. While communities with higher species diversity exhibited an overdispersed structure at mid‐elevations. For shrubs, overdispersion was exhibited at high elevations despite low species richness, which could be consistent with facilitative interactions or competition exclusion. However, most communities of herbs appear to have a markedly random structure, despite some incongruence between phylogenetic divergence and functional convergence, as well as influences from overstorey trees and local light conditions. The relative effects of abiotic variables on community structure were larger at the community scale than at the neighbourhood scale. Main conclusions Our study emphasises the importance of considering phylogenies and traits in understanding the strata‐ and scale‐dependent mechanisms of forest community assembly. Collectively, results indicate that contrasting assembly mechanisms interact across different strata along elevational gradients to shape diverse forest communities.

Petrogenesis of early Late Cretaceous Asa-intrusive rocks in central Tibet, western China: post-collisional partial melting of thickened lower crust - An-Bo Luo; Ming Wang; Cai Li; Chao-Ming Xie; Jian-jun Fan; Tian-Yu Zhang; Jin-Heng Liu; Wei Wang (International Journal of Earth Sciences, 2019)

Greater than the sum of the parts: how the species composition in different forest strata influence ecosystem function - Ya‐Huang Luo; Marc W. Cadotte; Kevin S. Burgess; Jie Liu; Shao‐Lin Tan; Jia‐Yun Zou; Kun Xu; De‐Zhu Li; Lian‐Ming Gao (Ecology Letters, 2019)
The mechanisms underpinning forest biodiversity‐ecosystem function relationships remain unresolved. Yet, in heterogeneous forests, ecosystem function of different strata could be associated with traits or evolutionary relationships differently. Here, we integrate phylogenies and traits to evaluate the effects of elevational diversity on above‐ground biomass across forest strata and spatial scales. Community‐weighted means of height and leaf phosphorous concentration and functional diversity in specific leaf area exhibited positive correlations with tree biomass, suggesting that both positive selection effects and complementarity occur. However, high shrub biomass is associated with greater dissimilarity in seed mass and multidimensional trait space, while species richness or phylogenetic diversity is the most important predictor for herbaceous biomass, indicating that species complementarity is especially important for understory function. The strength of diversity‐biomass relationships increases at larger spatial scales. We conclude that strata‐ and scale‐ dependent assessments of community structure and function are needed to fully understand how biodiversity influences ecosystem function.

Population structure and genetic diversity of Vibrio parahaemolyticus from a coastal area of China based on a multi-locus sequence typing (MLST) scheme - Yu Li; Hong-Qiu Yin; Jun Xia; Hong Luo; Ming-Yi Wang (Antonie van Leeuwenhoek, 2019)

RETRACTED ARTICLE: Cancer-derived exosomal miR-221-3p promotes angiogenesis by targeting THBS2 in cervical squamous cell carcinoma - Xiang-Guang Wu; Chen-Fei Zhou; Yan-Mei Zhang; Rui-Ming Yan; Wen-Fei Wei; Xiao-Jing Chen; Hong-Yan Yi; Luo-Jiao Liang; Liang-sheng Fan; Li Liang; Sha Wu; Wei Wang (Angiogenesis, 2019)

Quadruplex PCR detection of three quarantine Phytophthora pathogens of berries - Fang Liao; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Doudou Zhang; Jia-Feng Luo; Guan-Rong Li (European Journal of Plant Pathology, 2019)

Knowledge and behavior regarding pesticide use: a survey among caregivers of children aged 1–6 years from rural China - Yuanying Deng; Hongmei Dai; Ming Zeng; Lan Guan; Xiangwen Luo; Chen Zhang; Jing Tian; Jie Zhang; Ying Li; Qiong Xi; Mengwen Zhao; Mei Jiang; et al. (Environmental Science and Pollution Research, 2019)

Typical characteristics of large-scale landslides in the transition belt between the Qinghai-Tibet Plateau and the Loess Plateau - Bo Zhao; Yunsheng Wang; Ming Chen; Yonghong Luo; Ruifeng Liang; Jia Li (Arabian Journal of Geosciences, 2019)

Genetic mapping of a major QTL promoting homoeologous chromosome pairing in a wheat landrace - Chaolan Fan; Jiangtao Luo; Shujie Zhang; Meng Liu; Qingcheng Li; Yazhou Li; Lei Huang; Xuejiao Chen; Shunzong Ning; Zhongwei Yuan; Lianquan Zhang; Jirui Wang; et al. (Theoretical and Applied Genetics, 2019)

Role of Maize Root Exudates in Promotion of Colonization of Bacillus velezensis Strain S3-1 in Rhizosphere Soil and Root Tissue - Yeqing Jin; Hangfei Zhu; Si Luo; Wenwu Yang; Li Zhang; Shanshan Li; Qing Jin; Qin Cao; Shurong Sun; Ming Xiao (Current Microbiology, 2019)

Identification and Evaluation of Resistance to Sugarcane Streak Mosaic Virus (SCSMV) and Sorghum Mosaic Virus (SrMV) in Excellent Sugarcane Innovation Germplasms in China - Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Xin Lu; Rong-Yue Zhang; Xiao-Yan Wang; Jiong Yin; Zhi-Ming Luo; Ying-Kun Huang (Sugar Tech, 2019)

Field Resistance of Different Sugarcane Varieties to Sugarcane Thrips (Fulmekiola serratus) in China - Zhi-Ming Luo; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Wen-Feng Li; Hong-Li Shan; Xiao-Yan Cang; Jie Li; Jiong Yin (Sugar Tech, 2019)

First molecular evidence of Babesia occultans and Theileria separata infection in ticks and sheep in China - Ming Sun; Jinming Wang; Zhijie Liu; Guanquan Guan; Youquan Li; Junlong Liu; Jianlin Xu; Hong Yin; Jianxun Luo (Experimental and Applied Acarology, 2019)

MOTS-c peptide regulates adipose homeostasis to prevent ovariectomy-induced metabolic dysfunction - Huanyu Lu; Ming Wei; Yue Zhai; Qingyang Li; Zichen Ye; Li Wang; Wenjing Luo; Jingyuan Chen; Zifan Lu (Journal of Molecular Medicine, 2019)

A new triterpene diglycoside from the roots of Bupleurum chinense DC. and its inhibitory effect on adipogensis in 3T3-L1 cells - Yujing Feng; Zhou-Wei Wu; Yanyan Luo; Liang Chen; Yufeng Cao; Lun Wang; Aftab Yaseen; Bin Chen; Ashfaq Ahmad Khan; Ming-Kui Wang; Guo-Lin Zhang; Xin-Feng Wang; et al. (Medicinal Chemistry Research, 2019)

Reduced carbon use efficiency and increased microbial turnover with soil warming - Jianwei Li; Gangsheng Wang; Melanie A. Mayes; Steven D. Allison; Serita D. Frey; Zheng Shi; Xiao‐Ming Hu; Yiqi Luo; Jerry M. Melillo (Global Change Biology, 2019)
Global soil carbon (C) stocks are expected to decline with warming, and changes in microbial processes are key to this projection. However, warming responses of critical microbial parameters such as carbon use efficiency (CUE) and biomass turnover (rB) are not well understood. Here, we determine these parameters using a probabilistic inversion approach that integrates a microbial‐enzyme model with 22 years of carbon cycling measurements at Harvard Forest. We find that increasing temperature reduces CUE but increases rB, and that two decades of soil warming increases the temperature sensitivities of CUE and rB. These temperature sensitivities, which are derived from decades‐long field observations, contrast with values obtained from short‐term laboratory experiments. We also show that long‐term soil C flux and pool changes in response to warming are more dependent on the temperature sensitivity of CUE than that of rB. Using the inversion‐derived parameters, we project that chronic soil warming at Harvard Forest over six decades will result in soil C gain of

Loop-mediated isothermal amplification (LAMP) detection of Phytophthora hibernalis, P. syringae and P. cambivora - Guan-Rong Li; Guo-Ming Huang; Lin-Hui Zhu; Dajin Lv; Baohong Cao; Fang Liao; Jia-Feng Luo (Journal of Plant Pathology, 2019)

Direct and indirect effects of climate on richness drive the latitudinal diversity gradient in forest trees - Chengjin Chu; James A. Lutz; Kamil Král; Tomáš Vrška; Xue Yin; Jonathan A. Myers; Iveren Abiem; Alfonso Alonso; Norm Bourg; David F.R.P. Burslem; Min Cao; Hazel Chapman; et al. (Ecology Letters, 2019)
Climate is widely recognised as an important determinant of the latitudinal diversity gradient. However, most existing studies make no distinction between direct and indirect effects of climate, which substantially hinders our understanding of how climate constrains biodiversity globally. Using data from 35 large forest plots, we test hypothesised relationships amongst climate, topography, forest structural attributes (stem abundance, tree size variation and stand basal area) and tree species richness to better understand drivers of latitudinal tree diversity patterns. Climate influences tree richness both directly, with more species in warm, moist, aseasonal climates and indirectly, with more species at higher stem abundance. These results imply direct limitation of species diversity by climatic stress and more rapid (co‐)evolution and narrower niche partitioning in warm climates. They also support the idea that increased numbers of individuals associated with high primary productivity are partitioned to support a greater number of species.

Genetic diversity and large-scale connectivity of the scleractinian coral Porites lutea in the South China Sea - Wen Huang; Ming Li; Kefu Yu; Yinghui Wang; Jingjing Li; Jiayuan Liang; Yanqiu Luo; Xueyong Huang; Zhenjun Qin; Guanghua Wang; Hongfei Su; Fen Wei (Coral Reefs, 2018)

Cryo-EM structure reveals cylindrical nucleocapsids from two polydnaviruses - Ji-Hui Cui; Ya-Bin Chen; Ming Li; Qiu-Chen Cai; Li-Dan Zhang; Zi-Yun Lu; Jian-Cheng Li; Qi-Shun Zhu; Gang Ji; Kai-Jun Luo (Archives of Virology, 2018)

Origin of Early Cretaceous Guandian adakitic pluton in central eastern China: partial melting of delaminated lower continental crust triggered by ridge subduction - Ze-Bin Luo; Shuo Xue; Li-Peng Zhang; He Li; Cong-Ying Li; Hong Zhang; Yu-Long Liu; Ming-Xing Ling; Weidong Sun (International Geology Review, 2018)

Dendrocoumarin: a new benzocoumarin derivative from the stem of Dendrobium nobile - Xue-Ming Zhou; Bin Zhang; Guang-Ying Chen; Chang-Ri Han; Kun-Chi Jiang; Ming-Yue Luo; Bo-Zheng Meng; Wen-Xin Li; Shi-Dai Lin (Natural Product Research, 2018)

Corn yields with organic and inorganic amendments under changing climate - Ping Liu; Haijun Zhao; Yan Li; Zhaohui Liu; Xinhao Gao; Yingpeng Zhang; Ming Sun; Ziwen Zhong; Jiafa Luo (Nutrient Cycling in Agroecosystems, 2018)

Social Isolation During Adolescence Induces Anxiety Behaviors and Enhances Firing Activity in BLA Pyramidal Neurons via mGluR5 Upregulation - Song Lin; Xin Li; Yi-Hua Chen; Feng Gao; Hao Chen; Neng-Yuan Hu; Lang Huang; Zheng-Yi Luo; Ji-Hong Liu; Qiang-Long You; Ya-Nan Yin; Ze-Lin Li; et al. (Molecular Neurobiology, 2018)

SOX2-mediated inhibition of miR-223 contributes to STIM1 activation in phenylephrine-induced hypertrophic cardiomyocytes - Zhi-Hong Zhao; Jun Luo; Hai-xia Li; Sai-hua Wang; Xin-ming Li (Molecular and Cellular Biochemistry, 2018)

Re–Os dating of molybdenite and in-situ Pb isotopes of sulfides from the Lamo Zn–Cu deposit in the Dachang tin-polymetallic ore field, Guangxi, China - Hai Zhao; Wenchao Su; Peng Xie; Nengping Shen; Jiali Cai; Ming Luo; Jie Li; Zhian Bao (Acta Geochimica, 2018)

Human infection with a further evolved avian H9N2 influenza A virus in Sichuan, China - Jianan Xu; Shuang Li; Yong Yang; Bing Liu; Huiping Yang; Tiansu Li; Lin Zhang; Wei Li; Xiaohu Luo; Liquan Zhang; Ming Pan (Science China Life Sciences, 2018)

Effects of Boron Supplementation on Expression of Hsp70 in the Spleen of African Ostrich - Khaliq Haseeb; Jing Wang; Ke Xiao; Ke-li Yang; Peng-peng Sun; Xing-tong Wu; You Luo; Hui Song; Hua-zhen Liu; Ju-ming Zhong; Ke-mei Peng (Biological Trace Element Research, 2018)

Early Carboniferous ophiolite in central Qiangtang, northern Tibet: record of an oceanic back-arc system in the Palaeo-Tethys Ocean - Tian-Yu Zhang; Jian-Jun Fan; Cai Li; Chao-Ming Xie; Ming Wang; Yan-Wang Wu; Meng-Jing Xu; Wei Xu; Jin-Heng Liu; An-Bo Luo (International Geology Review, 2018)

In vivo toxicity assessment of aflatoxin B 1 -contaminated corn after ozone degradation - Xiaohu Luo; Ke Li; Jiali Xing; Lijun Qi; Ming Yang; Ren Wang; Li Wang; Yanan Li; Zhengxing Chen (Food Additives & Contaminants: Part A, 2018)

Identification of the genes in tea leafhopper, Empoasca onukii (Hemiptera: Cicadellidae), that encode odorant-binding proteins and chemosensory proteins using transcriptome analyses of insect heads - Lei Bian; Zhao-Qun Li; Long Ma; Xiao-Ming Cai; Zong-Xiu Luo; Zong-Mao Chen (Applied Entomology and Zoology, 2018)

Antioxidant enzyme activities of Folsomia candida and avoidance of soil metal contamination - Wencai Dai; Xin Ke; Zhu Li; Ming Gao; Longhua Wu; Peter Chiristie; Yongming Luo (Environmental Science and Pollution Research, 2018)

CLOCK rs1801260 Polymorphism is Associated with Susceptibility to Parkinson’s Disease in a Chinese Population - Fan Lou; Ming Li; Yan Ren; Xiao-Guang Luo; Na Liu; Xiaohong Li (Neuroscience Bulletin, 2017)

Complete plastid genomes of the genus Ammopiptanthus and identification of a novel 23-kb rearrangement - Lei Feng; Li-Fei Gu; Juan Luo; Ai-Si Fu; Qiong Ding; Siu-Ming Yiu; Jun-Xian He (Conservation Genetics Resources, 2017)

Multi-parametric analysis reveals enhanced G2-phase arrest of an optimized anti-HER2 antibody to inhibit breast cancer - Chunxia Qiao; Xiaoling Lang; Longlong Luo; Shusheng Geng; Ming Lv; Jing Geng; Xinying Li; Jiannan Feng; Beifen Shen; Yan Li (Biotechnology Letters, 2017)

Evaluation of European Schizophrenia GWAS Loci in Asian Populations via Comprehensive Meta-Analyses - Xiao Xiao; Xiong-jian Luo; Hong Chang; Zichao Liu; Ming Li (Molecular Neurobiology, 2017)

Molecular detection and phylogenetic analysis of viruses causing mosaic symptoms in new sugarcane varieties in China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (European Journal of Plant Pathology, 2017)

Climatic and geographic factors affect ecosystem multifunctionality through biodiversity in the Tibetan alpine grasslands - Ying Pan; Jun-xi Wu; Li-ming Luo; Yan-li Tu; Cheng-qun Yu; Xian-zhou Zhang; Yan-jun Miao; Yan Zhao; Jun-ling Yang (Journal of Mountain Science, 2017)

Erratum to: Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling‑Ling Zhang; Hu Chen; Mi Luo; Xiao‑Wei Zhang; Mei Deng; Jian Ma; Peng‑Fei Qi; Ji‑Rui Wang; Guo‑Yue Chen; Ya‑Xi Liu; Zhi‑En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Transposon insertion resulted in the silencing of Wx-B1n in Chinese wheat landraces - Ling-Ling Zhang; Hu Chen; Mi Luo; Xiao-Wei Zhang; Mei Deng; Jian Ma; Peng-Fei Qi; Ji-Rui Wang; Guo-Yue Chen; Ya-Xi Liu; Zhi-En Pu; Wei Li; et al. (Theoretical and Applied Genetics, 2017)

Determining the fluxes of ions (Pb2+, Cu2+ and Cd2+) at the root surface of wetland plants using the scanning ion-selective electrode technique - Lian-Zhen Li; Shun-Yang Yu; Willie J. G. M. Peijnenburg; Yong-Ming Luo (Plant and Soil, 2017)

Effects of Site-Mutations Within the 22 kDa No-Core Fragment of the Vip3Aa11 Insecticidal Toxin of Bacillus thuringiensis - Ming Liu; Rongmei Liu; Guoxing Luo; Haitao Li; Jiguo Gao (Current Microbiology, 2017)

Molecular Detection of Bru1 Gene and Identification of Brown Rust Resistance in Chinese Sugarcane Germplasm - Wen-Feng Li; Xiao-Yan Wang; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Jiong Yin; Zhi-Ming Luo (Sugar Tech, 2017)

Sodium P-Aminosalicylic Acid Improved Manganese-Induced Learning and Memory Dysfunction via Restoring the Ultrastructural Alterations and γ-Aminobutyric Acid Metabolism Imbalance in the Basal Ganglia - Chao-Yan Ou; Yi-Ni Luo; Sheng-Nan He; Xiang-Fa Deng; Hai-Lan Luo; Zong-Xiang Yuan; Hao-Yang Meng; Yu-Huan Mo; Shao-Jun Li; Yue-Ming Jiang (Biological Trace Element Research, 2017)

Phthalates in plastic bottled non-alcoholic beverages from China and estimated dietary exposure in adults - Ji-Feng Yang; Li-Ming Yang; Li-Ying Zheng; Guang-Guo Ying; Cheng-Bin Liu; Sheng-Lian Luo (Food Additives & Contaminants Part B-Surveillance, 2017)

A bifunctional type III polyketide synthase from raspberry (Rubus idaeus L.) with both chalcone synthase and benzalacetone synthase activity - Hui-Li Guo; Ya-Dong Yang; Ya-Di Ma; Wen-Bin Liu; Jing Feng; Zai-Qi Luo; He-Shu Lu; Chun-Mei Liu; Ming-Feng Yang; You-Nian Wang; Lan-Qing Ma (Journal of Plant Biochemistry and Biotechnology, 2017)

A polydnaviral genome of Microplitis bicoloratus bracovirus and molecular interactions between the host and virus involved in NF-κB signaling - Dong-Shuai Yu; Ya-Bin Chen; Ming Li; Ming-Jun Yang; Yang Yang; Jian-Sheng Hu; Kai-Jun Luo (Archives of Virology, 2016)

Soil nitrate–N residue, loss and accumulation affected by soil surface management and precipitation in a winter wheat-summer fallow system on dryland - Gang He; Zhaohui Wang; Fucui Li; Jian Dai; Xiaolong Ma; Qiang Li; Cheng Xue; Hanbing Cao; Sen Wang; Hui Liu; Laichao Luo; Ming Huang; et al. (Nutrient Cycling in Agroecosystems, 2016)

MAOA Variants and Genetic Susceptibility to Major Psychiatric Disorders - Zichao Liu; Liang Huang; Xiong-jian Luo; Lichuan Wu; Ming Li (Molecular Neurobiology, 2016)

Lead Exposure Impairs Hippocampus Related Learning and Memory by Altering Synaptic Plasticity and Morphology During Juvenile Period - Tao Wang; Rui-Li Guan; Ming-Chao Liu; Xue-Feng Shen; Jing Yuan Chen; Ming-Gao Zhao; Wen-Jing Luo (Molecular Neurobiology, 2016)

Cerebral blood flow changes in hemodialysis and peritoneal dialysis patients: an arterial-spin labeling MR imaging - Xiao Lu Jiang; Ji Qiu Wen; Long Jiang Zhang; Gang Zheng; Xue Li; Zhe Zhang; Ya Liu; Li Juan Zheng; Long Wu; Hui Juan Chen; Xiang Kong; Song Luo; et al. (Metabolic Brain Disease, 2016)

Adaptive evolution of interleukin-3 (IL3), a gene associated with brain volume variation in general human populations - Ming Li; Liang Huang; Kaiqin Li; Yongxia Huo; Chunhui Chen; Jinkai Wang; Jiewei Liu; Zhenwu Luo; Chuansheng Chen; Qi Dong; Yong-gang Yao; Bing Su; et al. (Human Genetics, 2016)

Sodium Para-aminosalicylic Acid Protected Primary Cultured Basal Ganglia Neurons of Rat from Manganese-Induced Oxidative Impairment and Changes of Amino Acid Neurotransmitters - Shao-Jun Li; Yong Li; Jing-Wen Chen; Zong-Xiang Yuan; Yu-Huan Mo; Guo-Dong Lu; Yue-Ming Jiang; Chao-Yan Ou; Fang Wang; Xiao-Wei Huang; Yi-Ni Luo; Shi-Yan Ou; et al. (Biological Trace Element Research, 2016)

Involvement of NADPH oxidases and non-muscle myosin light chain in senescence of endothelial progenitor cells in hyperlipidemia - Ting-Bo Li; Jie-Jie Zhang; Bin Liu; Wei-Qi Liu; Yan Wu; Xiao-Ming Xiong; Xiu-Ju Luo; Qi-Lin Ma; Jun Peng (Naunyn-Schmiedeberg's Archives of Pharmacology, 2016)

The effects of abscisic acid (ABA) addition on cadmium accumulation of two ecotypes of Solanum photeinocarpum - Jin Wang; Lijin Lin; Li Luo; Ming’an Liao; Xiulan Lv; Zhihui Wang; Dong Liang; Hui Xia; Xun Wang; Yunsong Lai; Yi Tang (Environmental Monitoring and Assessment, 2016)

Microsatellite records for volume 8, issue 1 - Maria Cristina Arias; Stéphane Aulagnier; Erin F. Baerwald; Robert M. R. Barclay; Jacqueline Silva Batista; Rochelle R. Beasley; Rodrigo A. Bezerra; Frédéric Blanc; Eli S. Bridge; Maria Teresa Cabria; Lívia Izabela Caputo; Jie Chen; et al. (Conservation Genetics Resources, 2016)

Phytosterol content and the campesterol:sitosterol ratio influence cotton fiber development: role of phytosterols in cell elongation - Shasha Deng; Ting Wei; Kunling Tan; Mingyu Hu; Fang Li; Yunlan Zhai; Shue Ye; Yuehua Xiao; Lei Hou; Yan Pei; Ming Luo (Science China Life Sciences, 2016)

The impact of nitrogen amendment and crop growth on dissolved organic carbon in soil solution - Xiao-guo Wang; Chang-sheng Li; Yong Luo; Ke-ke Hua; Ming-hua Zhou (Journal of Mountain Science, 2016)

Social Isolation During Adolescence Strengthens Retention of Fear Memories and Facilitates Induction of Late-Phase Long-Term Potentiation - Ji-Hong Liu; Qiang-Long You; Mei-Dan Wei; Qian Wang; Zheng-Yi Luo; Song Lin; Lang Huang; Shu-JI Li; Xiao-Wen Li; Tian-Ming Gao (Molecular Neurobiology, 2015)

Neuroprotective effect of bisabolangelone on hydrogen peroxide-induced neurotoxicity in SH-SY5Y cells - Jun-Zhi Wang; Xi-Ming Yan; Zi-Cheng Li; Hua-Jun Luo; Nian-Yu Huang; Wei-Qiao Deng (Medicinal Chemistry Research, 2015)

Repair of articular cartilage defects in rabbits through tissue-engineered cartilage constructed with chitosan hydrogel and chondrocytes - Ming Zhao; Zhu Chen; Kang Liu; Yu-qing Wan; Xu-dong Li; Xu-wei Luo; Yi-guang Bai; Ze-long Yang; Gang Feng (Journal of Zhejiang University-SCIENCE B, 2015)

Screening for simple sequence repeat markers in Puccinia striiformis tritici based on genomic sequence - Gang-ming Zhan; Fu-ping Wang; Huai-yong Luo; Shu-chang Jiang; Wen-ming Zheng; Li-li Huang; Zhen-sheng Kang (Journal of Zhejiang University-SCIENCE B, 2015)

Triple Recycling Processes Impact Systemic and Local Bioavailability of Orally Administered Flavonoids - Peimin Dai; Lijun Zhu; Feifei Luo; Linlin Lu; Qiang Li; Liping Wang; Ying Wang; Xinchun Wang; Ming Hu; Zhongqiu Liu (The AAPS Journal, 2015)

Systemic nematicidal activity and biocontrol efficacy of Bacillus firmus against the root-knot nematode Meloidogyne incognita - Jing Xiong; Qiaoni Zhou; Haiyan Luo; Liqiu Xia; Lin Li; Ming Sun; Ziquan Yu (World Journal of Microbiology and Biotechnology, 2015)

Prefrontal cortical α2A-adrenoceptors and a possible primate model of attention deficit and hyperactivity disorder - Chao-Lin Ma; Xuan Sun; Fei Luo; Bao-Ming Li (Neuroscience Bulletin, 2015)

Identification of Sugarcane White Leaf Phytoplasma in Fields and Quaratine Sugarcane Samples in Yunnan Province, China - Xiao-Yan Wang; Wen-Feng Li; Ying-Kun Huang; Rong-Yue Zhang; Hong-Li Shan; Zhi-Ming Luo; Jiong Yin; Ke Shen (Sugar Tech, 2015)

Genetic and physical mapping of powdery mildew resistance gene MlHLT in Chinese wheat landrace Hulutou - Zhenzhong Wang; Hanwen Li; Deyun Zhang; Li Guo; Jiaojiao Chen; Yongxing Chen; Qiuhong Wu; Jingzhong Xie; Yan Zhang; Qixin Sun; Jan Dvorak; Ming-cheng Luo; et al. (Theoretical and Applied Genetics, 2015)

Youngia erythrocarpa, a newly discovered cadmium hyperaccumulator plant - Lijin Lin; Bo Ning; Ming’an Liao; Yajun Ren; Zhihui Wang; Yingjie Liu; Ji Cheng; Li Luo (Environmental Monitoring and Assessment, 2015)

Comparative genomic sequence analysis of Chinese orf virus strain NA1/11 with other parapoxviruses - Wei Li; Wenbo Hao; Yongzheng Peng; Chaohui Duan; Chengbi Tong; Deguang Song; Feng Gao; Ming Li; Daniel L. Rock; Shuhong Luo (Archives of Virology, 2015)

Lipopolysaccharides Upregulate Hepcidin in Neuron via Microglia and the IL-6/STAT3 Signaling Pathway - Zhong-Ming Qian; Xuan He; Tuo Liang; Ka-Chun Wu; Yik-Chun Yan; Li-Na Lu; Guang Yang; Qian Qian Luo; Wing-Ho Yung; Ya Ke (Molecular Neurobiology, 2014)

KIM-1 and NGAL as biomarkers of nephrotoxicity induced by gentamicin in rats - Qi-hui Luo; Meng-lu Chen; Feng-jiao Sun; Zheng-li Chen; Ming-yang Li; Wen Zeng; Li Gong; An-chun Cheng; Xi Peng; Jing Fang; Li Tang; Yi Geng (Molecular and Cellular Biochemistry, 2014)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Susceptibility of the tick Haemaphysalis qinghaiensis to isolates of the fungus Metarhizium anisopliae in China - Qiaoyun Ren; Ming Sun; Guiquan Guan; Zhijie Liu; Ze Chen; Aihong Liu; Youquan Li; Miling Ma; Jifei Yang; Qingli Niu; Junlong Liu; Xueqing Han; et al. (Experimental and Applied Acarology, 2014)

Detection of polyketide synthase and nonribosomal peptide synthetase biosynthetic genes from antimicrobial coral-associated actinomycetes - Jie Li; Jun-De Dong; Jian Yang; Xiong-Ming Luo; Si Zhang (Antonie van Leeuwenhoek, 2014)

Engrailed-2 is down-regulated but also ectopically expressed in clear cell renal cell carcinoma - Cai-yong Lai; Bin Pan; Yun Luo; Wei-bo Liang; Jie Chen; Dong-ming Ye; Ji-Nan Guo; Li Li; Ze-xuan Su (Molecular Biology Reports, 2014)

Biological control of Ralstonia wilt, Phytophthora blight, Meloidogyne root-knot on bell pepper by the combination of Bacillus subtilis AR12, Bacillus subtilis SM21 and Chryseobacterium sp. R89 - Hong-Xia Liu; Shi-Mo Li; Yu-Ming Luo; Lai-Xin Luo; Jian-Qiang Li; Jian-Hua Guo (European Journal of Plant Pathology, 2014)

Temperature influence on biological phosphorus removal induced by aerobic/extended-idle regime - Hong-bo Chen; Dong-bo Wang; Xiao-ming Li; Qi Yang; Kun Luo; Guang-ming Zeng (Environmental Science and Pollution Research, 2014)

CATS derived SNPs discovery in the golden snub-nosed monkey (Rhinopithecus roxellanae) - Chen Cheng; Shuzhen Li; Boshi Wang; Maofang Luo; Yunxia Yang; Guang Yang; Ming Li (Conservation Genetics Resources, 2014)

Application of Endobronchial Ultrasound-Guided Transbronchial Needle Aspiration in the Management of Mediastinal and Hilar Lymphadenopathy Without Intrapulmonary Mass: Experience from the Largest Cancer Center of Southern China - Guang-yu Luo; Pei-qiang Cai; Jie-hua He; Jian-jun Li; Yin Li; Hong-bo Shan; Rong Zhang; Xiao-yan Gao; Xiang-ming Lao; Guo-liang Xu (Cell Biochemistry and Biophysics, 2013)

Polymorphism of follicle stimulating hormone beta (FSHβ) subunit gene and its association with litter traits in giant panda - Xiaoyu Huang; Desheng Li; Jiwen Wang; Yan Huang; Chunchun Han; Guiquan Zhang; Zhi Huang; Honglin Wu; Ming Wei; Guosong Wang; Haiping Hu; Tao Deng; et al. (Molecular Biology Reports, 2013)

Molecular cloning of vasa gene and the effects of LHRH-A on its expression in blue tilapia Oreochromis aureus - Jun Xiao; Yongju Luo; Libing Chen; Li Yang; Yulin Huang; Zhongbao Guo; Enyan Guo; Zhanyang Tang; Ming Zhang; Xi Gan (Fish Physiology and Biochemistry, 2013)

Revealing storage-area relationship of open water in ungauged subalpine wetland — Napahai in Northwest Yunnan, China - Jie Li; Jin-ming Hu; Wei Deng; Sheng-li Huang; Hai-feng Jia; Chun-ling Zhu; Huai-xiu Luo (Journal of Mountain Science, 2013)
Mountains and plateaus in Southwest China contain many subalpine and alpine wetlands, with significant hydroecological functions. But ungauged or poorly gauged conditions limit the study and understanding of hydrological regimes of these wetland types. This study selects an ungauged subalpine wetland — Napahai in Northwest Yunnan, China — as a case for developing a practical approach to revealing its storage-area relationship of open water. A Trimble R8 GNSS (Global Navigation Satellites Systems) RTK (Real-time Kinematic system) and sonar fathometer were used to survey fine-resolution elevation data and generate a digital elevation model of the Napahai Wetland. Forty-four Landsat images from 1987 to 2011 were collected, and the Normalized Difference Water Index was used to classify open water features in the area. The area of open water in Napahai was calculated for each phase. With these data and a developed conceptual model, the storage of open water for each phase was estimated using ArcGIS tools. Both storage and area of open water showed significant intra-annual and inter-annual variations. In the rainy season, the monthly change of average storage of open water in Napahai showed about 1–2 months lag behind mean monthly rainfall. The storage-area relationship of open water was well fit by a power function equation ( R 2 ≈0.91, n =44). This study indicates that if detailed elevations are available for similarly ungauged subalpine wetlands in Southwest China, researchers can use this practical approach to estimate multi-temporal areas and storages and reveal the storage-area relationship of open water in the wetlands. The study provided valuable information of this case wetland for optimizing its hydro-ecological managements and a new method to wetland researchers and managers for the hydrological study of similarly ungauged wetland complex.

Amyloid plaque pathogenesis in 5XFAD mouse spinal cord: retrograde transneuronal modulation after peripheral nerve injury - Jian-Ming Li; Zhi-Qin Xue; Si-Hao Deng; Xue-Gang Luo; Peter R. Patrylo; Gregory W. Rose; Huaibin Cai; Yan Cai; Xiao-Xin Yan (Neurotoxicity Research, 2013)

Synthesis and evaluation in vitro of 1-[2-(10-dihydroartemisininoxy) ethyl]-3-phenylurea derivatives as potential agents against cancer - Wei Luo; Ming-yu Xia; Takashi Ikejima; Li-hua Li; Chun Guo (Medicinal Chemistry Research, 2013)

Effective inhibition of mRNA accumulation and protein expression of H5N1 avian influenza virus NS1 gene in vitro by small interfering RNAs - Hanwei Jiao; Li Du; Yongchang Hao; Ying Cheng; Jing Luo; Wenhua Kuang; Donglin Zhang; Ming Lei; Xiaoxiao Jia; Xiaoru Zhang; Chao Qi; Hongxuan He; et al. (Folia Microbiologica, 2013)

Priming of Anti-Herbivore Defense in Tomato by Arbuscular Mycorrhizal Fungus and Involvement of the Jasmonate Pathway - Yuan Yuan Song; Mao Ye; Chuan You Li; Rui Long Wang; Xiao Chen Wei; Shi Ming Luo; Ren Sen Zeng (Journal of Chemical Ecology, 2013)

Quantification of serum HBXAP DNA in lung cancer patients by quantitative fluorescent polymerase chain reaction - Yu-Lei Hou; Hui Chen; Ming-Jian Ge; Feng-Zeng Li; Cheng-Jun Xue; Yan-Feng Wu; Hai-Xia Luo (Molecular Biology Reports, 2013)

Adaptive finite element modeling of marine controlled-source electromagnetic fields in two-dimensional general anisotropic media - Yuguo Li; Ming Luo; Jianxin Pei (Journal of Ocean University of China, 2013)

Molecular epidemiology of PRRSV from China’s Guangxi Province between 2007 and 2009 - Hong-Yun Zhang; Jing-Jing Liang; Xian-Ming Meng; Hui Li; Jian Yang; Li-Juan Su; Hong-Pu Zhang; Lin-Juan Xie; Xiao-Xia He; Yan-Sheng Li; Shan Yin; Xiao-Quan Li; et al. (Virus Genes, 2013)

Nuclear DNA content variation of three Miscanthus species in China - Xi Li; Die Hu; Manman Luo; Ming Zhu; Xinwei Li; Fan Luo; Jianqiang Li; Juan Yan (Genes & Genomics, 2013)

Activation of Wnt/β-catenin Pathway by Exogenous Wnt1 Protects SH-SY5Y Cells Against 6-Hydroxydopamine Toxicity - Lei Wei; Congcong Sun; Ming Lei; Guofei Li; Li Yi; Feifei Luo; Yi Li; Li Ding; Zhuolin Liu; Shaomin Li; Pingyi Xu (Journal of Molecular Neuroscience, 2013)

Wavelet analysis of lumbar muscle oxygenation signals during whole-body vibration: implications for the development of localized muscle fatigue - Zengyong Li; Ming Zhang; Guoqiang Chen; Site Luo; Feifei Liu; Jianping Li (European Journal of Applied Physiology, 2012)

Formation of the world's largest molybdenum metallogenic belt: a plate-tectonic perspective on the Qinling molybdenum deposits - Cong-Ying Li; Fang-Yue Wang; Xi-Luo Hao; Xing Ding; Hong Zhang; Ming-Xing Ling; Ji-Bin Zhou; Yi-Liang Li; Wei-Ming Fan; Wei-Dong Sun (International Geology Review, 2012)

A novel gene IBF1 is required for the inhibition of brown pigment deposition in rice hull furrows - Tian Shao; Qian Qian; Ding Tang; Jun Chen; Ming Li; Zhukuan Cheng; Qiong Luo (Theoretical and Applied Genetics, 2012)

Human influence on the population decline and loss of genetic diversity in a small and isolated population of Sichuan snub-nosed monkeys (Rhinopithecus roxellana) - Zong Fei Chang; Mao Fang Luo; Zhi Jin Liu; Jing Yuan Yang; Zuo Fu Xiang; Ming Li; Linda Vigilant (Genetica, 2012)

Identification and characterization of monoclonal antibodies against the ORFV059 protein encoded by Orf virus - Hong Li; Zhangyong Ning; Wenbo Hao; Shimeng Zhang; Xiaoqing Liao; Ming Li; Shuhong Luo (Virus Genes, 2012)

Inhibition of matrine against gastric cancer cell line MNK45 growth and its anti-tumor mechanism - Cong Luo; Hai Jun Zhong; Li Ming Zhu; Xian Guo Wu; Jie Er Ying; Xiao Hong Wang; Wang Xia LÜ; Qi Xu; Yong Liang Zhu; Jian Huang (Molecular Biology Reports, 2012)

The Group III Two-Component Histidine Kinase AlHK1 is Involved in Fungicides Resistance, Osmosensitivity, Spore Production and Impacts Negatively Pathogenicity in Alternaria longipes - Yi Yong Luo; Jin Kui Yang; Ming Liang Zhu; Chen Jian Liu; Hai Yan Li; Ze Bao Lu; Wen Zheng Pan; Zhong Hua Zhang; Wei Bi; Ke Qin Zhang (Current Microbiology, 2012)

Molecular cloning and functional characterization of MdSOS2 reveals its involvement in salt tolerance in apple callus and Arabidopsis - Da-Gang Hu; Ming Li; Hua Luo; Qing-Long Dong; Yu-Xin Yao; Chun-Xiang You; Yu-Jin Hao (Plant Cell Reports, 2012)

The molecular basis for the inhibition of human cytochrome P450 1A2 by oroxylin and wogonin - Yong-Xian Shao; Peng Zhao; Zhe Li; Ming Liu; Peiqing Liu; Min Huang; Hai-Bin Luo (European Biophysics Journal, 2012)

Method for generating SPOT natural-colour composite images based on spectrum machine learning - Changming Zhu; Jiancheng Luo; Dongping Ming; Zhanfeng Shen; Junli Li (International Journal of Remote Sensing, 2012)

A meta-analysis of HLA-DR polymorphism and genetic susceptibility to idiopathic dilated cardiomyopathy - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Wei Shen; Hai-Ming Shi; Yong Li (Molecular Biology Reports, 2012)

Intratumoral Heterogeneity Determines Discordant Results of Diagnostic Tests for Human Epidermal Growth Factor Receptor (HER) 2 in Gastric Cancer Specimens - Jiyuan Yang; Hesheng Luo; Yan Li; Junchuan Li; Zhiqiang Cai; Xiaoyan Su; Danqing Dai; Wei Du; Tingxuan Chen; Ming Chen (Cell Biochemistry and Biophysics, 2012)

Isolation and performance evaluation of halotolerant phosphate solubilizing bacteria from the rhizospheric soils of historic Dagong Brine Well in China - Wen-liang Xiang; Hua-zhong Liang; Sen Liu; Fan Luo; Jie Tang; Ming-yuan Li; Zhen-ming Che (World Journal of Microbiology and Biotechnology, 2011)

Induction of DIMBOA accumulation and systemic defense responses as a mechanism of enhanced resistance of mycorrhizal corn (Zea mays L.) to sheath blight - Yuan Yuan Song; Man Cao; Li Jun Xie; Xiao Ting Liang; Ren Sen Zeng; Yi Juan Su; Jing Hua Huang; Rui Long Wang; Shi Ming Luo (Mycorrhiza, 2011)

Effects of sediment size on transport capacity of overland flow on steep slopes - Guang-Hui Zhang; Li-Li Wang; Ke-Ming Tang; Rong-Ting Luo; X. C. Zhang (Hydrological Sciences Journal, 2011)

A disease associated with phytoplasma in Parthenium hysterophorus - Zhengnan Li; Lei Zhang; Haiyan Che; Hongguang Liu; Ming Chi; Daquan Luo; Yan Li; Wang Chen; Yunfeng Wu (Phytoparasitica, 2011)

Development of genetically engineered CD4+ and CD8+ T cells expressing TCRs specific for a M. tuberculosis 38-kDa antigen - Wei Luo; Xiao-Bing Zhang; Yong-Ta Huang; Pei-Pei Hao; Zhen-Min Jiang; Qian Wen; Ming-Qian Zhou; Qi Jin; Li Ma (Journal of Molecular Medicine, 2011)

The effects of simvastatin on angiogenesis: studied by an original model of atherosclerosis and acute myocardial infarction in rabbit - Wei Shen; Hai-Ming Shi; Wei-Hu Fan; Xin-Ping Luo; Bo Jin; Yong Li (Molecular Biology Reports, 2011)

Phylogenetic analysis of the E2 gene of classical swine fever virus from the Guangxi Province of southern China - Ting Rong Luo; Su-huan Liao; Xian-shi Wu; Li Feng; Zhao-Xia Yuan; Hui Li; Jing-Jing Liang; Xian-Ming Meng; Hong-Yun Zhang (Virus Genes, 2011)

Rice Gene OsDSR-1 Promotes Lateral Root Development in Arabidopsis Under High-Potassium Conditions - Xu Ming Yin; Pedro S. C. F. Rocha; Man Ling Wang; Yu Xin Zhu; Luo Ye Li; Shu Feng Song; Xinjie Xia (Journal of Plant Biology, 2011)

Disseminated Penicillium Marneffei Infection in an SLE Patient: A Case Report and Literature Review - Di-Qing Luo; Ming-Chun Chen; Jun-Hua Liu; Zhi Li; Hui-Ting Li (Mycopathologia, 2011)

Dynamic response of ginsenosides in American ginseng to root fungal pathogens - Xiao Lin Jiao; Wu Bi; Ming Li; Yong Luo; Wei Wei Gao (Plant and Soil, 2011)

Estimation of water dynamics in a vertical-flow constructed wetland with a growing plant species - Ying Ouyang; Shi Ming Luo; Li Hua Cui; Ying Hu Liu; Zhong Qin (Journal of Soils and Sediments, 2010)

Cardiac matrix remodeling following intracoronary cell transplantation in dilated cardiomyopathic rabbits - Bo Jin; Xin-Ping Luo; Huan-Chun Ni; Yong Li; Hai-Ming Shi (Molecular Biology Reports, 2010)

A hybrid promoter-containing vector for direct cloning and enhanced expression of PCR-amplified ORFs in mammalian cells - Lei-ming You; Jun Luo; Ai-ping Wang; Gai-ping Zhang; Hai-bo Weng; Ya-nan Guo; Yun-chao Liu; Qiao-mu Li; Man Teng (Molecular Biology Reports, 2010)

Characteristics and sources of atmospheric polycyclic aromatic hydrocarbons (PAHs) in Shanghai, China - Xian Yu Wang; Qing Bo Li; Yong Ming Luo; Qian Ding; Lian Min Xi; Jian Min Ma; Yan Li; Yi Peng Liu; Cui Li Cheng (Environmental Monitoring and Assessment, 2010)

Genetic analysis of strains of Japanese Encephalitis Virus isolated from swine in central China - Jian-Ming Fan; Jun Luo; Lu Chen; Man Teng; Dan Bu; Fang-Yu Wang; Li Wang; Chuan-Qing Wang; Gai-Ping Zhang (Virus Genes, 2010)

Leaf Wilting Movement Can Protect Water-Stressed Cotton (Gossypium hirsutum L.) Plants Against Photoinhibition of Photosynthesis and Maintain Carbon Assimilation in the Field - Ya-Li Zhang; Hong-Zhi Zhang; Ming-Wei Du; Wei Li; Hong-Hai Luo; Wah-Soon Chow; Wang-Feng Zhang (Journal of Plant Biology, 2010)

Preparation and Quality Test of Superparamagnetic Iron Oxide Labeled Antisense Oligodeoxynucleotide Probe: A Preliminary Study - Ming Wen; Bibo Li; Yu Ouyang; Yi Luo; Shaolin Li (Annals of Biomedical Engineering, 2009)

Evidence for programmed cell death and activation of specific caspase-like enzymes in the tomato fruit heat stress response - Gui-Qin Qu; Xiang Liu; Ya-Li Zhang; Dan Yao; Qiu-Min Ma; Ming-Yu Yang; Wen-Hua Zhu; Shi Yu; Yun-Bo Luo (Planta, 2009)

Infectivity and propagation of attenuated infectious bursal disease virus in the chicken B-lymphocyte cell line DT40 - Jun Luo; Gai-Ping Zhang; Jian-Ming Fan; Man Teng; Lei-Ming You; Ling Zhou; Rui-Guang Deng; Xuan-Nian Wang; Yan-Yan Yang; Li Wang; Guang-Xu Xing; Na Cheng (Archives of Virology, 2009)

Activation of the integrins α5β1 and αvβ3 and focal adhesion kinase (FAK) during arteriogenesis - Wei-Jun Cai; Ming Bo Li; Xiaoqiong Wu; Song Wu; Wu Zhu; Dan Chen; Mingying Luo; Inka Eitenmüller; Andreas Kampmann; Jutta Schaper; Wolfgang Schaper (Molecular and Cellular Biochemistry, 2009)

Ambient air monitoring of Beijing MSW logistics facilities in 2006 - Chun-Ping Li; Guo-Xue Li; Yi-Ming Luo; Yan-Fu Li (Environmental Monitoring and Assessment, 2008)

Litter pool sizes, decomposition, and nitrogen dynamics in Spartina alterniflora-invaded and native coastal marshlands of the Yangtze Estuary - Cheng Zhang Liao; Yi Qi Luo; Chang Ming Fang; Jia Kuan Chen; Bo Li (Oecologia, 2008)

Interaction of MT1-MMP and laminin-5γ2 chain correlates with metastasis and invasiveness in human esophageal squamous cell carcinoma - Xiao-Ming Shen; Yu-Peng Wu; Yan-Bin Feng; Man-Li Luo; Xiao-Li Du; Yu Zhang; Yan Cai; Xin Xu; Ya-Ling Han; Xun Zhang; Qi-Min Zhan; Ming-Rong Wang (Clinical & Experimental Metastasis, 2007)

Acetylene-Substituted Two-Photon Absorbing Molecules With Rigid Elongated Pi-Conjugation: Synthesis, Spectroscopic Properties and Two-Photon Fluorescence Cell Imaging Applications - Bo Liu; Hai-Li Zhang; Jun Liu; Zhen-Li Huang; Yuan-Di Zhao; Qing-Ming Luo (Journal of Fluorescence, 2007)

Seasonal Variation in the Activity Patterns and Time Budgets of Trachypithecus francoisi in the Nonggang Nature Reserve, China - Qihai Zhou; Fuwen Wei; Chengming Huang; Ming Li; Baoping Ren; Bang Luo (International Journal of Primatology, 2007)

Proteomic profiling of proteins dysregulted in Chinese esophageal squamous cell carcinoma - Xiao-Li Du; Hai Hu; De-Chen Lin; Shu-Hua Xia; Xiao-Ming Shen; Yu Zhang; Man-Li Luo; Yan-Bin Feng; Yan Cai; Xin Xu; Ya-Ling Han; Qi-Min Zhan; et al. (Journal of Molecular Medicine, 2007)

Rice Allelopathy Induced by Methyl Jasmonate and Methyl Salicylate - Hai Hong Bi; Ren Sen Zeng; Li Ming Su; Min An; Shi Ming Luo (Journal of Chemical Ecology, 2007)

Mutational analysis of the GDD sequence motif of classical swine fever virus RNA-dependent RNA polymerases - Yujing Wang; Ming Xiao; Jun Chen; Weiqiong Zhang; Jianglan Luo; Kan Bao; Ming Nie; Jiakuan Chen; Bo Li (Virus Genes, 2007)

Diet and Food Choice of Trachypithecus francoisi in the Nonggang Nature Reserve, China - Qihai Zhou; Fuwen Wei; Ming Li; Chengming Huang; Bang Luo (International Journal of Primatology, 2006)

Comparison of genetic variation in populations of wild rice, Oryza rufipogon, plants and their soil seed banks - Gui-hua Liu; Li-ming Luo; Bin Wang; Wei Li; Zhiping Song (Conservation Genetics, 2006)

Discussion on the forming factors of dog-tooth crystal and stone coral in Furong cave, Chongqing city, China - Qiao Chen; Kun-li Luo; Ke Hu; Ming-xing Dong; Cheng-li Ye; Qiang Liu (Carbonates and Evaporites, 2006)

Species diversity of Lachnum (Helotiales, Hyaloscyphaceae) from temperate China - Ming Ye; Shu-qing Cao; Shao-tong Jiang; Li-jun Pan; Shui-zhong Luo; Xing-jiang Li (Journal of Zhejiang University-SCIENCE B, 2006)

Comparative genetic maps reveal extreme crossover localization in the Aegilops speltoides chromosomes - Ming-Cheng Luo; Karin R. Deal; Zu-Li Yang; Jan Dvorak (Theoretical and Applied Genetics, 2005)

Construction of a genetic linkage map and QTL analysis of fiber-related traits in upland cotton (Gossypium hirsutum L.) - Zheng-Sheng Zhang; Yue-Hua Xiao; Ming Luo; Xian-Bi Li; Xiao-Ying Luo; Lei Hou; De-Mou Li; Yan Pei (Euphytica, 2005)

Identification of a Naturally Occurring Recombinant Isolate of Sugarcane Mosaic Virus Causing Maize Dwarf Mosaic Disease - Yongwang Zhong; Anyuan Guo; Chunbo Li; Binquan Zhuang; Ming Lai; Chunhong Wei; Jingchu Luo; Yi li (Virus Genes, 2005)

Genetic analysis and breeding use of blast resistance in a japonica rice mutant R917 - Ming Xian Zhang; Jian Long Xu; Rong Ting Luo; De Shi; Zhi Kang Li (Euphytica, 2003)

Bioluminescence of Aequorea macrodactyla, a Common Jellyfish Species in the East China Sea - Ning-Shao Xia; Wen-Xin Luo; Jun Zhang; Xiao-Yan Xie; Hai-Jie Yang; Shao-Wei Li; Ming Chen; Mun-Hon Ng (Marine Biotechnology, 2002)